Kogia Records in Brazilian Equatorial and Southwestern Atlantic Oceans - Joao Pedro M. Mura; Raphael B. Machado; Yasmin P. Viana; Natalia Rodrigues‐Soares; Giovanne A. Ferreira; Larissa Kelmer L. Kascher; Barbara S. Silva; Lucia O. Alencar; Gabrieli M. Rodrigues; Franciele R. de Castro; Daniela F. Godoy; Jose L. Pizzorno; et al. (Marine Mammal Science, 2026)
The pygmy ( Kogia breviceps ) and dwarf ( Kogia sima ) sperm whales are cryptic cetaceans characterized by inconspicuous surfacing behavior, small group sizes, and deep‐diving habits, making visual detection particularly challenging. Here, we present the first broad‐scale passive acoustic monitoring (PAM) assessment of Kogia spp. occurrence along the Brazilian coast, spanning both the Equatorial Atlantic Ocean (EAO) and Southwestern Atlantic Ocean (SWAO). Across 25 survey campaigns, 504 survey days, and more than 6441 h of acoustic recordings, 94 acoustic detections were identified, predominantly within the Brazilian Equatorial Margin (BEM), resulting in substantially higher detection‐per‐unit‐effort values in the EAO than in the SWAO. Two rare visual‐acoustic encounters of Kogia sima were also documented, including one detection incorporated into the dataset. A total of 2796 echolocation clicks were analyzed, exhibiting the characteristic narrow‐band high‐frequency acoustic profile of Kogia spp. (mean peak frequency = 126.2 ± 3.8 kHz; mean −3 dB bandwidth = 4.7 ± 2.56 kHz; mean inter‐click interval = 141 ± 97 ms). Detections occurred across a broad bathymetric range (9–4411 m), and kernel density analyses revealed spatial heterogeneity in occurrence patterns, with recurrent detection areas concentrated within the BEM. Collectively, these findings demonstrate the effectiveness of PAM for studying elusive deep‐diving cetaceans and provide an important baseline for future ecological monitoring, impact assessment, and conservation efforts targeting Kogia spp. in the western Atlantic.

Integrating cytotoxicity and NMR-based metabolomics to uncover bioactive aporphine alkaloids and pentacyclic triterpenoids from Siparuna guianensis - Salva Asghar; Cibele A. Cesila; Gracimerio J. Guarneire; Samira C. C. Ludgero; Sandra B. R. Castro; Alessandra P. Carli; Caio César S. Alves; Danielle F. Dias; Marisi G. Soares; Nerilson M. Lima (Natural Product Research, 2026)

Spawning and nursery habitats of Macruronus magellanicus in the Chilean Patagonia: Implications of oceanographic conditions - Carlos Veroes; Leonardo R. Castro; Diego A. Narváez (Journal of Marine Systems, 2026)

Building local energy resilience: a global review of climate adaptation in local energy communities - Ian B. Benitez; Kristina P. Badec; Jose Carlo R. Dizon; Shobhakar Dhakal; Francis Andrei De Castro; Lourdes Anne Marasigan; Mark Anthony G. Teodoro; Malena Lozada Montanari; Annlouise Genevieve Castro (Theoretical and Applied Climatology, 2026)

Photocatalytic caffeine degradation and toxicity reduction using reduced graphene oxide-modified zinc telluride - A. J. Vilvert; P. D. Macruz; R. P. Nippes; H. C. L. Geraldino; L. V. de Castro-Hoshino; I. R. Bautitz; J. C. G. Moraes (International Journal of Environmental Science and Technology, 2026)
The occurrence of emerging pollutants in aquatic matrices has raised environmental concern because of their persistence and potential toxicity. This study assessed caffeine degradation and toxicity reduction using zinc telluride functionalized with reduced graphene oxide as heterogeneous photocatalyst. The catalysts were synthesized by the wet impregnation method with excess solvent, and characterized by physicochemical and optical techniques. The results indicated zinc telluride nanoparticles distributed on the surface of reduced graphene oxide sheets, together with changes in textural and optical properties, including a lower band gap for the composites. Photocatalytic tests were performed using a mercury vapor lamp emitting ultraviolet–visible radiation, with the main emission at 365 nm. The effects of reduced graphene oxide content, catalyst loading, initial caffeine concentration, and pH variation were evaluated. Under the tested experimental conditions, the composite containing 1.0% reduced graphene oxide showed the highest degradation performance, reaching 93% caffeine degradation in 85 min. The degradation profile was best described by the half-order kinetic model. The reduced photoluminescence intensity suggests lower electron–hole recombination, although direct confirmation of reactive species requires complementary analyses. Toxicity tests indicated lower Artemia salina mortality and improved Lactuca sativa germination after treatment with the 1.0% reduced graphene oxide-modified zinc telluride catalyst. The results indicate that reduced graphene oxide incorporation can improve caffeine photodegradation and reduce toxicity under the evaluated conditions.

Evaluation of water quality from tubular wells in Brazil - G. G. O. de Souza; J. W. G. Castro; R. S. da Cadorso; E. M. de Lima; J. F. L. de Pereira; M. P. da Silva; Y. T. C. da Santos; F. G. Rodriguês; J. G. M. da Costa; H. D. M. Coutinho; G. B. Brito (International Journal of Energy and Water Resources, 2026)

Barrier spatial structure of co-occurring spawning of three small pelagic fish in the Northern Patagonia Estuarine Zone of Chile - Juan Antón-Heredia; Luis A. Cubillos; Leonardo R. Castro (Environmental Biology of Fishes, 2026)

Back to the Future of qEEG: Lifespan Normative Modeling of Spectral Ratios and Functional Indices with Potential Applications to Therapeutic Monitoring - J. Bosch-Bayard; J. Guerrero-Sauzameda; R. I. Bosch-Bayard; R. Pérez-Elvira; A. Bosch-Castro; J. Sánchez-Rodríguez; A. Flores; K. Flores; E Resendiz-Flores; A. Ferrando; P. Ferrando; L. Galán-García; et al. (Brain Topography, 2026)
Quantitative EEG (qEEG) provides objective, millisecond-resolution measures of brain dynamics. Despite decades of methodological advances, clinically relevant derived indices—spectral power ratios, cognitive-emotional state markers, and physiological parameters—are typically reported as raw values without the normative context required for individualized clinical inference. To develop the first systematic age-dependent normative models for this family of derived qEEG indices using a multinational database, enabling probabilistic Z-score interpretation at the individual level with potential applications in objective therapeutic monitoring. Normative modeling was applied to the HarMNqEEG database ( n = 1,564 neurologically healthy participants, ages 5–97, 9 countries, eyes-closed resting state). Electrode-level Spectral Normalization (ESN) removed inter-individual and inter-device amplitude variability while preserving the neurophysiological interpretability of each index. Age-dependent normative trajectories were estimated using Generalized Additive Models for Location, Scale, and Shape (GAMLSS) with P-splines on log(age), allowing conditional mean and variance to vary non-linearly across the lifespan. GAMLSS modeling revealed significant non-linear age-dependent trajectories for all indices. Slow-wave-dominated ratios showed steep decreases from childhood to early adulthood, consistent with cortical maturation; alpha-dominated indices increased during adolescence before stabilizing. ESN normalization yielded well-calibrated normative residuals across the full age range for all indices, except Valence. For the Valence index, a quantile regression model is provided as the recommended normative reference due to its spike-and-slab marginal distribution. These normative models provide a principled, age-adjusted probabilistic framework for individual-level qEEG interpretation, based on eyes closed resting state recordings, laying the methodological groundwork for future clinical validation in diagnostic and therapeutic monitoring applications. The ESN strategy requires no knowledge of recording equipment, ensuring broad applicability across clinical and research settings.

Genomic diversity and high-risk lineages in clinical Escherichia coli from Mexico - Ángel Ibarra-Rodríguez; José R. Aguirre-Sánchez; José A. Medrano-Félix; Nohemí Castro-del Campo; Bruno Gómez-Gil; Irvin González-López; Hilary A. Beltrán-Sauceda; Cristóbal Chaidez-Quiroz; Nohelia Castro-del Campo (Archives of Microbiology, 2026)

From by-product to benefit: the effect of white grape marc extracts on European seabass growth, gut microbiota, immune status, and resistance to Vibrio harveyi - Miguel Castro; Rui Magalhães; Rafaela A. Santos; Isabel M. Cerezo; Bárbara Guedes; Ana Couto; Martín Pérez-Díaz; Ana M. Azevedo; Roberto Bermúdez; María I. Quiroga; Maria Celeiro; Marta Lores; et al. (Frontiers in Marine Science, 2026)
Aquaculture intensification has increased the susceptibility of farmed fish to infectious diseases, which are traditionally managed with antibiotics. Growing environmental concerns and the emergence of antimicrobial resistance, however, have driven the search for more sustainable approaches to disease management. White grape marc, a polyphenol-rich by-product of the wine-making industry with known antimicrobial and antioxidant properties, represents a promising functional extract for aquafeeds. This study evaluated the effects of three white grape marc extracts obtained within the NeoGiANT project, using alcohol (ELN), glycol (PLN), and ketone (ACA) solvents, on growth performance, oxidative status, immune response, disease resistance, and gut microbiota of European seabass ( Dicentrarchus labrax ) juveniles. Fish were fed with four isoproteic and isolipidic diets: a control diet (CTRL) and three diets supplemented with white grape marc extracts at 450 ppm of total polyphenolic content per kg of feed. Fish were distributed into triplicate groups and fed for 48 days. Dietary supplementation did not affect survival, growth performance, or feed utilization. However, fish fed the PLN450 diet showed improved protein efficiency and antioxidant status, with higher catalase activity and reduced lipid peroxidation. Immune and stress-related gene expression also tended to be lower in fish fed the PLN450 diet than in those fed the other diets, while gut microbiota composition remained largely unchanged. Following a Vibrio harveyi challenge, mortality did not differ significantly among groups, although fish receiving the supplemented diets showed higher absolute survival than those receiving the CTRL diet. Overall, NeoGiANT grape marc extracts were safe for inclusion in the diets of European seabass juveniles and provided moderate antioxidant benefits, highlighting the potential of winery by-products as functional ingredients to support more sustainable aquaculture.

Functional venom activity and antivenom neutralization in rattlesnakes across Baja California and Gulf of California islands - Samuel R. Hirst; Edgar Neri-Castro; Emiliano Vázquez-García; Vanessa Zarzosa; Felipe Olvera; Cameron M. VanHorn; Alejandro Alagón; Hector Franz-Chávez; Gamaliel Castañeda-Gaytán; Christopher L. Parkinson; Jason L. Strickland; Miguel Borja; et al. (Toxicon, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Trophic ecology of two discarded elasmobranchs (Scyliorhinus canicula and Torpedo marmorata) in a NE Atlantic trawl fishery (Gulf of Cádiz) - C. Fernández-Oliveras; C. Rodríguez-García; J. Sarmiento-Carbajal; R. Cabrera-Castro (Marine Environmental Research, 2026)

Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Effect of sodium bicarbonate on performance and markers of kidney and gastrointestinal injury during repeated sprints in the heat - Jonathan W. Specht; Marissa Ramirez; Jennifer Raef; Mackenzie Schwartz; Alyssa R. Bailly; Oscar Chavez; Ozan Kumbasar; Jade X. Dawson; Jessica Apodaca; Raul Freire; Whitley C. Atkins; Flávio de Castro Magalhães; et al. (European Journal of Applied Physiology, 2026)
Purpose We tested the hypotheses that sodium bicarbonate (SB) supplementation improves performance, reduces markers of acute kidney injury (AKI) risk, and increases markers of acute gastrointestinal injury (AGI) during repeated sprints in the heat. Methods Using a double-blind design, 10 recreationally endurance-trained participants ingested 0.2 g/kg of body weight of SB or placebo before cycling in the heat (dry-bulb: 40 °C, relative humidity: 20%). Exercise bouts included a 22-min warm-up, then 4-sets of 5 × 6-sec maximal-effort standing cycling sprints. Core temperature (Tc) was measured at baseline, end of warm-up, after set two of sprints, and post-exercise bouts. Urine and plasma collected pre-ingestion and pre-, post-, and 1-h post-exercise were analyzed for markers of AKI risk, AGI, and endotoxemia. Results SB increased peak (average difference between conditions: 21 ± 11 W, condition effect: p = 0.02) and average ( p = 0.03) power across the sprints. Tc increased from pre- to post-exercise (placebo: Δ1.3 ± 0.3 °C, SB: Δ1.4 ± 0.4 °C, time effect: p < 0.001), but there were no effects of condition or interaction. Exercise increased the primary marker of AKI (urinary IGFBP7×TIMP-2, time effect: p = 0.005) but not urinary NGAL. There were no condition or interaction effects for either AKI marker. Plasma I-FABP, a marker of AGI, increased post-exercise bouts (placebo: Δ291 ± 550 pg/mL, SB: Δ397 ± 482 pg/mL, p = 0.03), with no condition or interaction effects. There were no significant effects for markers of endotoxemia (LBP, sCD14). Conclusions SB supplementation improves repeat sprint performance in the heat without altering Tc, markers of AKI risk, or markers of AGI.

First records of spinturnicid mites (Mesostigmata: Spinturnicidae) in Tocantins State, Brazil - Luís Fernando da Cruz; Letícia de Biasi; Liege R. Siqueira; Ana Beatriz Pais Borsoi; Ingrid Benevides Machado; Ademar Ferreira da Silva; Marinete Amorim; Gilberto S. Gazêta; Fernando de Castro Jacinavicius; Darci Moraes Barros-Battesti; Ricardo Bassini-Silva (Biologia, 2026)

Long-term deformation prediction of a tropical railway sub-ballast soil in heavy-haul tracks using a high-cycle accumulation model - G. Castro; R. Motta; A. Paixão; E. Moura; E. Fortunato; L. Bernucci (Transportation Geotechnics, 2026)

In vitro digestibility and nutrient bioaccessibility of Brazilian native fish (Tambaqui and sardine), chicken, and beef under common cooking methods - Leandro Presenza; Carlos M. Donado-Pestana; Lucas de Jesus Andrade; Vinicius Bonfieti Mantovam; Priscila R. dos Santos-Donado; Maurício Luis Sforça; Luis Felipe de Freitas Fabrício; Juliana Antunes Galvão; Thais Maria Ferreira de Souza Vieira; Inar Castro Erger; Jarlei Fiamoncini (Food Research International, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Mapping and quantifying nature’s contributions to people underpinning international food trade: the case of the Brazilian coffee and soy supply-chains - Gabriela Rabeschini; Antonio J. Castro; Abhishek Chaudhary; María R. Felipe-Lucia; Thomas Koellner; Kira Lancker; Alexandra Marques; Stephan Pfister; Catharina J. E. Schulp; Louise Willemen; Thomas Kastner (Sustainability Science, 2026)

A bromoform-based Investigational Veterinary Product reduced methane emissions and increased feed conversion efficiency of yearling steers when delivered via drinking water - W.L. de Souza; S.P. Quigley; A.L. Bates; R.J. Batley; M.A.O. Castro; J.M. Gasparina; O. Gillies; P. Guerreiro; P.S. Alvarez-Hess; M.J. Auldist; S. Jacques; R. Tognelli; et al. (Animal Feed Science and Technology, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Petasma as a Reliable External Indicator of Male Sexual Maturity in Penaeus schmitti : Integrating Morphological, Biometric and Histological Analyses - H. Castro‐Neto; C. Craveiro; M. G. do Rêgo; P. G. V. Oliveira; R. Soares; S. Peixoto (Fisheries Management and Ecology, 2026)
Understanding male sexual maturity in penaeid shrimp is crucial for stock assessment and size‐based management; however, maturity criteria remain heavily biased toward females and rarely validated for males. This study evaluated whether petasma fusion is a reliable external indicator of male sexual maturity in white shrimp Penaeus schmitti from Northeast Brazil and estimated size at first maturation using an integrative morphometric, histological, and statistical approach. Forty‐five males were classified according to petasma condition, morphometrically measured, histologically examined along the reproductive tract, and analyzed using individual‐level binomial logistic regression. The estimated cephalothorax length at first maturation was CL 50 = 2.24 cm (95% CI: 2.06–2.43), with a strong model performance (Nagelkerke R 2 = 0.80). Histological analysis revealed complete categorical agreement between external morphology and internal reproductive status: all males with unfused petasma lacked mature spermatozoa and exhibited only early germ cells, whereas all males with fused petasma presented the complete spermatogenic series and fully differentiated spermatozoa in the terminal ampulla. The relationship between petasma length and body size showed negative allometry, indicating a proportionally smaller investment in petasma growth relative to somatic growth. ANCOVA detected a significant maturity effect on the intercept, but not on the slope, demonstrating a discrete proportional change in petasma dimensions at maturation, rather than a change in growth trajectory. These findings demonstrate that petasma fusion is a robust and nondestructive indicator of physiological maturity in male P. schmitti . The results of the analysis combining petasma, histology, and length at first maturity indicated that petasma is a reliable indicator for validating physiological maturity and that male reproductive indicators should be formally incorporated into penaeid fishery management structures.

Non‐Stationary Dry‐Spell Hazard Probabilities for Spain - S. M. Vicente‐Serrano; S. Beguería; A. Royo; A. El Kenawy; M. Franquesa; A. Halifa‐Marin; M. Adell‐Michavila; A. Crespillo; D. Pérez‐Pajuelo; F. Domínguez‐Castro; C. Azorin‐Molina; L. Gimeno; et al. (International Journal of Climatology, 2026)
This study provides a comprehensive assessment of long‐term changes in dry‐spell dynamics across Spain for the period 1961–2024, using both classical non‐parametric methods and a novel non‐stationary probabilistic framework applied to exceedance series of dry‐spell durations. Using daily precipitation data from a dense network of quality‐controlled stations, dry‐spells were identified based on four thresholds (0.1, 1, 5, and 10 mm) to characterize their duration statistics, and generalized Pareto distributions (GPDs) were fitted under both stationary and non‐stationary specifications. A systematic percentile‐based evaluation was performed to determine optimal exceedance thresholds, and a bootstrap‐based significance test was applied to compare stationary and non‐stationary return levels. Complementary analyses examined trends in annual frequency, mean duration, and maximum dry‐spell length. Results consistently reveal that dry‐spell behaviour across Spain is dominantly stationary. Only a very small fraction of stations show significant non‐stationary effects in the GPD location parameter, whereas non‐stationary scale, shape, or full‐parameter models provide no robust improvement and introduce substantial uncertainty. Traditional trend analyses corroborate this finding: most stations (> 70%–85%, depending on threshold) exhibit no statistically significant changes in dry‐spell frequency, mean duration, or maximum duration. Spatial patterns of change are weak, and return levels associated with long recurrence periods (e.g., 50 years) remain highly stable throughout 1961–2024. Overall, these results support long‐term stationarity in the probability of extreme dry‐spells across Spain.

Heparin-incorporated whey protein isolate-derived hydrogels with an intended dual function as snakebite wound dressings and drug delivery systems inhibit spitting cobra venom-induced cytotoxicity - Matthew J. Gray; Daniel K. Baines; Gabrielle De Castro; Thomas Cobb; Layla A. Tyrrell; Sam J. Hyam; Alan M. Smith; Nicholas R. Casewell; Sarah L. Allinson; Timothy E.L. Douglas; Steven R. Hall (Toxicon, 2026)

Emergence of Dirofilaria immitis in humid coastal zones: Epidemiological predictors and molecular characterization - Ana Clara M.P. Monteiro; Cássia M. Ribeiro; Hllytchaikra F. Fehlberg; Anaiá P. Sevá; Renata J.C. Cruz; Laura P.F. Louro; Maria Eduarda G.S. Castro; Tainara F. Barbosa; Luane E. Barreto; Fábio B. Scott; Ian K. Daniel; Guilherme G. Verocai; et al. (The Veterinary Journal, 2026)

Parametrization of scour protection deformation around mud mats and pile clusters of complex jacket offshore substations - J. Sarmiento; R. Guanche; A. Álvarez; J. Castro (Coastal Engineering, 2026)

Seasonal phytochemical variation of Peumus boldus and Cryptocarya alba and its impact on forest therapy - Nicolás R. Mac Kay; Martha Hernández de la Torre; Karina Crisóstomo-Ayala; Mauricio Aguirre-Díaz; Darío Bagüés Castro; Fernando Teillier; Claudia Pérez Manríquez (Trees, 2026)

Trees just go “nuts”: prioritizing carbon allocation to yield in almond trees - Shreya S. Veeravelli; Andrew J. McElrone; Ian R. Wright; Mina Momayyezi; Kyle R. Knipper; Nicolas E. Bambach; Sebastian Castro Bustamante; Andrew J. Gal; Sat Darshan S. Khalsa; Ranjith Karunakaran; Hung T. T. Nguyen; Morgan E. Furze (Planta, 2026)
Main conclusion Almond trees prioritize C to yield rather than stem growth, and their overall lower NSC stores compared to forest trees may have consequences for resilience under environmental variability. Abstract Perennial tree crops store nonstructural carbohydrates (NSCs) as energy reserves that can be used to persist during both predictable periods of reduced activity like dormancy and more unpredictable periods associated with stress. For deciduous tree crops, which lose their leaves at the start of dormancy, the NSC reserves accrued by that time are critically important for fueling respiration but may also influence processes in the following growing season. To quantify the seasonal NSC fluctuation surrounding dormancy and its influence on downstream processes like growth and yield, we conducted a comparative study of four almond varieties in a commercial orchard (California, USA). Sugar and starch concentrations were quantified in branch, stem, and coarse root when entering and exiting dormancy. We then assessed the correlation between these NSC data and metrics of stem growth and yield in the following growing season. We further explored long-term trade-offs between stem growth and yield using historical data from 2017 to 2022. Overall, total NSC concentrations significantly decreased during the dormant season in all organs. We observed a significant positive correlation between branch total NSC concentration when entering dormancy and yield the next year. However, we unexpectedly found that stem total NSC concentrations when entering dormancy were negatively correlated with stem growth the next year, suggesting that stem reserves were primarily used to support wintertime respiration or translocated to other organs. A long-term trade-off between stem growth and yield was evident; as yield increased, basal area increment tended to decrease. Additionally, we found whole-tree NSC storage to be lower in almond trees compared to temperate forest trees, reflecting prioritization to yield over NSC storage. Overall, these findings advance our understanding of crop tree carbon physiology and provide insight into the resilience of different almond cultivars under changing environmental conditions.

Is Genista anxantica (Fabaceae, Genisteae) worth of taxonomic recognition? An integrative approach - E. Del Guacchio; R. Vallariello; E. Di Iorio; S. Tomasello; O. De Castro (Plant Biosystems, 2026)
Genista anxantica is an extremophile taxon described by Michele Tenore and strictly endemic to the mephitic fields in Ansanto Valley (Mefite, Rocca San Felice, province of Avellino, Campania region, SW Italy). Its taxonomic distinctness from the widespread G. tinctoria subsp. tinctoria , initially undoubted, has later been long debated. Recent population genetic evidence suggests that the Mefite population represents an ecotype within G. tinctoria , shaped by extreme ecological conditions. In this contribution, we integrate morphological data and ploidy estimation by flow cytometry with ecological and genetic information to reassess its taxonomical status. Our results highlight the distinctness of G. anxantica as a local, genetically established variant adapted to a peculiar ecology. Accordingly, we propose the subspecific rank. The name G. anxantica is typified on a specimen preserved in Tenore’s herbarium (NAP, Botanical Garden of Naples).

Impacts of aqueous extracts of tree leaves on the aquatic snail Potamopyrgus antipodarum: exploring the roles of leaf habit and geographic origin - Alberto Romero-Blanco; Paula Cruces; Celeste Llandres; Beatriz R. Vázquez-de-Aldana; Virginia O. González-Blanco; Pilar Castro-Díez; Álvaro Alonso (Aquatic Ecology, 2026)
The introduction of exotic tree species with dissimilar leaf habits or distinctive chemical composition into native communities may cause impacts on aquatic organisms, yet the relative influence of leaf habit and geographic origin on those impacts remain poorly understood. In this study, we experimentally explored the ecotoxicological effects of aqueous leaf litter extracts from 15 tree species differing in leaf habit (deciduous vs evergreen) and geographic origin (exotics vs natives in Spain) on the mortality and behavior of the aquatic snail Potamopyrgus antipodarum (Gray, 1843). Snails were exposed for 7 days to three leaf extract concentrations of each tree species. No mortality effects were observed at any concentration. In contrast, the behavioral responses of snails were negatively affected at the highest concentration, showing increased reaction time and reduced speed. These responses were species-specific and associated with leaf habit and chemical composition of extracts rather than geographic origin. Leaf extracts from deciduous trees caused a greater slowing down of snails than extracts from evergreen trees. Overall, our results indicate that leaf litter impacts on Potamopyrgus antiporadrum depend more on tree species identity and leaf habit than on native or exotic status, highlighting the importance of leaf traits when assessing ecotoxicological risks in freshwater ecosystems.

Encapsulated Amazonian Microalgae Reduce Ammonia and Improve Survival of Female Poecilia reticulata During Simulated Transport - Marianela Cobos; Marcos J. Guerra; Leonardo J. Pizarro; Gladys R. Panduro; Danitza E. Ampudia; Freddy O. Espinoza-Campos; Carlos G. Castro; Juan C. Castro (Fishes, 2026)
The accumulation of un-ionized ammonia (NH3) during the transport of live ornamental fish poses a critical threat to animal welfare and post-transport survival. This study evaluated the efficacy of calcium alginate-encapsulated native Amazonian microalgae, Ankistrodesmus sp., Chlorella sp., Scenedesmus sp., and Synechococcus sp., for NH3 bioremediation during a 15-day simulated transport of female Poecilia reticulata. Biometric endpoints were selected using a four-criterion framework, identifying specific growth rate by weight (SGRW), specific growth rate by length (SGRL), and Fulton’s condition factor (K) as essential non-redundant parameters. Time-weighted average (TWA) NH3 served as the primary dose variable for four-parameter log-logistic modeling fitted to biological replicate means (n = 15). Ankistrodesmus sp. and Scenedesmus sp. maintained 97.8% survival and restricted TWA NH3 to 0.036 and 0.047 mg/L, respectively, whereas the empty capsule control reached 6.7% survival and 0.150 mg/L TWA NH3. Kruskal–Wallis tests on biological replicate means confirmed significant treatment effects on all biometric endpoints (SGRW: H(4) = 13.50, ε2 = 0.950; SGRL: H(4) = 13.50, ε2 = 0.95; p

Assessment of water quality and microbial contamination in Santa Marta’s major rivers using conventional methods and next-generation sequencing - Miguel Mateo Rodríguez; Vanessa Urrea; Nicolas Luna; Isaac Romero; Daniela Palma Polo; Luz H. Patiño; Juan David Ramírez; Marina Muñoz; Lyda R. Castro (Environmental Science and Pollution Research, 2026)
Water quality assessment is critical for determining the suitability of water resources for human consumption. In Santa Marta, northern Colombia, limited access to potable water and sewage systems, along with poor treatment infrastructure, poses a significant risk to both urban and rural communities. In some areas, untreated water is sourced directly from rivers or cisterns. Despite being a public health concern, molecular surveillance of waterborne pathogens remains limited. In this study, we integrated next-generation sequencing (NGS) with conventional physicochemical and microbiological analyses to assess water quality in the Gaira and Manzanares rivers. A total of 24 water samples were collected from eight sites along these rivers between August 2023 and February 2024. Microbial communities were characterized using Oxford Nanopore sequencing targeting the 16S-rRNA and 18S-rRNA genes. Physicochemical variables evidenced high levels of contamination, as elevated concentrations of nitrates, phosphates, ammonium, BOD, and COD were detected across the sampling sites. Other parameters, such as pH and temperature, remained stable, while conductivity and dissolved oxygen varied across sites. Microbiological analyses indicated elevated coliform levels, and Cryptosporidium spp. DNA, but not Giardia intestinalis DNA, was detected by PCR. Sequencing analysis revealed 1080 prokaryotic and 149 eukaryotic taxa, including environmental bacteria, Escherichia-Shigella group, and important taxa like Enterocytozoon . Diversity analyses showed that prokaryotic community structure was significantly influenced by basin location (upstream vs. downstream), whereas eukaryotic communities were primarily structured by river identity. Overall, integrating NGS with conventional methods provided a comprehensive characterization of microbial diversity and contamination risks in these tropical river systems, highlighting the urgent need to strengthen water management and public health strategies in Santa Marta and similar regions.

Sex‐Specific Atlantic Salmon Upstream Passage and Fallback at a Natural Cascade After Dam Removal - Kurt C. Heim; Jonah L. Withers; William R. Ardren; Laurie A. Earley; David Minkoff; Theodore Castro‐Santos (Fisheries Management and Ecology, 2026)
In the Boquet River (NY, USA) a low‐head dam set above a ~200‐m bedrock cascade was removed in 2015. We used radio‐telemetry to assess landlocked Atlantic salmon passage at the remaining cascade (2020, 2022). Across years, 52% of males (13/25) attempted cascade passage whereas females made no discernable attempts (0/11). Attempt probability increased with stream discharge and decreased with fish size, though overall passage success was low (1/36). Shallow depths—likely owing to an artificially widened channel—appear to be limiting passage. Additionally, we transported fish upstream but observed high fallback (72%) that was associated with fish size and energetic status. Following dam removal, this cascade continues to limit upstream passage resulting in increased vulnerability to angling during migratory delay. Overall, we highlight the importance of follow‐up studies after dam removal, and that further modifications at this site may be required to improve passage.

Combined Analysis of Gait Cycle and Imaging Parameters in Patients with Lumbar Disc Herniation: An Exploratory Study - Inês F. Mendes; Rita N. S. Fernandes; André P. G. Castro; Nuno A. R. Cristino (Annals of Biomedical Engineering, 2026)
This exploratory study investigates the association between imaging findings, clinical symptoms and gait parameters in patients with lumbar disc herniation (LDH). To explore this hypothesis, this study aims (1) to study how IVD height and intervertebral angle measurements obtained from MRI compare with those obtained from X-ray imaging; (2) to compare spatiotemporal gait parameters between LDH patients and healthy individuals and (3) to study if gait parameters vary in relation to clinical and imaging-derived measurements in LDH patients. Patients in this study underwent lumbar spine X-ray imaging and MRI, completed the Oswestry Disability Index (ODI) and Numerical Pain Rating Scale (NPRS) and participated in a gait analysis assessment. Measurements of IVD height and intervertebral angle revealed unexpected higher values in X-ray scans when compared to MRI, particularly in anterior IVD height and upper lumbar levels, providing important hints for the analysis of the initial imaging exam (usually X-ray scan). In addition, the analyzed gait parameters were altered in most LDH patients, with reduced walking speed, cadence, stride length and single support time and increased double support time, comparatively to healthy controls. A general tendency was found between intense radicular pain and high disability (NPRS and ODI scores, respectively) – both reflecting the impact of the clinical condition – and significant IVD pathology – evident on imaging – and altered gait parameters. However, some cases showed inconsistencies between clinical symptoms, imaging findings and gait parameters, suggesting that the relationship between the mentioned parameters is not always consistent. These findings underscore the importance of a multidimensional approach in evaluating LDH biomechanics, integrating clinical and gait parameters, while identifying potential discrepancies between imaging modalities for better initial assessment and follow-up.

Detection of Anisakis spp. (Nematoda, Anisakidae) in frozen and processed hake products marketed in Spain - R. González-Soñora; A. Ramilo; R. Ríos-Castro; E. Abollo; S. Pascual (International Journal of Food Microbiology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Partial replacement of cement with port dredging waste in the production of coating mortars - Isabela Devesa Batista; Juliana Fadini Natalli; Markssuel Teixeira Marvila; Juliane Castro Carneiro; Luiz Gustavo Cruz Henriques da Silva; Afonso R. G. de Azevedo (Environmental Science and Pollution Research, 2026)
The accelerated expansion of the cement industry, driven by the growing housing demand in urban centers, has resulted in increased consumption of raw materials and elevated carbon dioxide (CO 2 ) emissions. Simultaneously, the disposal of dredged material from ports and navigation channels presents an environmental concern, as improper management can significantly harm marine ecosystems. This study investigates the use of port dredging waste (PDW) as a supplementary cementitious material in coating mortars acting as a filler material, promoting packing and nucleation. Two types of cement were used: Ordinary Portland Cement (OPC) and Calcium Sulfoaluminate Cement (CSA), with PDW partially replacing cement at 10%, 30%, and 50% in mass, along with a control mix without replacement. The experimental program included evaluations of fresh and hardened properties, such as consistency (flow table and plunger tests), bulk density, entrained air content, water retention, flow, hydration kinetics by isothermal calorimetry, capillary water absorption, compressive and tensile strength, adhesion to substrates, and durability under wet-dry cycles. Characterization of the PDW indicated that it is appropriate for use as a filler material in coating mortars. In the fresh state, the incorporation of PDW reduced workability due to increased water demand, as observed in consistency tests. In the hardened state, replacing 10% of OPC with PDW improved compressive strength from 4.06 to 4.59 MPa and tensile strength from 0.3461 to 0.5796 MPa. In contrast, CSA-based mixtures showed reduced mechanical performance and durability as PDW content increased. These results suggest that 10% PDW replacement in OPC-based mortars is a viable and sustainable alternative, while further research is needed to address technical challenges in CSA-based systems. Practically, the use of PDW in OPC mortars offers an environmentally friendly strategy to reduce cement consumption, valorize dredged materials, and enhance the sustainability of construction coatings.

Dendropsophin 1, an antimicrobial peptide from skin secretion of the tree frog Dendropsophus columbianus, exhibits tissue repair potential - Isabella S. Cassimiro; Bruno A. Ferreira; Simone R. Deconte; Taís C. Lima; Francyelle B.R. Moura; Mariana S. Castro; Fernanda A. Araújo (Toxicon, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

The isotopic niche breadth of aquatic insects increases with elevation in neotropical mountain streams - Diego M.P. Castro; Robert M. Hughes; Diego R. Macedo; Marcos Callisto (Food Webs, 2026)

Reply to Schien et al. (2025) “Global datacentre electricity consumption is not correlated with data demand: Responding to implausible Assumptions and flawed modelling in castro et al.” comment on Castro et al. (2024) paper in energy policy “Digital data demand and renewable energy limits: Forecasting the impacts on global electricity supply and sustainability” - Vitor Castro; Marios Georgiou; Thomas Jackson; Ian R. Hodgkinson; Lisa Jackson; Steve Lockwood (Energy Policy, 2026)

Influence of almond’s canopy-induced shadows on actual evapotranspiration estimation by the TSEB model using sUAS multispectral and thermal imagery - M. R. Duran-Gomez; A. Torres-Rua; L. Hipps; W. Kustas; N. E. Bambach; K. Knipper; I. Wright; A. J. McElrone; J. H. Prueger; J. G. Alfieri; C. Coopmans; K. Meza; et al. (Irrigation Science, 2026)
Over the past decade, the estimation of water requirements in almond orchards has improved through the application of remote sensing models like the Two-Source Energy Balance (TSEB) model using various remote sensing platforms. However, there is limited understanding of how canopy-induced shadows influence surface reflectance and thermal infrared (TIR) signals particularly from small Unmanned Aircraft System (sUAS) imagery in energy balance models, and the effect on Latent Heat Flux (LE) estimations. This study evaluates LE estimates from the Priestley-Taylor TSEB model (TSEB-PT) with and without shadow filtering using sUAS-based multispectral and TIR imagery. It establishes a baseline for the impact of shadow filtering on model inputs and performance. Datasets were collected in 2021 and 2022, as part of the USDA led Tree-crop Remote sensing of Evapotranspiration eXperiment (T-REX) in almonds orchards across California. LAI-2200 C Plant Canopy Analyzer measurements facilitated the calibration of an empirical Leaf Area Index (LAI) model based on canopy fractional cover (FC) and NDVI (R 2 = 0.68). Shadow filtering caused land surface temperature (LST) differences up to 5 °C in young to semi-mature orchards (FC 0.40–0.80). In contrast, mature orchards (FC > 0.80) showed minimal influence due to the limited shadow occurrence on the imagery. Shadows appeared to reduce surface albedo (α alb ), mainly in interrow areas, thereby affecting the absorption of radiation and the partitioning of energy balance components. Their presence in sUAS imagery also hindered canopy delineation, impacting the accuracy of key TSEB inputs derived from canopy physical characteristics. Thus, the influence of shadow on TSEB estimated LE was more significant in lower fractional tree covers. While LE estimated by TSEB-PT without shadow filtering showed better agreement with observations, combining instantaneous TIR imagery with solar-noon shortwave data is recommended for accurate ETa assessment using sUAS datasets. These baseline results can be improved with more advanced formulations, supporting continued research on E/T partitioning and water stress in almond orchards under varying environmental conditions, particularly when there is advection of hot dry air.

Integrated policy and AI-assisted technologies to address extreme heat and enhance urban resilience - Johanne Rei R. Castro; Laurence L. Delina (Journal of Environmental Studies and Sciences, 2026)
Cities are increasingly facing extreme heat due to rising temperatures from accelerating climate change and the heat island effect caused by rapid urban expansions. In response to this emerging hazard, cities are developing and implementing policies aimed at mitigating the impacts of extreme heat, including initiatives to increase public awareness and enhance adaptive capacities. Additionally, many cities are leveraging artificial intelligence (AI)-assisted technologies to forecast heatwaves, develop evidence-based mitigation strategies, and optimize infrastructure development in anticipation of these challenges. Previous studies have identified the vulnerabilities and risks associated with extreme heat in cities, quantified its impacts, and evaluated the probable outcomes of adaptation and mitigation measures utilizing AI-assisted technologies. However, most of this research has concentrated on cities in developed regions such as the USA, Europe, and Australia. There has been limited exploration of the synergistic effects of policy and AI-assisted technology responses to extreme heat. To address these gaps, we employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol to scope studies exploring the integration of heat-related policies and AI-assisted technologies. This approach revealed strategic methods, underlying motivations, and key stakeholders involved. Our review offers insights into future research needs, particularly in bridging the geographical gaps in urban overheating studies and enhancing the integration of policy and AI-assisted technologies in cities.

Spatial evaluation of groundwater pollution by pesticides in the agroindustrial hub “La Comarca Lagunera” in México: the anthropogenic activity and local factors’ impact - Virgilio R. Góngora-Echeverría; Javier Castro-Larragoitia; Germán Giácoman-Vallejos; Antonio Cardona-Benavides; Avel González-Sánchez; Dario Cauich-Kau; Gonzalo G. García-Vargas (Environmental Monitoring and Assessment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Understanding and predicting CO2 capacity loss in activated carbons under humid conditions - R. Morales-Ospino; M. Aoun; J. Castro-Gutiérrez; M.T. Izquierdo; A. Celzard; V. Fierro (Chemical Engineering Journal, 2026)

Spatiotemporal variation of black carbon in snow surface and atmosphere in an upper basin of central Chilean Andes: A retrospective analysis and future projections - Felipe Aranda; Lina Castro; Tomás R. Bolaño-Ortiz; Felipe McCracken (Atmospheric Environment, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Thermoregulation strategies and microhabitat structure as determinants of susceptibility to heat waves in two sympatric Mediterranean lizards - S. Blázquez-Castro; R. Barrientos; S. Reguera; I. Barja; R. Megía-Palma (Climatic Change, 2026)

Replacing natural savannas with eucalyptus and soybeans changes the matrix use and reduces bat taxonomic and functional diversity in the Amazonian savannas - Bruna S. Xavier; Karen Mustin; Tiago M. Marques; Marcelo M. Ferreira; Renato R. Hilário; José J. Toledo; Isaí J. Castro; Jorge M. Palmeirim; Ana M.C. Santos; Marcus V. Vieira; William D. Carvalho (Agriculture, Ecosystems & Environment, 2026)

Characterization of metal contaminants in the Critically Endangered angelshark (Squatina squatina): A first ecotoxicological insight - Tomas Bañeras; David Jiménez-Alvarado; Eva K.M. Meyers; Hector Toledo-Padilla; Arturo Hardisson; Dailos Gonzalez-Weller; Joanna Barker; Lucy R. Mead; Ana Espino-Ruano; Ayoze Castro-Alonso; María José-Caballero; Ángel Gutiérrez (Marine Pollution Bulletin, 2026)

Laboratory investigation and modelling of alternative materials for sub-ballast and formation rehabilitation in a heavy haul railway line - G. Castro; J. Saico; R. Motta; E. Moura; R. Costa; L. Bernucci; A. Paixão; E. Fortunato (Transportation Geotechnics, 2026)

The ornithine-arginine cycle supported a toxic, metalimnic Planktothrix rubescens bloom - Brittany N. Zepernick; David J. Niknejad; Emily E. Chase; Blessing A. Abiodun; Meaghan J. Adler; Katelyn A. Houghton; Jason L. Olavesen; Qudus Sarumi; Alexander R. Truchon; Jillian L. Walton; Jack H. Cheshire; Keara Stanislawczyk; et al. (Harmful Algae, 2026)

Enantioselective toxicity of 3,4-methylenedioxypyrovalerone in Daphnia magna: Assessment of morphophysiological, behavioural, biochemical and reproductive responses - Ariana Pérez-Pereira; Ana R. Carvalho; Pedro A. Costa; Bruno B. Castro; João S. Carrola; Virgínia M.F. Gonçalves; Ana R.L. Ribeiro; Ana Sofia Almeida; Carla Fernandes; Maria E. Tiritan; Cláudia Ribeiro (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Replacing the natural savanna matrix with eucalyptus plantations and soybean fields changes the seed rain promoted by bats in Amazonian savannas - Bruna S. Xavier; Jeferson Vizentin-Bugoni; Marcelo M. Ferreira; Tiago M. Marques; Renato R. Hilário; José J. Toledo; Isaí J. Castro; Karen Mustin; Jorge M. Palmeirim; Marcus V. Vieira; William D. Carvalho (Biological Conservation, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

3D printing of ascorbic acid-rich protein-starch gels for dysphagia diets: texture, nutritional and bioactive properties - Jaqueline Souza Guedes; Bruna Sousa Bitencourt; Isabela Soares Magalhães; Bruna de Oliveira Gomes; Bruno Ricardo de Castro Leite Junior; Wanessa R. Melchert; Pedro Esteves Duarte Augusto (Innovative Food Science & Emerging Technologies, 2025)

Reproductive success over Calliandra fasciculata Benth. floral anthesis: evidence of adaptive generalization - Rodrigo Santiago; Pedro J. Bergamo; Vinícius L.G. Brito; Marsal D. Amorim; Lucas B. Castro; Sabrina A. Lopes; Cinthia S. Novaes; Larissa C. Mendes; Gizele C.A. Silva; Danila M. Silva; Ilmara A.O. Ferreira; Bernardo O. Dias; et al. (Flora, 2025)

Multi-objective optimization of glutathione production by Saccharomyces cerevisiae in a mini-bubble column reactor via a multifactorial batch-design approach - Isabella Giraldo-Rodriguez; Ángela M. Ossorio-Tróchez; Isabella M. Giraldo-Castro; Carlos A. Diaz; Andres Ceballos-Bermudez; Carlos A. Alvarez-Vasco; Colomba M. Dazzarola; José R. Perez-Correa; Nelson H. Caicedo-Ortega (Bioresource Technology Reports, 2025)

Unveiling enantioselective mechanisms of toxicity of butylone in Daphnia magna - Renata Vidal; Ana R. Carvalho; Juliana Faria; Joana Barbosa; Virgínia M.F. Gonçalves; Maria E. Tiritan; Cristina Couto; João S. Carrola; Bruno B. Castro; Adrián M.T. Silva; Ana R.L. Ribeiro; Cláudia Ribeiro (Aquatic Toxicology, 2025)

Andrographolide increases adult hippocampal neurogenesis and prolongs contextual fear memory - Laura F. Jaimes; Matheus C. Passos; Lara M. Z. Mansk; Caio M. de Castro; Julián T. F. Vega; Leonardo de O. Guarnieri; Flávio A. G. Mourão; Alexander Birbrair; Victor R. Santos; Márcio F. D. Moraes; Grace S. Pereira (Psychopharmacology, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Developing science-informed maps and climate service for extreme rainfall in Spain - S. M. Vicente-Serrano; S. Beguería; F. Reig; A. Royo; M. Arretxea; M. Gil; B. Latorre; A. El Kenawy; M. Franquesa; A. Halifa-Marin; M. Adell-Michavila; A. Crespillo; et al. (Natural Hazards, 2025)
This study introduces the first high-resolution hazard probability maps of extreme precipitation for Spain, marking a significant step toward a national climate service for hydrometeorological extremes. Using long-term daily precipitation records from a dense network of stations and incorporating topographic data, the methodology combines the Generalized Pareto distribution with universal kriging to spatially interpolate distribution parameters. These maps offer reliable estimates of extreme precipitation quantiles, validated against station-level observations, and are based on a stationary modelling framework—an approach supported by recent findings showing the temporal stability of such extremes in Spain and considered more robust than non-stationary alternatives. Distinct spatial patterns emerge, with intense daily precipitation distributed mainly along the Mediterranean coast and high total event precipitation in the northwest and southwest, reflecting the influence of varied weather systems. To support decision-making, the study aggregates these high-resolution data at the provincial level, aligning risk information with administrative boundaries, and enhancing its relevance for policy and planning. Furthermore, the maps are made accessible via an interactive online platform ( https://retornolluvias.csic.es ), enabling users to explore localized hazard probabilities, thereby supporting adaptation in water management and civil protection, among others.

Near-source attenuation of foreshocks preceding the 2010 El Mayor-Cucapah, Baja California, Mexico earthquake (Mw7.2) - Raúl R. Castro; Carlos E. Reinoza; Favio Cruz-Hernández (Journal of Seismology, 2025)

Characterization of anti-neutrophil extracellular traps (NET) antibodies according to systemic lupus erythematosus clinical phenotypes - Daniel Alberto Carrillo-Vázquez; Jennifer Tiaré Balderas-Miranda; Rosa Icela Arvizu Rivera; Alfredo Pérez-Fragoso; Beatriz Alcalá-Carmona; Miroslava Nuñez-Aguirre; Ana Sofía Vargas-Castro; Abdiel Absalón-Aguilar; Jaquelin Lira-Luna; Nancy R. Mejía-Domínguez; Guillermo Juárez-Vega; Karina Santana-de Anda; et al. (Immunologic Research, 2025)

High levels of recruitment underline the sustainability of octocoral populations to harvest - Carolina Castro-Sanguino; Howard R. Lasker (Coral Reefs, 2025)

Thrips (Insecta: Thysanoptera) species associated with avocado orchards in central Veracruz, Mexico - David Alarcón-Utrera; Daniel López-Lima; Carlos R. Cerdán-Cabrera; Gerardo Alvarado-Castillo; Alejandro Salinas-Castro; Gloria Carrión (International Journal of Tropical Insect Science, 2025)

Estimates of S-wave Q(f) in the rupture area of the mainshock and in the last-week foreshocks area preceding the L'Aquila 2009 (Mw6.1) earthquake sequence, Central Italy - Raúl R. Castro; Leonardo Colavitti; Daniele Spallarossa; Giovanna Calderoni; Simona Gabrielli; Francesca Pacor (Tectonophysics, 2025)

Antioxidant, UV-blocking, and biodegradable pectin films containing selenium nanoparticles for sustainable food packaging - Guilherme A.M. Jesus; Michael C. Castro; Paulo R. Souza; Johny P. Monteiro; Roberta M. Sabino; Shyam S. Sablani; Alessandro F. Martins; Elton G. Bonafé (Food Hydrocolloids, 2025)

Hydro‐Functional Traits and Their Dissimilarity to the Neighbourhood Buffer Tree Growth Against the 2018–2020 Central European Drought - Lena Sachsenmaier; Florian Schnabel; Fon R. Tezeh; Pablo Castro Sánchez‐Bermejo; Nico Eisenhauer; Olga Ferlian; Sylvia Haider; Ronny Richter; Sharath S. Paligi; Bernhard Schuldt; Christian Wirth (Global Change Biology, 2025)
Climate change is predicted to increase the frequency and duration of drought events, threatening the functioning of Central European forests. While diverse forests often promote long‐term growth stability, their performance during extreme drought events remains debated. Understanding the effects of forest diversity on tree growth during drought requires not only a consideration of tree interactions with direct neighbouring trees but also of the species' morphological and physiological characteristics, i.e., a trait‐based approach. Contrasting species‐specific drought responses might be driven by hydro‐functional traits, which shape a tree's hydraulic safety and stomatal control strategy. We investigated individual tree growth before, during, and after the unprecedented 2018–2020 Central European drought, from a hydro‐functional perspective. We analysed annual growth data from 2611 trees in a temperate tree diversity experiment (MyDiv experiment, Germany), measured 14 hydro‐functional traits, and modelled individual tree growth across the years 2016–2021, considering the interaction of climatic conditions with hydro‐functional trait syndromes. Our results reveal that traits related to hydraulic safety and stomatal control potential were key drivers of tree growth across drought and non‐drought years. During the severe multi‐year drought, the growth of focal trees increased with either higher hydraulic safety or tighter stomatal control potential. Trait syndromes that were less advantageous under normal conditions provided beneficial effects under drought stress, reflecting a trade‐off in performance across conditions. Additionally, we found that hydro‐functional dissimilarity between a tree and its surrounding neighbors provided benefits for tree growth during drought. Therefore, our study suggests that planting tree mixtures with distinct hydro‐functional strategies can enhance resistance to future droughts.

Wildlife of tidal forested wetlands in the southeastern Atlantic United States - James T. Anderson; Andrew P. Hopkins; Crystal Anderson; Miriam Boucher; Rene Brown; Aruã de Castro; Sindupa De Silva; Robert M. Greco; Jordan E. McCall; Oluwatobi Emmanuel Olaniyi; Christopher Pettengill; Akshit R. Suthar; et al. (Estuarine, Coastal and Shelf Science, 2025)

Design, manufacturing, and performance of innovative aluminium-backed BIPV facade modules: a case-study in Germany - S. Jahreis; B. Jaeckel; R. Koepge; J. Fröbel; P. Schenk; M. Pander; R. Castro (Energy and Buildings, 2025)

AT1 receptors play a role in sepsis-induced vasoplegia by increasing iNOS expression in the perivascular adipose tissue - Wanessa M. C. Awata; Gustavo F. Pimenta; Thales M. H. Dourado; Kathleen A. Paulino; Marcela M. Blascke de Mello; Lucas C. Pinheiro; Michele M. Castro; Carlos R. Tirapelli (Pflügers Archiv - European Journal of Physiology, 2025)

Conservation for production? The benefits of mangroves for sustainable shrimp aquaculture - Aji W. Anggoro; Miguel Castro; Muhammad Ilman; Sara Leavitt; Basir; Mariski Nirwan; Vabian Adriano; Andi Trisnawati; Topik Hidayat; Rahmadi Muis; Dzimar A. R. Prakoso; Yusuf Fajariyanto; et al. (Aquaculture International, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Essential oil-embedded starch based films for active packaging: Insights into migration, stability, and preservation efficiency - Rakesh Kumar Gupta; Sunil Pipliya; Jyotsana Patel; Prem Prakash Srivastav; Roberto Castro-Muñoz; Chin-Kun Wang; Monica R. Nemţanu (Trends in Food Science & Technology, 2025)

Oxidative foliar photo-necrosis, a mechanism of damage by phyto-pathogenic fungi - Roberto Hernández-Chacón; Lervin Hernández-Ramos; Laura Navarro de la Fuente; Manuel E. Medina; José J. Fernández; Ana R. Díaz-Marrero; Alejandro Salinas-Castro; Irene Lagunes; Ángel Trigos (Physiological and Molecular Plant Pathology, 2025)

Functional recovery of tropical forests: The role of restoration methods and environmental conditions - Rens Brouwer; Marielos Peña-Claros; Frans Bongers; Lourens Poorter; Joannès Guillemot; Danilo R.A. Almeida; Catherine Torres de Almeida; Angélica F. Resende; Laura H.P. Simões; Natália M. Ivanauskas; Renato A. Ferreira de Lima; Vinicius Castro Souza; et al. (Biological Conservation, 2025)

Productive Potential and Contribution of Biological Nitrogen Fixation To Sugarcane Cultivation for Energy Purposes - Carolina Almada Gomes de Oliveira; Edevaldo de Castro Monteiro; Wesley dos Santos Souza; Paulo Vitor Alves Pio; Bruno J. R. Alves; Robert Michael Boddey; Segundo Urquiaga (Journal of Soil Science and Plant Nutrition, 2025)

Cross-canyon variability in zooplankton backscattering strength in a river-influenced upwelling area - Macarena Díaz-Astudillo; Manuel I. Castillo; Pedro A. Figueroa; Leonardo R. Castro; Ramiro Riquelme-Bugueño; Iván Pérez-Santos; Oscar Pizarro; Gonzalo S. Saldías (Ocean Science, 2025)
Zooplankton are a key component of food webs in upwelling systems. Their distribution is influenced not only by mesoscale and climate dynamics but also by topography and local currents. Submarine canyons that incise the continental shelf can act as conduits, transporting deep, nutrient-rich waters to shallower regions and promoting coastal biological productivity. Consequently, these canyons facilitate the advection and accumulation of zooplankton. We aimed to describe the spatio-temporal variability in zooplankton distribution (using net samples and acoustic data) and their association with local currents in a long, narrow submarine canyon located in the highly productive continental shelf off central Chile. The backscattering strength (Sv), a proxy for zooplankton biomass, was highly variable on both diurnal and spatial scales. Higher Sv and abundances were found at night, following the classic diel vertical migration pattern. Zooplankton were not uniformly distributed within the canyon. In the surface and mid-depth layers, the canyon walls accumulated more zooplankton than the center, particularly during the nighttime. Within the canyon, the currents were asymmetrical and frequently reversed direction. When the positive along-canyon current was stronger on the northern slope, Sv was also higher on that wall. This pattern was especially evident in the section closer to the canyon head. We show that the Biobio Canyon is a highly dynamic environment where oceanographic conditions can rapidly shift. Our findings suggest a feasible mechanism for zooplankton retention driven mainly by along-canyon flow asymmetry and vertical migrations.

Multiple anthelmintic drug resistance in the canine hookworm Ancylostoma caninum: AAVP position paper and research needs - Timothy G. Geary; Jason Drake; John S. Gilleard; Jeba R.J.Jesudoss Chelladurai; Pablo D. Jimenez Castro; Ray M. Kaplan; Antoinette E. Marsh; Craig R. Reinemeyer; Guilherme G. Verocai (Veterinary Parasitology, 2025)

The social, technological, economic, and political roles of information and communication technologies in extreme heat adaptation in urban Southeast Asia - Johanne Rei R. Castro; Laurence L. Delina (Urban Climate, 2025)

First report of biological contaminants in household water in the Philippines and long-term viability of Acanthamoeba species in one-year-old household water sediment - Frederick R. Masangkay; Rafaella Maxine N. Almeda; Alianna Louise M. Abustan; Sarah Veronica F. Almendrala; Jan Camille B. Bathan; Jowey Shekainah C. Belandres; Maria Allana Angela M. Buenaventura; Lea May F. Cabansag; Gemina Bienne V. Caralian; Mikhaella Denise V. Cueva; Leizette P. Cata-Al; Rance Leander H. Clemente; et al. (Science of The Total Environment, 2025)

Highly open 3D carbon structures enhance solar steam generation - R. Fillet; V. Nicolas; P. Blyweert; J. Castro-Gutiérrez; B. Rousseau; A. Celzard; V. Fierro (Chemical Engineering Journal, 2025)

HIstopathological study of diseased sea urchins found dead in a rocky beach of Gran Canaria (Canary Islands) - M.J. Caballero; R. Nuñez-González; E. Montesdeoca-Morales; D. Padilla; J. Luis Martín Barrasa; G. Montero-Hernández; J. Juan Castro; A. Castro-Alonso (Journal of Comparative Pathology, 2025)

Ecological impacts of agrochemical and pharmaceutical antifungals on a non-target aquatic host-parasite model - AR Pimentão; R. Ribeiro; BA Silva; AP Cuco; BB Castro (Aquatic Toxicology, 2025)

Ethanol-induced dysfunction of the mesenteric perivascular adipose tissue is driven by mineralocorticoid receptors - Ivis V. O. Martins; Thales M. H. Dourado; Gustavo F. Pimenta; Marcela M. Blascke de Mello; Aline G. Fedoce; Wanessa M. C. Awata; Michele M. Castro; Rita C. Tostes; Carlos R. Tirapelli (Pflügers Archiv - European Journal of Physiology, 2025)

Ecological legacies in a tropical savanna: woody layer responses to long-term changes in soil chemistry - Isabela B. Castro; Leonardo Ferreira-Sousa; Thiago R. B. Mello; Alexandra Martins; Mercedes M. C. Bustamante (Oecologia, 2025)

Potential contribution of foreign-flagged recreational and craft vessels to the introduction and spread of non-indigenous species: A preliminary assessment for Brazil - F.S. Rangel-Pereira; M.C.T. Castro; M.P. Scapolatempore; L.D.A. Fernandes; R. Coutinho; G.M. Ruiz (Marine Pollution Bulletin, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Body development, ingestive behaviour, and physiological responses of Nelore and Crossbred heifers - C. S. Santos; A. R. D. L. Souza; A. L. J. Ferraz; F. A. M. Sterza; R. V. Rohod; M. F. Castro; L. S. Amorim; M. C. E. Queiroz; G. B. Almeida; M. V. M. Oliveira; A. R. D. Santos; D. M. Oliveira (Tropical Animal Health and Production, 2025)

How septoria leaf blotch affects nitrogen dynamics, grain yield and protein concentration in wheat - S. I. Golik; A. C. Castro; H. M. Pardi; M. R. Simón (Cereal Research Communications, 2025)

Wastewater-Based Epidemiology for Analysis of Human Papillomavirus Infections in a Uruguayan Urban Area - C. Fernandez-Sabatella; G. Corrales; L. Monzon; E. Andrade; N. Sica; E. Cardozo; N. Baccardatz; J. Jacques; S. Castro; M. Castells; M. Victoria; R. Colina (Food and Environmental Virology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Effects of dietary supplementation with slow-release urea coated with carnauba wax on intake, ingestive behavior, selectivity, ruminal parameters, performance and carcass traits of lambs - Tainan da Silva Batista; Leilson R. Bezerra; Pedro H.S. Mazza; Analivia M. Barbosa; Beatriz S.C. de Castro; Melissa D. Ferrer; Ana Carolina Ferreira; Jasiel S. de Morais; Edson C. da Silva Filho; Ronaldo L. Oliveira (Small Ruminant Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Effective novel and conventional technologies for decontamination of aflatoxin B1 in foods: a review - Diego Fernando García-Ramón; Heber P. Cornelio-Santiago; Edgar Norabuena; Liliana Sumarriva; Hermelinda Alvarez-Chancasanampa; Marlitt Naupay Vega; Alejandrina Sotelo-Méndez; Luis Alfredo Espinoza-Espinoza; Lucia R. Pantoja-Tirado; Sara H. Gonzales-Agama; Esmila Y. Chavarría-Marquez; Cesar Raul Castro-Galarza (Mycotoxin Research, 2025)

Porcine circovirus type 2 (PCV2) in Brazil in the past 55 years (1967-2022): evolutionary rates and patterns - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; B. V. Lago; R. L. Silveira; T. X. Castro (Archives of Virology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

Bio-desulfurization of different vulcanized rubber blends: An ecofriendly approach for end-of-life tires waste pollution - R. Andler; C. Cancino; F. González-Arancibia; J. Rojas; R. Castro; D. Kasai; V. Sanhueza (Journal of Environmental Chemical Engineering, 2025)

Effects of digestate soil amendment on the fate of trace metals and on the soil microbial community - Veronica Baldasso; Maria Paola Tomasino; Stéphanie Sayen; Emmanuel Guillon; Luigi Frunzo; Carlos A.R. Gomes; Maria João Alves; Ricardo Castro; Ana Paula Mucha; C. Marisa R. Almeida (Environmental Pollution, 2025)

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Can macro- or meso-scale coping capacity variables improve the classification of building flood losses? - D. Rodríguez Castro; M. Cools; S. Roucour; P. Archambeau; D. Molinari; A. R. Scorzini; C. Dessers; S. Erpicum; M. Pirotton; J. Teller; B. Dewals (Natural Hazards, 2025)

Valorization of residual ashes from boiler combustion process into activated carbon for adsorption of food industry wastewater - L. E. N. Castro; L. R. Matheus; W. G. Sganzerla; L. M. S. Colpini (International Journal of Environmental Science and Technology, 2025)

Unveiling the diversity of macrobenthic crustaceans on sandy beaches of the eastern Mexican coast: new records and an updated checklist - María R. Muciño-Reyes; Edlin Guerra-Castro; Raúl E. Castillo-Cupul; Carlos E. Paz-Ríos; Nuno Simões (Frontiers in Marine Science, 2025)
Despite the ecological importance of sandy beaches, the diversity and distribution of macrocrustacean communities in the eastern Mexican coast (Mexican coast of the Gulf of Mexico and Caribbean Sea) remain understudied. As the first large-scale sampling effort along the eastern Mexican coast, this study aimed to estimate macrocrustacean diversity and evaluate sampling methodologies, while providing historical context for macrocrustacean research in the region. Two sampling designs using sediment cores (4 versus 6 cores per transect) were implemented across 15 sandy beaches. A total of 3,352 organisms were collected, representing 22 species from 17 genera, spanning 14 families, 7 suborders, 5 orders, and 2 superorders. Amphipoda and Isopoda exhibited the highest species richness and abundance. The study yielded seven new geographical records ( Haustorius jayneae , Rhepoxynius epistomus , Americorchestia salomani , Heterodina mosaica , Cassidinidea ovalis , Exosphaeroma diminutum , and Sphaeroma walkeri ). Results demonstrated that the 6-core sampling design provided better diversity representation. An updated checklist comprising 77 species/taxa for the eastern Mexican coast was compiled, integrating historical and new data. This comprehensive assessment enhances our understanding of these vulnerable ecosystems and emphasizes the need for broader temporal and spatial scale studies to inform effective conservation strategies.

Monte Carlo simulation of community microgrid operation: Business prospects in the Brazilian regulatory framework - Francisco C.R. Coelho; Fernando A. Assis; José Filho C. Castro; Antonio R. Donadon; Ronaldo A. Roncolatto; Vittoria E.M.S. Andrade; Pedro A.C. Rosas; Silvangela L.S.L. Barcelos; Osvaldo R. Saavedra; Rafael G. Bento; Rafael K. Carneiro; Pablo F. Hernandez; et al. (Utilities Policy, 2025)

Validation of the spray drift modeling software AGDISPpro applied to remotely piloted aerial application systems - Sebastian Castro-Tanzi; Michael Winchell; Zhenxu Tang; Milton E. Teske; Glen R. Whitehouse; Brad Fritz; Dan Martin (Science of The Total Environment, 2025)

Cost-effective alternatives to facilitate biomonitoring and bioassessment of neotropical streams - Francisco Valente-Neto; Renato B. Dala-Corte; Almir M. Cunico; André L.B. Magalhães; Bruno S. Godoy; Cecília G. Leal; Diego M.P. Castro; Diego R. Macedo; Dilermando P. Lima-Junior; Éder A. Gubiani; Fabio de O. Roque; Fabrício B. Teresa; et al. (Science of The Total Environment, 2025)

Distribution and bioconcentration of semivolatile organic compounds (SVOCs) in soils and vascular plant Colobanthus quitensis from Sub-Antarctic and Antarctic regions - C. Egas; T. Luarte; R. Vargas; E. Castro-Nallar; K. Pozo; P. Přibylová; J. Martiník; M. Molina-Montenegro; C. Galbán-Malagón (Science of The Total Environment, 2025)

Effect of penicillamine, hypotaurine and epinephrine (PHE) and pH on stallion sperm during in vitro capacitation - R. Gonzalez-Castro; C. Porflidt; E. Carnevale (Journal of Equine Veterinary Science, 2025)

Escherichia coli-associated granulomatous diseases in three cats - Milena C. Paz; Igor R. Santos; Lucas T. de Castro; Gabriela Hartmann; Luan C. Henker; Jacqueline Raiter; Regina T. Kemper; Júlia G. Wronski; Eryca C. Lamego; Luiza da Rosa Robusto; Luciana Sonne; David Driemeier; et al. (Journal of Comparative Pathology, 2025)

One Health tropical wetlands: a transdisciplinary framework for assessing the risks of emerging zoonotic diseases in the Brazilian Pantanal - Fabio de Oliveira Roque; Heitor Miraglia Herrera; Gisele Braziliano de Andrade; Matthew Johnson; André Valle Nunes; Alessandra Gutierrez de Oliveira; Eduardo de Castro Ferreira; Geraldo Wilson Fernandes; Giulia Armani Araujo; Luiz Gustavo R. O. Santos; Rafael Morais Chiaravalloti; Reinaldo Farias Paiva de Lucena; et al. (Wetlands Ecology and Management, 2025)

Distinct management units for the Critically Endangered angelshark (Squatina squatina) revealed in the Canary Islands - Eva K.M. Meyers; Nadia Faure; David Jiménez-Alvarado; Joanna Barker; Hector Toledo-Padilla; Fernando Tuya; Charlotte Pike; Lucy R. Mead; Michael J. Sealey; Maria Belén Caro; David M.P. Jacoby; Felipe Ravina Olivares; et al. (Conservation Genetics, 2025)
The angelshark, Squatina squatina , is listed as Critically Endangered on the IUCN Red List of Threatened Species, and remaining populations are highly fragmented throughout its historical distribution. The Canary Islands archipelago in the North East Atlantic has been identified as a uniquely large stronghold for the species. In the present study, we compared the population genetic structure of S. squatina across different islands of the Canary Island archipelago using both microsatellite and single nucleotide polymorphism (SNP) markers. Both markers revealed significant differentiation of angelsharks between islands in the archipelago, with three main genetic units at: (1) Tenerife, (2) Gran Canaria and (3) the island group consisting of La Graciosa, Lanzarote and Fuerteventura. Our results imply a connectivity barrier between some adjacent islands, most likely driven by abyssal depths, and varying geological history and formation of each island and oceanographic patterns (i.e. seasonal coastal upwellings off the African coast). Therefore, we suggest that in the Canary Islands, S. squatina populations should be managed locally, with conservation and research priorities designed and implemented specifically for each of the three genetic units.

Effect of dietary citrus pulp on performance and dry matter digestibility in dairy cows: A meta-analysis and meta-regression - E.E. Corea-Guillen; M. Benaouda; A.H. Ramirez-Perez; A.C. Lizarazo; J.M. Castro-Montoya; R. Vieyra-Alberto; J.C. Angeles-Hernandez (Animal Feed Science and Technology, 2025)

Annular solar eclipse effects observed over Mexico on October 14, 2023: A multi-instrument study - M.A. Sergeeva; J.A. Gonzalez-Esparza; O.A. Maltseva; J.H. Castro-Chacon; V.J. Gatica-Acevedo; A. Melgarejo-Morales; I.D. Orrala Legorreta; X. Chiappa; R. Bonifaz; M.E. González-Álvarez; A. Vesnin; P. Corona-Romero; et al. (Advances in Space Research, 2025)

Evaluation of impacts of biosolids application and drainage water management on soil N2O and CH4 emissions using the flux gradient method - Qiurui Zhu; Eric A. Davidson; Jacob G. Hagedorn; Mark S. Castro; Thomas R. Fisher; Rebecca J. Fox; Shannon E. Brown; James W. Lewis (Agriculture, Ecosystems & Environment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Monitoring macroplastics in aquatic and terrestrial ecosystems: Expert survey reveals visual and drone-based census as most effective techniques - L. Gallitelli; P. Girard; U. Andriolo; M. Liro; G. Suaria; C. Martin; A.L. Lusher; K. Hancke; MCM Blettler; O. Garcia-Garin; I.E. Napper; L. Corbari; et al. (Science of The Total Environment, 2024)

Living between sand and waves: Age and feeding habits of sand sole (Pegusa lascaris, Risso 1810) and brill (Scophthalmus rhombus, Linnaeus, 1758) on the beaches of the Gulf of Cádiz (Southwest Iberian Peninsula) - C. Rodríguez-García; M. Jiménez-Cobo; R. Cabrera-Castro (Regional Studies in Marine Science, 2024)

Associations of exposure to outdoor PM2.5 and NO2 during pregnancy with childhood asthma, rhinitis, and eczema in a predominantly rural French mother-child cohort - Alan R. Patlán-Hernández; Marine Savouré; Etienne Audureau; Christine Monfort; Montserrat de Castro; Ralph Epaud; Kees de Hoogh; Ian Hough; Itai Kloog; Sophie Lanone; Johanna Lepeule; Mark Nieuwenhuijsen; et al. (Environmental Pollution, 2024)

Digital data demand and renewable energy limits: Forecasting the impacts on global electricity supply and sustainability - Vitor Castro; Marios Georgiou; Thomas Jackson; Ian R. Hodgkinson; Lisa Jackson; Steve Lockwood (Energy Policy, 2024)

Green coffee extracts microencapsulated by spray freezing into the liquid cryogenic - Jaime López-Domínguez; Maria Teresa González-Arnao; Cesar A. Ortíz-Sánchez; Marisol Castillo-Morales; Martha P. Rascón-Díaz; Ubaldo R. Marin-Castro (Cryobiology, 2024)

Retraction notice to “An organic-solvent-tolerant esterase from thermophilic Bacillus licheniformis S-86” [Bioresour. Technol. 100(2) (2009) 896–902] - Sebastián Torres; M. Alejandra Martínez; Ashok Pandey; Guillermo R. Castro (Bioresource Technology, 2024)

Strong climate mitigation potential of rewetting oil palm plantations on tropical peatlands - Nisa Novita; Adibtya Asyhari; Rasis P. Ritonga; Adi Gangga; Gusti Z. Anshari; Joni Jupesta; Jennifer C. Bowen; Nurul Silva Lestari; J. Boone Kauffman; Alison M. Hoyt; Clarice R. Perryman; Israr Albar; et al. (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Assessment of endogenous and exogenous silver nanoparticles effects on the microalgae Chlorella vulgaris - Natalí Romero; Adrianne Brito; Horacio E. Troiani; Iseli L. Nantes; Guillermo R. Castro; Ana M. Gagneten (World Journal of Microbiology and Biotechnology, 2024)

Testing molecular date estimates using an ecological and vicariant case study in treefrogs: The Geological‐Ecological Molecular Calibration - Michael J. Jowers; Jesús Muñoz Pajares; John Weber; Jeanette Arkle; Salvador Arenas‐Castro; Simon Y. W. Ho; Gilson A. Rivas; John C. Murphy; Amaël Borzée; R. Alexander Pyron; Marcos Perez‐Losada; Mayke De Freitas; et al. (Journal of Biogeography, 2024)
Aim To date a vicariant event through the mutualistic relationship of a hylid frog and its bromeliad host found across two isolated mountain ranges as part of an island–continental split and to use this information to calibrate a molecular dating analysis of hylids. Location South America. Time Period Pliocene. Major Taxa Studied Treefrogs, Arboranae. Methods Pliocene tectonic movements sank a portion of a mountain range that connected present‐day Trinidad (island) and northern Venezuela, eventually isolating populations of the golden tree frog Phytotriades auratus and its host bromeliad Glomeropitcairnia erectiflora on both sides of a saltwater barrier. We estimated the submersion rate timing of the vicariant event, then employed ecological niche modelling to establish the distribution of the frog and its host to the Pliocene. We generated nucleotide sequence data for the hylid on each side of the marine barrier and proposed a biogeographic calibration for the split between populations. Using Bayesian phylogenetic analysis, we evaluated the impact of incorporating this biogeographic calibration on estimates of treefrog divergence times. Results A relatively continuous, high‐elevation mountain range existed before the Pliocene and the opening of the Gulf of Paria (4.45 ± 0.85 Ma). Phytotriades auratus and G. erectiflora would have been distributed across the Paria and Northern Range mountains as a single population since the Pliocene. Divergence times among treefrogs (Arboranae) were older than those inferred using fossil calibrations alone, with mean age estimates for subfamilies and genera being ~2 and ~1.2 million years older, respectively. Main Conclusions Our study presents a biogeographic calibration based on a vicariant model that connects the evolution of the populations of a hylid through geology and ecological data. The implementation of this date as a molecular clock calibration reduces the uncertainty in date estimates for the shallower nodes in the phylogeny of Arboranae.

Effects of the harmful algal bloom toxin, okadaic acid, on the mechanoreceptors of larval anchoveta (Engraulis ringens) under varying environmental conditions - Piera Pepe-Vargas; Leonardo R. Castro; Catharina Alves-de-Souza; Alejandra Llanos-Rivera (Frontiers in Marine Science, 2024)
The effect of the combination of marine toxins produced by algal blooms, in conjunction with varying environmental characteristics on organisms in the water column, is a poorly explored research field. Pelagic fish species of commercial importance, such as anchoveta ( Engraulis ringens ) in central Chile, may be exposed to these combined factors in a climate change scenario. This is observed from documented changes in the length of the upwelling season, frequency of upwelling events, and the increased frequency of atmospheric rivers affecting the southern spawning zone of this species. This study evaluated the integrity of hair cells in neuromasts, mechanosensory organs present in fish larvae, under exposure to different combinations of the algal bloom-produced okadaic acid OA (1 ng mL −1 ), and two temperature (12 and 14°C), and salinity treatments (historically more frequent: 34 PSU- 12°C; expected: 32 PSU - 14°C). Viable hair cells were counted in newly hatched larvae from the Biobío region, central Chile. Results showed a significant decrease in the average number of viable hair cells per neuromast (from 6.1 ± 1.6 to 4.0 ± 1.2) under lower salinity treatments (32 PSU) compared to normal conditions. Additionally, a seasonal trend was observed with fewer viable cells (from 7.4 ± 1.2 to 4.4 ± 1.1) as the fish species’ reproductive period progressed. The combined effect of OA exposure and modifications with the environmental factors also resulted in a significant decrease of up to 70% in the number of viable hair cells in larvae exposed to OA and high temperatures, indicating damage influenced by the toxin along with a synergistic and/or additive role of temperature. These findings reveal how the lipophilic toxin okadaic acid, produced by harmful algal blooms, interacts with abiotic environmental factors affecting coastal ecologically and socio-economically important organisms. This emphasizes the need to consider multiple factors when studying the effects of marine toxins.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Magnetic nanostructured agents for the mitigation of mycotoxins and cyanotoxins in the food chain - Jesús M. González-Jartín; Lisandra de Castro Alves; Y. Piñeiro; Amparo Alfonso; Rebeca Alvariño; Manuel González Gomez; Mercedes R. Vieytes; J. Rivas; Luis M. Botana (Food Chemistry, 2024)

Protease inhibitors characterisation by SDS-PAGE and MALDI-TOF from Alocasia macrorrhizos and their modulation of macrophage immune-inflammatory properties - Isac H. Cordeiro; Nerilson M. Lima; Elaine C. Scherrer; Gabriela P. Carli; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Marcone A. L. de Oliveira; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2024)

Periorbital necrotizing fasciitis: clinical perspectives on nine cases - David Oliver-Gutierrez; R. L. P. van der Veen; Elena Ros-Sánchez; Gloria Segura-Duch; Tirso Alonso; Alejandra Herranz-Cabarcos; Jessica Matas; Roberto Castro Seco; Miguel Ángel Arcediano; Miguel Ángel Zapata; Joan Oliveres (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Beyond counting calls: estimating detection probability for Antarctic blue whales reveals biological trends in seasonal calling - Franciele R. de Castro; Danielle V. Harris; Susannah J. Buchan; Naysa Balcazar; Brian S. Miller (Frontiers in Marine Science, 2024)
We explore the utility of estimating the density of calls of baleen whales for better understanding acoustic trends over time. We consider as a case study stereotyped ‘song’ calls of Antarctic blue whales ( Balaenoptera musculus intermedia ) on their Antarctic feeding grounds over the course of a year-long, continuous recording from 2014. The recording was made in the Southern Ocean from a deep-water autonomous hydrophone moored near the seafloor in the Eastern Indian sector of the Antarctic. We estimated call density seasonally via a Monte-Carlo simulation based on the passive sonar equation, and compared our estimates to seasonal estimates of detection rate, which are commonly reported in acoustic studies of Antarctic blue whales. The resulting seasonal call densities at our Antarctic site were strongly influenced by seasonally varying noise levels, which in turn yielded seasonal differences in detection range. Incorporating the seasonal estimates of detection area into our analysis revealed a pattern of call densities in accord with historic (non-acoustic) knowledge of Antarctic blue whale seasonal distribution and migrations, a pattern that differed from seasonal detection rates. Furthermore, our methods for estimating call densities produced results that were more statistically robust for comparison across sites and time and more meaningful for interpretation of biological trends compared to detection rates alone. These advantages came at the cost of a more complex analysis that accounts for the large variability in detection range of different sounds that occur in Antarctic waters, and also accounts for the performance and biases introduced by automated algorithms to detect sounds. Despite the additional analytical complexities, broader usage of call densities, instead of detection rates, has the potential to yield a standardized, statistically robust, biologically informative, global investigation of acoustic trends in baleen whale sounds recorded on single hydrophones, especially in the remote and difficult to access Antarctic.

New MMO coatings for electro-refinery applications: Promoting the production of carboxylates - Raira S.S. Castro; Géssica O.S. Santos; Marcos R.V. Lanza; Giancarlo R. Salaza-Banda; Katlin I.B. Eguiluz; Manuel A. Rodrigo; Cristina Sáez (Chemosphere, 2024)

P21-75 Protective effect of the carotenoid astaxanthin against Pb-induced cytotoxicity in human kidney cells - A.S. Cândido; R. Manguinhas; R.B. Soares; D.C. Carreira; M. Castro; M.F. Cabral; N.G. Oliveira (Toxicology Letters, 2024)

Deadwood decomposition in burnt mediterranean pine reforestations across an elevation gradient: A 15-year study - R. Juan-Ovejero; M.P. Reyes-Martín; A. Elghouat; A.B. Leverkus; S. Seibold; J. Castro (Forest Ecology and Management, 2024)

Konjac glucomannan: A comprehensive review of its extraction, health benefits, and pharmaceutical applications - Devesh U. Kapoor; Himanshu Sharma; Rahul Maheshwari; Ashutosh Pareek; Mansi Gaur; Bhupendra G. Prajapati; Guillermo R. Castro; Kasitpong Thanawuth; Supakij Suttiruengwong; Pornsak Sriamornsak (Carbohydrate Polymers, 2024)

Sounds in common: Time-frequency as the classification parameters for pulsed sounds produced by Delphinus delphis - Bruna Pagliani; Thiago O.S. Amorim; Franciele R. de Castro; Artur Andriolo (Behavioural Processes, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Analysis of the influence of carbon dioxide and nitrogen gases on the stability of heavy oil–water emulsions - Mayara da Silva; Cristina M.S. Sad; Rayane R.B. Corona; Laine B. Pereira; Edna F. Medeiros; Paulo R. Filgueiras; Valdemar Lacerda; Eustáquio V.R. Castro (Fuel, 2024)

Aging- and alcohol-associated spatial transcriptomic signature in mouse acute pancreatitis reveals heterogeneity of inflammation and potential pathogenic factors - Rachel R. Tindall; Yuntao Yang; Isabella Hernandez; Amy Qin; Jiajing Li; Yinjie Zhang; Thomas H. Gomez; Mamoun Younes; Qiang Shen; Jennifer M. Bailey-Lundberg; Zhongming Zhao; Daniel Kraushaar; et al. (Journal of Molecular Medicine, 2024)
The rapidly aging population is consuming more alcohol, leading to increased alcohol-associated acute pancreatitis (AAP) with high mortality. However, the mechanisms remain undefined, and currently there are no effective therapies available. This study aims to elucidate aging- and alcohol-associated spatial transcriptomic signature by establishing an aging AAP mouse model and applying Visium spatial transcriptomics for understanding of the mechanisms in the context of the pancreatic tissue. Upon alcohol diet feeding and caerulein treatment, aging mice (18 months) developed significantly more severe AAP with 5.0-fold increase of injury score and 2.4-fold increase of amylase compared to young mice (3 months). Via Visium spatial transcriptomics, eight distinct tissue clusters were revealed from aggregated transcriptomes of aging and young AAP mice: five acinar, two stromal, and one islet, which were then merged into three clusters: acinar, stromal, and islet for the comparative analysis. Compared to young AAP mice, > 1300 differentially expressed genes (DEGs) and approximately 3000 differentially regulated pathways were identified in aging AAP mice. The top five DEGs upregulated in aging AAP mice include Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp with heterogeneous distributions among the clusters. Taken together, this study demonstrates spatial heterogeneity of inflammatory processes in aging AAP mice, offering novel insights into the mechanisms and potential drivers for AAP development. Key messages Mechanisms regarding high mortality of AAP in aging remain undefined. An aging AAP mouse model was developed recapturing clinical exhibition in humans. Spatial transcriptomics identified contrasted DEGs in aging vs. young AAP mice. Top five DEGs were Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp in aging vs. young AAP mice. Our findings shed insights for identification of molecular drivers in aging AAP.

SpinelVA. A new perspective for the visual analysis and classification of spinel group minerals - Antonella S. Antonini; Leandro Luque; Gabriela R. Ferracutti; Ernesto A. Bjerg; Silvia M. Castro; María Luján Ganuza (Earth Science Informatics, 2024)

Organic petrology and geochemistry data reveal depositional and thermal history of coal in the Guaduas formation, Colombian Eastern Cordillera - L. Camacho-Aristizabal; L. Burnaz; L. Castro-Vera; L. Mojica Silva; R. Littke (International Journal of Coal Geology, 2024)

Recovering and reusing water, H2SO4, nickel and cobalt from gold mining wastewater using air-gap membrane distillation and solvent extraction - Victor R. Moreira; Livia M.C. Castro; Julio C. Balarini; Tania L.M. Santos; Míriam C.S. Amaral (Desalination, 2024)

Thermodynamic and economic analysis of a deployable and scalable process to recover Monomer-Grade styrene from waste polystyrene - Madison R. Reed; Elizabeth R. Belden; Nikolaos K. Kazantzis; Michael T. Timko; Bernardo Castro-Dominguez (Chemical Engineering Journal, 2024)

Synthesis of GO-Fe3O4/Ag and its Evaluation in the Aqueous Removal of Pb (II) and Methylene Blue - L. G. García; R. Pérez; Nicolás Cayetano-Castro; G. Rosas (Water, Air, & Soil Pollution, 2024)

Proteomic features of gray matter layers and superficial white matter of the rhesus monkey neocortex: comparison of prefrontal area 46 and occipital area 17 - Paola B. Castro-Mendoza; Christina M. Weaver; Wayne Chang; Maria Medalla; Kathleen S. Rockland; Lisa Lowery; Elizabeth McDonough; Merina Varghese; Patrick R. Hof; Dan E. Meyer; Jennifer I. Luebke (Brain Structure and Function, 2024)
In this novel large-scale multiplexed immunofluorescence study we comprehensively characterized and compared layer-specific proteomic features within regions of interest of the widely divergent dorsolateral prefrontal cortex (A46) and primary visual cortex (A17) of adult rhesus monkeys. Twenty-eight markers were imaged in rounds of sequential staining, and their spatial distribution precisely quantified within gray matter layers and superficial white matter. Cells were classified as neurons, astrocytes, oligodendrocytes, microglia, or endothelial cells. The distribution of fibers and blood vessels were assessed by quantification of staining intensity across regions of interest. This method revealed multivariate similarities and differences between layers and areas. Protein expression in neurons was the strongest determinant of both laminar and regional differences, whereas protein expression in glia was more important for intra-areal laminar distinctions. Among specific results, we observed a lower glia-to-neuron ratio in A17 than in A46 and the pan-neuronal markers HuD and NeuN were differentially distributed in both brain areas with a lower intensity of NeuN in layers 4 and 5 of A17 compared to A46 and other A17 layers. Astrocytes and oligodendrocytes exhibited distinct marker-specific laminar distributions that differed between regions; notably, there was a high proportion of ALDH1L1-expressing astrocytes and of oligodendrocyte markers in layer 4 of A17. The many nuanced differences in protein expression between layers and regions observed here highlight the need for direct assessment of proteins, in addition to RNA expression, and set the stage for future protein-focused studies of these and other brain regions in normal and pathological conditions.

Antimicrobial resistance patterns of Staphylococcus spp. isolated from clinical specimens of companion animals in Northern Portugal, 2021–2023 - D. Araújo; R. Oliveira; B.L. Silva; J. Castro; C. Ramos; F. Matos; C. Almeida; S. Silva (The Veterinary Journal, 2024)

Distribution, diversity and genetic structure of alders (Alnus lusitanica and A. glutinosa) in Spain - M. Angela Martín; R. Moreno; J.V. Die; A. Cabrera; P. Castro; M.D. Pérez; C. Palomino; B. Cuenca; F. Pérez; A. Solla (Forest Ecology and Management, 2024)

Blown film of PLA for packaging with green tea and fish industrial residues: An insight on their properties - Pedro V. Rodrigues; Ana B. Cunha; Mariana A. Andrade; Fernanda Vilarinho; Ana Vera Machado; M. Cidália R. Castro (Food Packaging and Shelf Life, 2024)

Toxicity of butylone and its enantiomers to Daphnia magna and its degradation/toxicity potential using advanced oxidation technologies - Ana R. Carvalho; Ana M. Morão; Virgínia M.F. Gonçalves; Maria Elizabeth Tiritan; Ana M. Gorito; M.Fernando Pereira; Adrián M.T. Silva; Bruno B Castro; João S. Carrola; Maria M. Amorim; Ana R.L. Ribeiro; Cláudia Ribeiro (Aquatic Toxicology, 2024)

A Review on the State of the Art in Frugivory and Seed Dispersal on Islands and the Implications of Global Change - Manuel Nogales; Kim R. McConkey; Tomás A. Carlo; Debra M. Wotton; Peter J. Bellingham; Anna Traveset; Aarón González-Castro; Ruben Heleno; Kenta Watanabe; Haruko Ando; Haldre Rogers; Julia H. Heinen; et al. (The Botanical Review, 2024)
We provide an overview of the current state of knowledge of island frugivory and seed dispersal and identify knowledge gaps that are important for fundamental research on—and applied conservation of—island ecosystems. We conducted a systematic literature search of frugivory and seed dispersal on islands, omitting large, continental islands. This revealed a total of 448 studies, most (75%) published during the last two decades, especially after 2010. Nearly 65% of them were focused on eight archipelagos. There is a paucity of studies in Pacific archipelagos near Asia and Australia, and in the Indian Ocean. Data on island frugivory and seed dispersal are diverse but highly uneven in geographic and conceptual coverage. Despite their limited biodiversity, islands are essential reservoirs of endemic plants and animals and their interactions. Due to the simplicity of insular ecosystems, we can assess the importance of seed dispersal theory and mechanisms at species and community levels. These include the ecological and biogeographical meaning and prevalence of non-standard mechanisms of seed dispersal on islands; the seed dispersal effectiveness and the relative roles of different frugivore guilds (birds and reptiles being the most important); and patterns of community organization and their drivers as revealed by interaction networks. Island systems are characterized by the extinction of many natives and endemics, and high rates of species introductions. Therefore, understanding how these losses and additions alter seed dispersal processes has been a prevailing goal of island studies and an essential foundation for the effective restoration and conservation of islands.

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

Impact of defibrillation technique on the rheological, thermo-mechanical, and nutritional properties of nanosuspensions produced from multiple fractions of pinhão seed (Araucaria angustifolia (Bertol.) Kuntze) - Fernando Castro Leal; Karina Mayumi Ueda; Matheus Samponi Tucunduva Arantes; Tielidy Angelina de Morais de Lima; Fabrício Augusto Hansel; Washington Luiz Esteves Magalhães; Cristiane Vieira Helm; Rilton Alves de Freitas; Fabiane Oliveira Farias; Marcos R. Mafra; Luciana Igarashi-Mafra (Food Chemistry, 2024)

Biodegradable PBAT/PLA blend films incorporated with turmeric and cinnamomum powder: A potential alternative for active food packaging - Layara L.R.L. de Castro; Lauriene G.L. Silva; Iago R. Abreu; Cristiano J.F. Braz; Samara C.S. Rodrigues; Regilda S. dos R. Moreira-Araújo; Rudy Folkersma; Laura H. de Carvalho; Renata Barbosa; Tatianny S. Alves (Food Chemistry, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

The key role played by mesoporous alumina as binder for obtaining ultra-hard CaO based pellets for thermochemical heat storage leveraging the CaO/CaCO3 cycle - D. Castro-Yáñez; M. Erans; A. Peral; R. Sanz; J. González-Aguilar; M. Romero; L. Briones; E.S. Sanz-Pérez; J.M. Escola (Journal of Cleaner Production, 2024)

Reducing citrus effluent toxicity: Biological-electrochemical treatment with diamond anode - Débora S. Vilar; Hugo H. Correia da Silva; Aline R. Dória; Nádia H. Torres; José H. Vallim; Vera L.S. Salgado de Castro; Juliana Heloisa Pinê Américo-Pinheiro; Giancarlo R. Salazar-Banda; Katlin I. Barrios Eguiluz; Luiz Fernando R. Ferreira (Environmental Pollution, 2024)

New hard tick (Acari: Ixodidae) reports and detection of Rickettsia in ticks from Sierra Nevada de Santa Marta, Colombia - Ángel Oviedo; Miguel M. Rodríguez; Fernando S. Flores; Lyda R. Castro (Experimental and Applied Acarology, 2024)
The Sierra Nevada de Santa Marta (SNSM), located in northern Colombia, is considered a geographical island with high levels of biodiversity and endemism. However, little is known about tick species and their associated microorganisms at the SNSM. In this study we sampled host-seeking ticks in areas of the town of Minca within the SNSM. We collected 47 ticks identified as Amblyomma pacae , Amblyomma longirostre , Amblyomma ovale , Amblyomma mixtum , Haemaphysalis juxtakochi , Ixodes sp. cf. Ixodes affinis and Ixodes sp. Of these ticks, we tested for Rickettsia spp. by amplifying the gltA , SCA1 , and 16S rRNA genes via PCR. Rickettsia amblyommatis was detected in one pool of 3 larvae and in a female of A. pacae . Additonally, we isolated Rickettsia sp. belonging to the group of spotted fevers in larvae of A. longirostre . This study reports new findings of six species of ticks and two species of Rickettsia within the SNSM.

Database of immature stage traits of Ephemeroptera, Plecoptera, and Trichoptera (EPT) genera for the Amazon - Natália Beatriz Barros Santos; Gabriel Martins Cruz; Josinete Sampaio Monteles; Ana Paula Justino de Faria; Viviane Caetano Firmino; Yulie Shimano; Victor Rennan Santos Ferreira; Ana Luiza-Andrade; Frederico Falcão Salles; Diego M. P. Castro; Fábio B. Quinteiro; Lucas R. C. Lima; et al. (Aquatic Sciences, 2024)

Resilience of Ricinus communis L. to high temperatures during germination and seedling growth resulting from efficient superoxide dismutase modulation - Valdir G. Neto; Wilco Ligterink; Henk W. M. Hilhorst; Isabela D. Santos; Carine R. Teixeira; Emily E. Santos; Marta B. Loureiro; Daniele Takahashi; Luzimar G. Fernandez; Paulo R. Ribeiro; Renato D. De Castro (Brazilian Journal of Botany, 2024)

Leucaena leucocephala toxicity in Brazilian horses - Mizael Machado; Cintia R.R. Queiroz-Machado; Dale R. Gardner; Márcio B. Castro; Antônio Carlos L. Câmara; Luciano A. Pimentel; Glauco J.N. Galiza; Franklin Riet-Correa (Toxicon, 2024)

What makes a cyanobacterial bloom disappear? A review of the abiotic and biotic cyanobacterial bloom loss factors - Ted D. Harris; Kaitlin L. Reinl; Marzi Azarderakhsh; Stella A. Berger; Manuel Castro Berman; Mina Bizic; Ruchi Bhattacharya; Sarah H. Burnet; Jacob A. Cianci-Gaskill; Lisette N. de Senerpont Domis; Inge Elfferich; K. Ali Ger; et al. (Harmful Algae, 2024)

Analysis of gaseous emission and particle number size distributions in metal casting processes with binder jetting moulds - C. Blanco-Alegre; A.I. Calvo; M.Á. Castro-Sastre; A.I. Fernández-Abia; P. Rodríguez-González; F. Oduber; A. Castro; J. Barreiro; R. Fraile (Building and Environment, 2024)

Large-scale crops are sources of polyphagous pest populations for small farmers at the landscape level: an isotope tracing model - Érika C. S. Castro; Nícholas F. Camargo; Danyelle R. Novaes; Marina A. M. Pereira; Gabriela B. Nardoto; Pedro H. B. Togni (Journal of Pest Science, 2024)

Effects of parity, seasonal heat stress, and colostrum collection time postpartum on colostrum quality of Holstein cattle in an arid region - L. Avendaño-Reyes; U. Macías-Cruz; M. A. Sánchez-Castro; F. Anzures-Olvera; R. Vicente-Pérez; M. Mellado; R. Zamorano-Algándar; P. H. Robinson; V. J. Castañeda-Bustos; A. López-Baca (International Journal of Biometeorology, 2024)

Empirical ground-motion relations of peak ground acceleration in the region of the Gulf of California - Gina P. Villalobos-Escobar; Raúl R. Castro; Tomás A. Peña-Alonso (Natural Hazards, 2024)

Urban socio-ecosystem renewal: an ecosystem services assessment approach - M. LopezDeAsiain; J. M. Castro Bonaño; M. Borrallo-Jiménez; R. Mora Esteban (International Journal of Environmental Science and Technology, 2024)
Using a novel approach based on the urban ecosystem services approach, this research explores the relation between socio-economic, architectonic and ecological factors in urban renewal processes. This deductive conceptual approach is based on the definition of an urban diagnosis and intervention model based on the concept of urban socio-ecosystemic services. This conceptual approach is applied to three research cases in Andalusia (Spain) neighbourhoods linked to participatory urban renewal processes. A model is inductively defined from these analysed case studies: the socio-ecosystemic services model, based on the conceptual frame, the development of particular instruments and the definition of a participatory methodological strategy. The results obtained in these urban workshops show that the socio-ecosystem model better integrates the relationships between the architectural, socio-economic and ecological dimensions in addressing the need for urban services and infrastructure and the quality of life in neighbourhoods. Citizens can formulate their needs and perceptions of the neighbourhood beyond traditional quantitative variables (i.e. number of car parks, average size of dwellings, population density, etc.), incorporating aspects such as urban landscape, air quality, urban noise, shaded rest areas and children’s spaces. All these perceptions are collected and transformed into proposals for neighbourhood improvement, which are assessed and prioritized by the citizens. Together with participatory processes, this approach can be considered as the key to success in urban renewal strategies in neighbourhoods. However, it is necessary to develop indicators and metrics of the relationships between the socio-economic and ecological dimensions that allow a more integrated study of the model at different urban scales.

Congruence between microsatellite loci, SNPs, and COI gene reveals a phylogeographic break in the southern Caribbean Sea: The case of West Indian top shell Cittarium pica (Gastropoda: Tegulidae) - Juan Carlos Narváez Barandica; Julian F. Quintero-Galvis; Ana Caruso Vargas; Germán Blanco Cervantes; Juan Carlos Aguirre Pabón; Lyda Castro García; Ricardo Betancur-R.; Arturo Acero P. (Fisheries Research, 2024)

The role of snow in scavenging aerosol particles: A physical-chemical characterization - C. Blanco-Alegre; A.I. Calvo; A. Castro; F. Oduber; E. Alonso-Blanco; C. Alves; M. Cerqueira; R. López; F. Lucarelli; S. Nava; G. Calzolai; R. Fraile (Science of The Total Environment, 2024)

Vertically distinct sources modulate stable isotope signatures and distribution of Mesozooplankton in central Patagonia: The Golfo de Penas - Baker Channel connection and analogies with the Beagle Channel - Leonardo R. Castro; Samuel Soto-Mendoza; Luciana Riccialdelli; María L. Presta; Pamela Barrientos; Humberto E. González; Giovanni Daneri; Marcelo Gutiérrez; Paulina Montero; Italo Masotti; Beatriz Díez (Journal of Marine Systems, 2024)

Improvement in Sunlight-Irradiated Photocatalytic Activity and Stability of Ca10(PO4)6(OH)2/g-C3N4 for Dye Mixture Degradation - Mário A. M. Castro; José Victor S. Galvão; Débora F. S. Morais; Marcio D. Teodoro; Ricardo P. Souza; Maurício R. D. Bomio; Fabiana V. Motta (Water, Air, & Soil Pollution, 2024)

Ecological thresholds of Odonata larvae to anthropogenic disturbances in neotropical savanna headwater streams - Larissa F. R. Silva; Diego M. P. Castro; Leandro Juen; Marcos Callisto; Robert M. Hughes; Marcel G. Hermes (Hydrobiologia, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Monitoring corn nitrogen nutrition index from optical and synthetic aperture radar satellite data and soil available nitrogen - Adrián M. Lapaz Olveira; Mauricio Castro-Franco; Hernán R. Saínz Rozas; Walter D. Carciochi; Mónica Balzarini; Oscar Avila; Ignacio Ciampitti; Nahuel I. Reussi Calvo (Precision Agriculture, 2023)

Variation in the fatty acid composition of microalgal lipids due to the effect of the extraction method - F. V. Pérez-Barradas; L. A. Ortega-Clemente; I. A. Pérez-Legaspi; M. I. Jiménez-García; A. A. Huerta-Heredia; R. Quintana-Castro (Journal of Applied Phycology, 2023)

Quantification of soil N2O and CH4 fluxes using the flux gradient method on a drainage water managed farm on the eastern shore of Maryland - Qiurui Zhu; Eric A. Davidson; Jacob G. Hagedorn; Mark S. Castro; Thomas R. Fisher; Rebecca J. Fox; Shannon E. Brown; James W. Lewis (Agricultural and Forest Meteorology, 2023)

Who are the superhosts? The chemical and structural profiles of superhosts of galling arthropods and the gaps in gall studies - Gabriela S. Martins; Leticia P. Nobrega; Rayssa R. M. Castro; Filipe R. Valeriano; Leonardo G. Sant’Anna; Pedro E. F. Barbosa; Bruno G. Ferreira (Arthropod-Plant Interactions, 2023)

Isolation drives species gains and losses of insect metacommunities over time in a mountaintop forest archipelago - Pedro Giovâni da Silva; Marina do Vale Beirão; Flávio Siqueira de Castro; Lucas Neves Perillo; Flávio Camarota; Ricardo R. C. Solar; Geraldo Wilson Fernandes; Frederico de Siqueira Neves (Journal of Biogeography, 2023)
Aim We evaluated the effects of forest island size, isolation and area in the landscape driving temporal changes of insect biodiversity in a mountaintop forest archipelago. We expected that (i) in smaller, less isolated forest islands, changes in insect composition are more prominent, primarily driven by gains over time; (ii) more forest in the landscape leads to increased gains of vagile species over time, regardless of forest island size and isolation; (iii) less vagile groups undergo heterogenisation, while highly vagile groups experience homogenisation due to differing dispersal capabilities. Location Espinhaço Range Biosphere Reserve, Brazil. Taxon Insects. Methods We used ants, dung beetles, bees, wasps and butterflies as study models to represent a gradient of low‐to‐high dispersal capability. We evaluated the colonisation‐ and extirpation‐resultant components of temporal β‐diversity using area‐ and isolation‐related variables as predictors. Results Distinct colonisation‐ and extirpation‐resultant homogenisation and heterogenisation processes are acting according to each insect group, likely due to different dispersal capabilities. Species losses dominated in ants, with widespread and rare species being lost. Butterflies gained species, represented mainly by widespread species, leading to an increased colonisation‐resultant homogenisation. Distance to neighbouring forest islands was the underlying predictor affecting the temporal β‐diversity of insect groups, and also species gains and losses but differently according to the survey period. Effects of the forest amount in the landscape increased the temporal β‐diversity of bees and butterflies but decreased that of ants, dung beetles and wasps. Main Conclusions These findings provide valuable biogeographic insights into the complex interactions between forest island characteristics, landscape attributes, and dispersal capabilities that shape the temporal dynamics of insect biodiversity on mountaintops. Conserving the forest amount in the landscape and keeping forest connectivity among forest islands are necessary because the temporal dynamics of local colonisation and extirpation can depend on the organisms' dispersal capability.

Dietary oleic acid supplementation improves feed efficiency and modulates fatty acid profile and cell signaling pathway in European sea bass (Dicentrarchus labrax) juveniles fed high-lipid diets - Nicole Martins; Rui Magalhães; Lúcia Vieria; Ana Couto; Cláudia R. Serra; Margarida R.G. Maia; António J.M. Fonseca; Ana R.J. Cabrita; Pedro Pousão-Ferreira; Carolina Castro; Helena Peres; Aires Oliva-Teles (Aquaculture, 2023)

Contribution of the nursery areas to the major fishing grounds of the Brazilian sardine (Sardinella brasiliensis) in Southeastern Brazilian Bight inferred from otolith fingerprints - Rafael Schroeder; Paulo R. Schwingel; Richard Schwarz; Felippe A. Daros; Taynara P. Franco; Natasha T. Hoff; Ana Méndez Vicente; Jorge P. Castro; André M. Vaz-dos-Santos; Alberto T. Correia (Fisheries Research, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Limited population genetic structure in the littoral gastropod Nerita tessellata (Neritimorpha, Neritidae) suggests high dispersal across the Caribbean Sea - Julian F. Quintero-Galvis; Korina Ocampo-Zuleta; Lyda R. Castro; Juan Carlos Narváez-Barandica (Journal of Experimental Marine Biology and Ecology, 2023)

Altered E-cadherin/β-catenin expression in feline cutaneous squamous cell carcinomas - Berenice L. Sanz Ressel; Gimena Gomez Castro; Adriana R. Massone; Claudio G. Barbeito (Journal of Comparative Pathology, 2023)

Hepatocellular carcinoma induced by hepatocyte Pten deletion reduces BAT UCP-1 and thermogenic capacity in mice, despite increasing serum FGF-21 and iWAT browning - Álbert S. Peixoto; Mayara F. Moreno; Érique Castro; Luiz A. Perandini; Thiago Belchior; Tiago E. Oliveira; Thayna S. Vieira; Gustavo R. Gilio; Caroline A. Tomazelli; Bianca F. Leonardi; Milene Ortiz-Silva; Luciano P. Silva Junior; et al. (Journal of Physiology and Biochemistry, 2023)

Age, growth, and feeding of boarfish, Capros aper (Linnaeus, 1758) in the Southwest of the Iberian Peninsula - J. Castro-Gutiérrez; A. García-González; C. Rodríguez-García; Á. R. Domínguez-Bustos; R. Cabrera-Castro (Marine Biology Research, 2023)

A new method for extraction and pre-concentration of the heavy metals using a microemulsion system in winsor II equilibrium and determination by HR-CS AAS - Emily Cintia Tossi de A. Costa; Tereza N. de Castro Dantas; Djalma R. da Silva; Tatiane de A. Maranhão (Chemosphere, 2023)

Whose values count? A review of the nature valuation studies with a focus on justice - M Schaafsma; S Ahn; AJ Castro; N Dendoncker; A Filyushkina; D González-Jiménez; Mariaelena Huambachano; N Mukherjee; TH Mwampamba; J Ngouhouo-Poufoun; I Palomo; R Pandit; et al. (Current Opinion in Environmental Sustainability, 2023)

Mobile terrestrial laser scanner vs. UAV photogrammetry to estimate woody crop canopy parameters – Part 1: Methodology and comparison in vineyards - Alexandre Escolà; José M. Peña; Francisca López-Granados; Joan R. Rosell-Polo; Ana I. de Castro; Eduard Gregorio; Francisco M. Jiménez-Brenes; Ricardo Sanz; Francesc Sebé; Jordi Llorens; Jorge Torres-Sánchez (Computers and Electronics in Agriculture, 2023)

Mobile terrestrial laser scanner vs. UAV photogrammetry to estimate woody crop canopy parameters – Part 2: Comparison for different crops and training systems - Jorge Torres-Sánchez; Alexandre Escolà; Ana Isabel de Castro; Francisca López-Granados; Joan R. Rosell-Polo; Francesc Sebé; Francisco Manuel Jiménez-Brenes; Ricardo Sanz; Eduard Gregorio; José M. Peña (Computers and Electronics in Agriculture, 2023)

P03-24: Impact of cadmium on cell viability and migration of human lung cells in vitro - D.C. Carreira; R. Manguinhas; R.B. Soares; N. Gil; M. Castro; J.P. Miranda; N.G. Oliveira (Toxicology Letters, 2023)

Seismicity and state of stress in the north-central region of the Gulf of California, Mexico - Favio Cruz-Hernández; Raúl R. Castro-Escamilla; Juan A. Mendoza-Camberos; Arturo Pérez-Vertti (Tectonophysics, 2023)

Temporal and spatial evolution of the 2021 eruption in the Tajogaite volcano (Cumbre Vieja rift zone, La Palma, Canary Islands) from geophysical and geodetic parameter analyses - M. B. Benito; G. E. Alvarado; M. Marchamalo; J. G. Rejas; P. Murphy; R. Franco; D. Castro; C. Garcia-Lanchares; J. Sanchez (Natural Hazards, 2023)
The eruption of the Tajogaite volcano in 2021, in the Cumbre Vieja rift zone (La Palma, Canary Islands), is the most recent but also the most damaging and longest-lasting eruption on the island since historical records began. We analyzed geophysical parameters (seismicity, surface deformation, thermal anomalies, and volcanic activity) with the aim of reconstructing the temporal development of the magma plumbing system. The seismic sequence (> 9000 events, mbLg ≤ 5.0) can be grouped into nine distinct phases, which correspond to well-separated spatial clusters and distinct earthquake regimes. A strong premonitory thermal anomaly was calculated on July 2021 in the South of La Palma. The source of the magma was within the upper mantle (40–20 km depth). A second magma budget (< 15 km depth) indicated a short-term stagnation of alkaline magma within the lower crust, near the Moho. The outline of these earthquakes delineates the magma pathway. Just before and immediately after the eruption (phases 2 and 3), the high-frequency seismicity in the mantle disappeared completely, reappearing ten days after the eruption started. The pattern of deformation began before the eruption with a breakpoint around September 11, after which, deformation accelerated sharply, followed by stabilization in phase 3 and a decrease in the following phases. The level of deformation suggested that a shallow magma intrusion was established. Based on the historical eruptive pattern, it is possible to infer two possible hazard-forecast scenarios: (a) the volcano could enter a prolonged phase of tranquility for more than one century or, (b) a new eruption could occur between ca. 2045 and 2065, with a slightly shorter duration than this recent one. Therefore, if the more pessimistic scenario is assumed, appropriate territorial planning is required.

Geometric morphometrics as a tool to identify Dasypodini osteoderms: Implications for the oldest records of Dasypus - Juan S. Salgado-Ahumada; Marcos D. Ercoli; Alicia Álvarez; Mariela C. Castro; Martín R. Ciancio (Journal of Mammalian Evolution, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Coastal warming under climate change: Global, faster and heterogeneous - R. Varela; M. de Castro; J.M. Dias; M. Gómez-Gesteira (Science of The Total Environment, 2023)

Antibiotics reduce Pocillopora coral‐associated bacteria diversity, decrease holobiont oxygen consumption and activate immune gene expression - Michael T. Connelly; Grace Snyder; Ana M. Palacio‐Castro; Phillip R. Gillette; Andrew C. Baker; Nikki Traylor‐Knowles (Molecular Ecology, 2023)
Corals are important models for understanding invertebrate host–microbe interactions; however, to fully discern mechanisms involved in these relationships, experimental approaches for manipulating coral–bacteria associations are needed. Coral‐associated bacteria affect holobiont health via nutrient cycling, metabolic exchanges and pathogen exclusion, yet it is not fully understood how bacterial community shifts affect holobiont health and physiology. In this study, a combination of antibiotics (ampicillin, streptomycin and ciprofloxacin) was used to disrupt the bacterial communities of 14 colonies of the reef framework‐building corals Pocillopora meandrina and P . verrucosa, originally collected from Panama and hosting diverse algal symbionts (family Symbiodiniaceae ). Symbiodiniaceae photochemical efficiencies and holobiont oxygen consumption (as proxies for coral health) were measured throughout a 5‐day exposure. Antibiotics altered bacterial community composition and reduced alpha and beta diversity, however, several bacteria persisted, leading to the hypothesis that these bacteria are either antibiotics resistant or occupy internal niches that are shielded from antibiotics. While antibiotics did not affect Symbiodiniaceae photochemical efficiency, antibiotics‐treated corals had lower oxygen consumption rates. RNAseq revealed that antibiotics increased expression of Pocillopora immunity and stress response genes at the expense of cellular maintenance and metabolism functions. Together, these results reveal that antibiotic disruption of corals' native bacteria negatively impacts holobiont health by decreasing oxygen consumption and activating host immunity without directly impairing Symbiodiniaceae photosynthesis, underscoring the critical role of coral‐associated bacteria in holobiont health. They also provide a baseline for future experiments that manipulate Pocillopora corals' symbioses by first reducing the diversity and complexity of coral‐associated bacteria.

Electrocoagulation treatment of furniture industry wastewater - Carolina Vicente; João R. Silva; Andreia D. Santos; João F. Silva; Jorge T. Mano; Luis M. Castro (Chemosphere, 2023)

Review of the adsorbents/catalysts for the removal of sulfur compounds from natural gas - Percival Soni Castro; Gerson Martinez Zuniga; William Holmes; Prashanth R. Buchireddy; Daniel D. Gang; Emmanuel Revellame; Mark Zappi; Rafael Hernandez (Gas Science and Engineering, 2023)

Water reclamation via membrane distillation applied to textile dye wastewater using a commercial poly(vinylidene fluoride) membrane - H. Ramlow; B. de Castro Santos; C. M. Tolentino Filho; C. D. K. Cavalcanti; R. A. F. Machado; C. Marangoni (International Journal of Environmental Science and Technology, 2023)

Dereplication of Siparuna brasiliensis extract with in vivo anti-inflammatory activity - Leandro A. Castro; Nerilson M. Lima; Gracimério J. Guarneire; Gabriela P. Carli; Allyne Aparecida S. Castro; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Boniek Gontijo Vaz; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2023)

Exploring the prevalence and antibiotic resistance profile of Klebsiella pneumoniae and Klebsiella oxytoca isolated from clinically ill companion animals from North of Portugal - D. Araújo; J. Castro; F. Matos; R. Oliveira; C. Ramos; C. Almeida; S. Silva (Research in Veterinary Science, 2023)

Epigenetic regulation of collagen in the mare's placenta: putative relationship with maternal age - Manuel A. Vasconcelos; Yat Wong; Joana Alpoim-Moreira; Maria R. Rebordão; Maria J. Fradinho; Ana L. Costa; Miguel Bliebernicht; Fidel O. Castro; Elisabete Silva; Graça M. Ferreira-Dias (Journal of Equine Veterinary Science, 2023)

Responses of ground-dwelling birds and mammals to local environmental variables and human pressure in an Amazonian protected area - Carlos R. Brocardo; Dian C. P. Rosa; Arlison B. Castro; Clarissa Rosa; Kelly Torralvo; Pedro Pequeno; William E. Magnusson; Rodrigo F. Fadini (European Journal of Wildlife Research, 2023)

Molecular detection of Burkholderia mallei in different geographic regions of Brazil - Paula A. Pereira Suniga; Cynthia Mantovani; Maria G. Santos; Juliana S. Gomes Rieger; Emanuelle B. Gaspar; Fernando Leandro dos Santos; Rinaldo A. Mota; Karla P. Chaves; Andréa A. Egito; José Carlos O. Filho; Alessandra F. Castro Nassar; Lenita Ramires dos Santos; et al. (Brazilian Journal of Microbiology, 2023)

Quantification of Wood Biomass in an Area of Sustainable Annual Production in the Brazilian Semiarid Region Aiming at Generating Renewable Energy - R. C. Santos; F. G. C. Pareyn; C. P. S. Santos; D. Minini; S. M. G. Rocha; F. J. O. Souza; L. F. C. Cezario; A. F. Dias Júnior; R. V. O. Castro (BioEnergy Research, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Spring plankton energy content by size classes in two contrasting environments of a high latitude ecosystem: The Beagle Channel - Daniel O. Bruno; Constanza Valencia-Carrasco; María A. Paci; Ezequiel Leonarduzzi; Leonardo Castro; Luciana Riccialdelli; Clara M. Iachetti; Andreana Cadaillon; Ricardo Giesecke; Irene R. Schloss; Carla F. Berghoff; Jacobo Martín; et al. (Journal of Marine Systems, 2023)

Data fusion applied in near and mid infrared spectroscopy for crude oil classification - Mariana K. Moro; Eustáquio V.R. de Castro; Wanderson Romão; Paulo R. Filgueiras (Fuel, 2023)

Job satisfaction and job security as moderators in the relationships among job demands, musculoskeletal symptoms, and work performance - Suyoung Kwon; A. B. de Castro; Jerald R. Herting; Soo-Jeong Lee; Kurt Johnson; Stephen Bao (International Archives of Occupational and Environmental Health, 2023)

Bacillus subtilis KM0 Impacts gut Microbiota Profile and Transcription of Genes Related to Transcellular Transport in Zebrafish (Danio rerio) - Caroline G. Castro; Marcela G. Meirelles; Raíza Azevedo; Jeferson V. Ramos; Tony L. R. da Silveira; Bruna F. Nornberg; Luis F. Marins (Current Microbiology, 2023)

Sulfolipid substitution ratios of Microcystis aeruginosa and planktonic communities as an indicator of phosphorus limitation in Lake Erie - Robbie M. Martin; Maddie K. Denney; Helena L. Pound; Justin D. Chaffin; George S. Bullerjahn; R. Michael L. McKay; Arthur Zastepa; Katarina A. Jones; Hector F. Castro; Shawn R. Campagna; Steven W. Wilhelm (Limnology and Oceanography, 2023)
Phosphorus (P) availability frequently limits primary production in lakes, influences the physiology of phytoplankton, shapes community structure, and can stimulate or constrain the formation of cyanobacterial blooms. Given the importance of P, numerous methods are available to assess P stress in phytoplankton communities. Marine phytoplankton are known to substitute sulfolipids for phospholipids in response to P limitation. We asked whether sulfolipid substitution might serve as an additional indicator of P stress in freshwater phytoplankton communities. The question was addressed using cultures of Microcystis aeruginosa , Lake Erie microcosms, and surveys of lipid profiles in Lake Erie during a Microcystis spp. bloom. Peak area response ratios of the intact polar lipids sulfoquinovosyldiacylglycerol (SQDG) to phosphatidylglycerol (PG) were used as the metric of lipid substitution. In cultures of M. aeruginosa NIES‐843, the SQDG : PG ratio increased from ~ 0.9 to ~ 3.3 with decreasing P concentration. In P‐limited communities, the SQDG : PG ratio increased from ~ 6 to ~ 11 after 48 h in microcosm controls, while P amendments reduced the ratio to ~ 3. In Lake Erie surveys, the SQDG : PG ratio ranged from ~ 0.4 to ~ 7.4 and was negatively correlated (Pearson r = −0.62) with total dissolved P. The SQDG : PG ratio was not correlated with concentrations of chlorophyll a , soluble reactive P, or N : P molar ratios. These results demonstrated that M. aeruginosa and Microcystis ‐dominated communities remodel lipid profiles in response to P scarcity, providing a potential short‐term, time‐integrated biomarker of nutrient history and P stress in fresh waters.

Metabolic profiling by LC-DAD-MS, FTIR, NMR and CE-UV of polyphenols with potential against skin pigmentation disorder - Isac H. Cordeiro; Nerilson M. Lima; Elaine C. Scherrer; Gabriela P. Carli; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Marcone A. L. de Oliveira; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2023)

The exposed Mule Creek vent deposits record the structure of a volcanic conduit during a hybrid explosive–effusive eruption - Holly E. Unwin; Hugh Tuffen; Fabian B. Wadsworth; Emrys R. Phillips; Mike R. James; Annabelle Foster; Stephan Kolzenburg; Jonathan M. Castro; Lucy A. Porritt (Bulletin of Volcanology, 2023)
Silicic volcanic eruptions commonly begin with the explosive ejection of pyroclastic material, before transitioning to gentler effusion-dominated activity. Well-exposed dissected silicic systems are scarce and poorly studied, hindering the advances in our understanding of the explosive–effusive transition needed to improve interpretations of volcanic unrest and hazard forecasting. The Mule Creek vent (New Mexico, USA) is a dissected silicic conduit that records the processes controlling conduit formation and evolution, and the role tuffisites (fractures filled with variably welded pyroclasts) play in conduit dynamics. Here, we use decimeter-scale photo-mapping of lithostratigraphic units and thin section analysis to differentiate and interpret three dominant emplacement styles during vent evolution. First, there was repeated deposition and erosion of pyroclastic material at the conduit walls, recorded by erosive surfaces in pyroclastic breccia and agglomerates at the conduit margins. Second, sub-vertical domains of dense melt-dominated magma were emplaced and preserved as glass-dominated vitrophyre and brecciated vitrophyre, with the textural hallmarks of assembly from welding of pyroclasts. Finally, the sub-horizontal fracturing of previously deposited lithologies produced laterally cross-cutting tuffisites. The vent deposits track the widening and then narrowing of the conduit through time and reflect progressive insulation and generally higher temperatures towards the conduit center as pyroclasts accumulate. Welding of pyroclastic fill and the formation of dense vitrophyres towards the conduit center lowers deposit porosity and effective wall permeability. This drives localized gas pressure increases and results in gas-driven fracturing, generating tuffisites, which act as transient outgassing pathways. The structure of the Mule Creek vent records an explosive–effusive transition, constraining the processes controlling conduit evolution and aiding our interpretation of volcanic unrest.

Novel clinical and immunological features associated with persistent post-acute sequelae of COVID-19 after six months of follow-up: a pilot study - Jiram Torres-Ruiz; Julieta Lomelín-Gascón; Jaquelin Lira Luna; Ana Sofia Vargas- Castro; Alfredo Pérez-Fragoso; Miroslava Nuñez-Aguirre; Beatriz Alcalá-Carmona; Abdiel Absalón-Aguilar; Jennifer T. Balderas-Miranda; José Luis Maravillas-Montero; Nancy R. Mejía-Domínguez; Carlos Núñez-Álvarez; et al. (Infectious Diseases, 2023)

Farmers’ perceptions and acceptance of crossbred guinea pigs in Mantaro Valley, Peru - J. I. Cedano-Castro; R. Jiménez; A. Huamán; G. Gutiérrez Reynoso; M. Wurzinger (Tropical Animal Health and Production, 2023)
This study aimed at assessing farmers’ perceptions and acceptance of the proposed breeding strategy of Instituto Veterinario de Investigaciones Tropicales y de Altura (IVITA), located in the Central Andes of Peru. A total of 34 farmers, who had received guinea pigs from IVITA, were interviewed. The questionnaire was performed in Spanish language and covered topics about the guinea pig production, feeding, mating system, training, the main products, perception and acceptance of crossbred lines (“cuy RG”), and the farmers’ comment about the terminal crossbred animal (“cuy G”). The preferred feeding strategy was a combination of forage and supplement. All farmers implemented a controlled mating system. Most farmers had received training on feeding, reproduction, management, equipment, and facilities. The main product is animals for slaughter. The 82.40% of farmers reported that they do not purchase guinea pigs from IVITA anymore, because they are highly susceptibility to lymphadenitis, which is a highly contagious disease and causes swollen lymph nodes and affects the meat quality. Most of the respondents classified the “cuy RG” and “cuy G” as suitable for meat production and were satisfied with the performance of the animals. Therefore, 58.80% of respondents already recommended “cuy RG” to other farmers. However, 17.70% of the respondents would not recommend these animals because they are susceptible to disease, especially lymphadenitis. Therefore, IVITA should engage in more structured dialogue with farmers and regularly include their opinion in future improvement of its breeding strategies. This could help to reach higher acceptance rates by farmers.

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Valorization of waste mill tailings from small-scale mining through geopolymerization: strength, durability, and heavy metal leaching potential - Christian R. Orozco; Kim Deirdre Lynn T. Castro; Ma. Mikaela T. De Boda (Journal of Soils and Sediments, 2023)

Acaricidal action of ozone on larvae and engorged females of Rhipicephalus microplus: a dose-dependent relationship - R. A. Castro; O. P. Neto; A. L. S. Mendes; L. H. Moreira (Experimental and Applied Acarology, 2023)

Effects of different management strategies on long‐term trends of Australian threatened and near‐threatened mammals - Ayesha I. T. Tulloch; Micha V. Jackson; Elisa Bayraktarov; Alexander R. Carey; Diego F. Correa‐Gomez; Michael Driessen; Ian C. Gynther; Mel Hardie; Katherine Moseby; Liana Joseph; Harriet Preece; Andrés Felipe Suarez‐Castro; et al. (Conservation Biology, 2023)
Monitoring is critical to assess management effectiveness, but broadscale systematic assessments of monitoring to evaluate and improve recovery efforts are lacking. We compiled 1808 time series from 71 threatened and near‐threatened terrestrial and volant mammal species and subspecies in Australia (48% of all threatened mammal taxa) to compare relative trends of populations subject to different management strategies. We adapted the Living Planet Index to develop the Threatened Species Index for Australian Mammals and track aggregate trends for all sampled threatened mammal populations and for small ( 5500 g) from 2000 to 2017. Unmanaged populations (42 taxa) declined by 63% on average; unmanaged small mammals exhibited the greatest declines (96%). Populations of 17 taxa in havens (islands and fenced areas that excluded or eliminated introduced red foxes [ Vulpes vulpes ] and domestic cats [ Felis catus ]) increased by 680%. Outside havens, populations undergoing sustained predator baiting initially declined by 75% but subsequently increased to 47% of their abundance in 2000. At sites where predators were not excluded or baited but other actions (e.g., fire management, introduced herbivore control) occurred, populations of small and medium mammals declined faster, but large mammals declined more slowly, than unmanaged populations. Only 13% of taxa had data for both unmanaged and managed populations; index comparisons for this subset showed that taxa with populations increasing inside havens declined outside havens but taxa with populations subject to predator baiting outside havens declined more slowly than populations with no management and then increased, whereas unmanaged populations continued to decline. More comprehensive and improved monitoring (particularly encompassing poorly represented management actions and taxonomic groups like bats and small mammals) is required to understand whether and where management has worked. Improved implementation of management for threats other than predation is critical to recover Australia's threatened mammals.

Characterization of proteases in the seminal plasma and spermatozoa of llama - L. Sari; X. Castro-González; R. Zampini; S. Apichela; M. Ratto; M. Argañaraz (Theriogenology, 2023)

Sewage sludge biochars as effective PFAS-sorbents - Katinka M. Krahn; Gerard Cornelissen; Gabriela Castro; Hans Peter H. Arp; Alexandros G. Asimakopoulos; Raoul Wolf; Rune Holmstad; Andrew R. Zimmerman; Erlend Sørmo (Journal of Hazardous Materials, 2023)

Role of Vertically Migrating and Not-Migrating Large Crustacean Zooplankton as Potential Consumers of Spring Phytoplankton in an Inshore Patagonian Gulf - Leonardo R. Castro; José Luis Iriarte; Samuel Soto; Humberto González (Estuaries and Coasts, 2023)

Beeswax multifunctional composites with thermal-healing capability and recyclability - Ricardo Brito-Pereira; Clarisse Ribeiro; Carmen R. Tubio; Nelson Castro; Pedro Costa; Senentxu Lanceros-Mendez (Chemical Engineering Journal, 2023)

Influence of pigeon pea (Cajanus cajan) on oviposition behaviour of Diceraeus melacanthus stink bug, an important pest of soybean and maize crops in South America - M. Borges; M. F. F. Michereff; R. A. Laumann; G. T. Santana; B. S. Castro; C. C. Silva; M. C. Blassioli-Moraes (Arthropod-Plant Interactions, 2023)

Metabolomics during the spontaneous fermentation in cocoa (Theobroma cacao L.): An exploraty review - César R. Balcázar-Zumaeta; Efraín M. Castro-Alayo; Ilse S. Cayo-Colca; Guillermo Idrogo-Vásquez; Lucas D. Muñoz-Astecker (Food Research International, 2023)

Modelling and evaluation of brittle shear effects on the seismic performance and loss assessment of RC buildings - R. Peres; R. Couto; I. Sousa; J.M. Castro; R. Bento (Engineering Structures, 2023)

Mothers of children with Down syndrome: a clinical and epidemiological study - Joissy Aprigio; Carolina M. L. de Castro; Marcelo A. Costa Lima; Márcia G. Ribeiro; Iêda M. Orioli; Márcia R. Amorim (Journal of Community Genetics, 2022)

Natural occurrence and controls of arsenic in groundwater in a semiarid basin in the Mexican Altiplano - Dario Cauich-Kau; Thomas R. Rüde; Antonio Cardona-Benavides; Javier Castro-Larragoitia (Hydrogeology Journal, 2022)
The sources, mobility, and controlling processes of arsenic (As) in an aquifer system in the Cerritos-Guadalcazar area of Central Mexico were investigated. High As concentrations (up to 128 μg/L) in groundwater were found to be associated with both primary sources (rocks and tailings) and secondary sources (soil and sediments). The high As concentrations in the otherwise pristine Cerritos shallow granular aquifer are the result of a distant source of As-rich sediments eroded from a mineralized area in the recharge zone of a karstic aquifer. An intermediate groundwater flow system delivers the As load from the karstic to the granular aquifer. In addition, identification of a Na–Cl water type in the shallow granular aquifer indicates a regional flow; however, additional information is needed to corroborate this assumption. Local flows in the karstic aquifer are Ca–HCO 3 water type with low (<1 μg/L) dissolved As concentrations. Principle axis factor analysis shows distinct groupings associated with different aquifer characteristics. The sulfate factor dominates in the southern area of the granular aquifer, which explains 30% of the total variance. The arsenic-uranium factor is expressed in samples from deep and dug wells tapping the basin sediments. A conceptual model was developed where the path of the As is shown. Three groups of samples showed negative correlation among deuterium excess and As concentrations. Evaporation modeling to simulate the As enrichment showed that evaporation processes play an important role in As behavior. This research can provide a tool for further studies in the Sierra Madre Oriental.

Genomic Characterization of Twelve Lytic Bacteriophages Infecting Midgut Bacteria of Aedes aegypti - Osvaldo López-Cuevas; Jean P. González-Gómez; José R. Aguirre-Sánchez; Bruno Gomez-Gil; Edith H. Torres-Montoya; José A. Medrano-Félix; Célida I. Martínez-Rodríguez; Nohelia Castro-del Campo; Cristóbal Chaidez (Current Microbiology, 2022)

Bradyrhizobium occurrence in nodules of perennial horsegram - Mayan Blanc Amaral; Tamiris dos Santos Lopes; Caroline Bueno Feder; Thiago Gonçalves Ribeiro; Rafael Sanches Pacheco; Thiago Neves Teixeira; Edevaldo de Castro Monteiro; Israel Oliveira Ramalho; Robert de O. Macedo; Robert M. Boddey; Jerri Edson Zilli; Bruno J. R. Alves (Brazilian Journal of Microbiology, 2022)

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Assessing bias in aerial surveys for cetaceans: Results from experiments conducted with the franciscana dolphin - Federico Sucunza; Daniel Danilewicz; Artur Andriolo; Franciele R. de Castro; Marta Cremer; Pablo Denuncio; Emanuel Ferreira; Paulo A. C. Flores; Paulo H. Ott; Martin S. Perez; Dan Pretto; Camila M. Sartori; et al. (Frontiers in Marine Science, 2022)
Line transect aerial surveys are widely used for estimating abundance of biological populations, including threatened species. However, estimates obtained with data collected from aircraft are often underestimated because of visibility bias and bias in estimating group sizes from a fast-moving platform. An assessment of multiple sources of bias in aerial surveys were carried out in Brazilian coastal waters by experiments on multiple survey platforms (i.e., boat, airplane and helicopter). These studies focused on evaluating visibility bias (perception and availability bias) and potential differences in the estimation of group sizes from different types of platforms used in franciscana ( Pontoporia blainvillei ) abundance surveys. The ultimate goal was to develop correction factors to improve accuracy of estimates of density and population size for this threatened dolphin. Estimates of density and group sizes computed from boats were assumed to be unbiased and were compared to estimates of these quantities obtained from an airplane in the same area and period. In addition, helicopter surveys were conducted in two areas where water turbidity differed (clear vs. murky waters) to determine surfacing-diving intervals of franciscana groups and to estimate availability for aerial platforms. Abundance computed from the aerial survey data underestimated the true abundance by about 4-5 times, with ~70% of the total bias resulting from visibility bias (~80% from availability bias and ~20% from perception bias) and ~30% from bias in estimates of group size. The use of multiple survey platforms in contrasting habitats provided the opportunity to compute correction factors that can be used to refine range wide abundance estimates of the threatened franciscana given certain assumptions are met. Visibility bias and group size bias were substantial and clearly indicate the importance for accounting for such correction factors to produce unequivocal population assessment based on aerial survey data.

Biosynthetic studies through feeding experiments in Eclipta prostrata (L.) L. hairy roots - Adriana A. Lopes; Giuliana R. S. Souza; Suzelei de Castro França; Miriam V. Lourenço (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Improving the spatiotemporal resolution of remotely sensed ET information for water management through Landsat, Sentinel-2, ECOSTRESS and VIIRS data fusion - Jie Xue; Martha C. Anderson; Feng Gao; Christopher Hain; Kyle R. Knipper; Yun Yang; William P. Kustas; Yang Yang; Nicolas Bambach; Andrew J. McElrone; Sebastian J. Castro; Joseph G. Alfieri; et al. (Irrigation Science, 2022)
Robust information on consumptive water use (evapotranspiration, ET) derived from remote sensing can significantly benefit water decision-making in agriculture, informing irrigation schedules and water management plans over extended regions. To be of optimal utility for operational usage, these remote sensing ET data should be generated at the sub-field spatial resolution and daily-to-weekly timesteps commensurate with the scales of water management activities. However, current methods for field-scale ET retrieval based on thermal infrared (TIR) imaging, a valuable diagnostic of canopy stress and surface moisture status, are limited by the temporal revisit of available medium-resolution (100 m or finer) thermal satellite sensors. This study investigates the efficacy of a data fusion method for combining information from multiple medium-resolution sensors toward generating high spatiotemporal resolution ET products for water management. TIR data from Landsat and ECOSTRESS (both at ~ 100-m native resolution), and VIIRS (375-m native) are sharpened to a common 30-m grid using surface reflectance data from the Harmonized Landsat-Sentinel dataset. Periodic 30-m ET retrievals from these combined thermal data sources are fused with daily retrievals from unsharpened VIIRS to generate daily, 30-m ET image timeseries. The accuracy of this mapping method is tested over several irrigated cropping systems in the Central Valley of California in comparison with flux tower observations, including measurements over irrigated vineyards collected in the GRAPEX campaign. Results demonstrate the operational value added by the augmented TIR sensor suite compared to Landsat alone, in terms of capturing daily ET variability and reduced latency for real-time applications. The method also provides means for incorporating new sources of imaging from future planned thermal missions, further improving our ability to map rapid changes in crop water use at field scales.

Older adults’ episodic memory is related to a neurophysiological marker of brain cholinergic activity - Patrick S. R. Davidson; Galit Karpov; Lauriane Giguère; Alex W. Castro; François Tremblay (Experimental Brain Research, 2022)

Water reuse in industries: analysis of opportunities in the Paraíba do Sul river basin, a case study in Presidente Vargas Plant, Brazil - Giulianna Costa Fico; Afonso R. G de Azevedo; Markssuel Teixeira Marvila; Daiane Cecchin; Gustavo de Castro Xavier; Bassam A. Tayeh (Environmental Science and Pollution Research, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Attitudes of Filipino parents of children with Down syndrome on noninvasive prenatal testing - Leniza G. de Castro-Hamoy; Ma-am Joy R. Tumulak; Maria Stephanie Fay S. Cagayan; Peter A. Sy; Nona Rachel C. Mira; Mercy Y. Laurino (Journal of Community Genetics, 2022)

Physicochemical and computational analysis of the melamine resin derivative for the glyphosate absorption from water using Langmuir-type model - L. Morales-Quintana; D. Bustos; J. Gallego; O. Valdes; L. Guzmán; F. M. Nachtigall; A. Marican; E. W. Hernández-Rodríguez; F. Avila-Salas; W. Bueno-Silva; L. S. Santos; R. I. Castro (International Journal of Environmental Science and Technology, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Setting Performance Indicators for Coastal Marine Protected Areas: An Expert-Based Methodology - Mariana Cardoso-Andrade; Henrique Queiroga; Mafalda Rangel; Inês Sousa; Adela Belackova; Luís Bentes; Frederico Oliveira; Pedro Monteiro; Nuno Sales Henriques; Carlos M. L. Afonso; Ana F. Silva; Bernardo R. Quintella; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) require effective indicators to assess their performance, in compliance with the goals of relevant national and international commitments. Achieving and prioritizing shortlists of multidisciplinary indicators demands a significant effort from specialists to depict the multiple conservation and socioeconomic interests, and the large complexity of natural systems. The present paper describes a structured expert-based methodology (process and outputs) to co-define a list of multidisciplinary MPA performance indicators. This work was promoted by the management authority of coastal MPAs in mainland Portugal to gather a consensual and feasible list of indicators that would guide the design of a future national monitoring program. Hence, Portuguese coastal MPAs served as a case study to develop such a process between 2019 and 2020. In the end, participants (1) agreed on a shortlist of prioritized indicators ( i.e. , environmental, governance, and socioeconomic indicators) and (2) defined minimum monitoring frequencies for the indicators in this list, compatible with the potential replicability of the associated survey methods. The present approach recommends that management plans incorporate monitoring procedures and survey methods, with a validated list of indicators and associated monitoring periodicity, agreed among researchers, MPA managers and governance experts. The proposed methodology, and the lessons learned from it, can support future processes aiming to define and prioritize MPA performance indicators.

The effect of repetition tempo on cardiovascular and metabolic stress when time under tension is matched during lower body exercise - Zachary A. Mang; Rogelio A. Realzola; Jeremy Ducharme; Gabriella F. Bellissimo; Jason R. Beam; Christine Mermier; Flavio de Castro Magalhaes; Len Kravitz; Fabiano T. Amorim (European Journal of Applied Physiology, 2022)

Genetic diversity of Chlamydia pecorum detected in sheep flocks from Mexico - M. M. Limón-González; R. Hernández-Castro; F. Martínez-Hernández; J. Xicohtencatl-Cortes; H. Ramírez-Alvarez; E. G. Palomares-Resendiz; E. Díaz-Aparicio (Brazilian Journal of Microbiology, 2022)

Polyethylene microplastics and substrate availability can affect emergence responses of the freshwater insect Chironomus sancticaroli - Gleyson B. Castro; Aline C. Bernegossi; Mayara C. Felipe; Allan P. Ogura; Mara R. de Lima e Silva; Juliano J. Corbi (Ecotoxicology, 2022)

Do CMIP models capture long-term observed annual precipitation trends? - S. M. Vicente-Serrano; R. García-Herrera; D. Peña-Angulo; M. Tomas-Burguera; F. Domínguez-Castro; I. Noguera; N. Calvo; C. Murphy; R. Nieto; L. Gimeno; J. M. Gutierrez; C. Azorin-Molina; et al. (Climate Dynamics, 2022)
This study provides a long-term (1891–2014) global assessment of precipitation trends using data from two station-based gridded datasets and climate model outputs evolved through the fifth and sixth phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively). Our analysis employs a variety of modeling groups that incorporate low- and high-top level members, with the aim of assessing the possible effects of including a well-resolved stratosphere on the model’s ability to reproduce long-term observed annual precipitation trends. Results demonstrate that only a few regions show statistically significant differences in precipitation trends between observations and models. Nevertheless, this pattern is mostly caused by the strong interannual variability of precipitation in most of the world regions. Thus, statistically significant model-observation differences on trends (1891–2014) are found at the zonal mean scale. The different model groups clearly fail to reproduce the spatial patterns of annual precipitation trends and the regions where stronger increases or decreases are recorded. This study also stresses that there are no significant differences between low- and high-top models in capturing observed precipitation trends, indicating that having a well-resolved stratosphere has a low impact on the accuracy of precipitation projections.

Effect of calving season on the parameters and components of the lactation curve in Holstein dairy cows managed in a semi-desert climate - Ricardo Zamorano-Algandar; Juan F. Medrano; Milton G. Thomas; R. Mark Enns; Scott E. Speidel; Miguel A. Sánchez-Castro; Guillermo Luna-Nevárez; José C. Leyva-Corona; Pablo Luna-Nevárez (Tropical Animal Health and Production, 2022)

RI75, a curcumin analogue, inhibits tumor necrosis factor-α and interleukin-6 production and exhibits antiallodynic and antiedematogenic activities in mice - Sarah O. A. M. Costa; Ianny B. Rodrigues; Alysson V. Braga; Bárbara C. M. Barbosa; Roger R. L. Silva; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela Í. Morais; Brenda F. M. Castro; Armando S. Cunha Júnior; Vinícius G. Maltarollo; Renata B. Oliveira; et al. (Inflammopharmacology, 2022)

Nanotechnology-Driven Cell-Based Therapies in Regenerative Medicine - D. Alzate-Correa; W. R. Lawrence; A. Salazar-Puerta; N. Higuita-Castro; D. Gallego-Perez (The AAPS Journal, 2022)

Assessing Caffeine and Linear Alkylbenzene Sulfonate Effects on Molting and Reproduction of Daphnia magna by Quantitative and Qualitative Approaches - Mara R. de Lima e Silva; Aline C. Bernegossi; Gleyson B. Castro; Allan P. Ogura; Juliano J. Corbi; Mayara C. Felipe (Water, Air, & Soil Pollution, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Megabenthic communities distributed in the outer margins of the Yucatan shelf and their relationship to environmental variables - J Rubio-Polania; D Torruco-Gómez; A González-Solís; R Rodríguez-Canul; M Améndola-Pimenta; I Mariño-Tapia; J Herrera-Silveira; F Árcega-Cabrera; V Ceja-Moreno; J Romo-Alvarado; I Lizarraga-Castro; C Gutiérrez-Solís (Marine Biology Research, 2022)

Small Differences in Diet Facilitate the Coexistence of Three Forage Fish Species in an Inshore Northern Patagonian Habitat - Lauren E. Wiesebron; Leonardo R. Castro; Samuel Soto; Jorge Castillo (Frontiers in Marine Science, 2022)
Forage fish play the crucial role of transferring energy from lower to upper trophic levels. These small pelagic fish feed on plankton and can compete with each other for food, leading to potentially complex interactions. Three forage fish species ( Sprattus fuegensis , Strangomera bentincki , and Engraulis ringens ) are commonly found in the inshore waters of Northern Chilean Patagonia, a region with large spatial variability in oceanographic conditions and in the zooplankton community. To better understand what factors may explain coexistence among these three forage fish species, we examined differences in resource availability (zooplankton community and abundances) in three locations (Chiloé, Cordillera, and Aysén regions) within Northern Patagonia. We compared the diet of the three fish species using both stable isotope and stomach content analyses, and we measured their gill rakers. S. fuegensis , the only species found in all three regions, had flexible diets which lent it greater success than the other two species at foraging in waters with fewer prey. We found little diet differentiation among the three species in the copepod-rich Cordillera region, but the diverging diets of S. bentincki and S. fuegensis in the copepod-poor Chiloé region suggest that diet partitioning in areas with fewer resources is due to competition. The small differences in diet facilitates coexistence among the three species, which may help explain the lack of correlation between the three species’ population abundances in the Cordillera region over the past 6 years. Finally, our results show that the high degree of oceanographic heterogeneity in Northern Patagonia may encourage species separation based on their specific environmental requirements.

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

A new species of Hoplias malabaricus species complex ( Characiformes: Erythrinidae ) from the Crepori River , Amazon basin, Brazil - Karen L. A. Guimarães; Juan J. Rosso; Mariano González‐Castro; Mendelsohn F. B. Souza; Juan M. Díaz de Astarloa; Luís R. R. Rodrigues (Journal of Fish Biology, 2022)
A new species belonging to the Hoplias malabaricus complex from the Amazon basin, Brazil, is described. The new species is characterized by 15–16 predorsal scales, 37–39 lateral‐line scales, 5 scales from dorsal fin to lateral line, 38–39 vertebrae, iii‐iv, 7–8 anal‐fin rays, ii‐iv, 12–15 caudal‐fin rays, last vertical series of scales on the base of caudal‐fin rays forming a straight line, 6–7 dark bands in anal fin and no distinctive dark bands or blotches on flanks. The new species is also distinguished from other congeners of the H. malabaricus species‐group by means of landmark‐based morphometrics and DNA Barcoding ( Cytochrome c Oxidase I gene ). An identification key to species of the H. malabaricus species complex is provided.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Opportunities Surrounding the Use of Sargassum Biomass as Precursor of Biogas, Bioethanol, and Biodiesel Production - Jorge Gabriel Orozco-González; Fernando Amador-Castro; Angela R. Gordillo-Sierra; Tomás García-Cayuela; Hal S. Alper; Danay Carrillo-Nieves (Frontiers in Marine Science, 2022)
Climate change (along with other factors) has caused an increase in the proliferation of brown algal mats floating freely along the Atlantic Ocean since 2011. These brown algae mats are composed of sea plants from the Sargassum genus. The gargantuan agglomeration of biomass flows alongside currents and lands in beaches belonging to the Eastern coasts of the Mexican Caribbean and several other countries in the region. These events, dubbed golden tides, harm the local economy and environment. Current elimination approaches involve the mechanical harvesting of the Sargassum and ultimate landfill disposal. However, explorations into the commercial application of other brown algae have elucidated the potential of Sargassum as a feedstock for valorization. This review informs the trends, challenges, and opportunities presented by the coastal invasion of this biomass. Primarily, the potential use of this material is as a precursor in biorefineries where multiple value-added products are generated concurrent with the ultimate production of biofuels.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Addition of proteinase K during the culture alter the physiology of Bacillus thuringiensis culture and the cry1Ac, nprX, nprA, and spo0A gene transcription - Miguel A. Peña-Rico; Humberto R. Bravo-D; Crisanto Roldan-Sabino; Karla V. Castro-Cerritos; Ariana Huerta-Heredia; A. Karin Navarro-Mtz (Antonie van Leeuwenhoek, 2022)

In vitro and in vivo evaluation of anti-inflammatory activity and free radical scavenging potential of leaves extract from Anadenanthera colubrina - Oswaldo Cardoso Junior; Nerilson M. Lima; Marcos G. A. Silva; Virgilio B. Aguiar; Gabriela P. Carli; Elaine C. Scherrer; Sandra B. R. Castro; Caio C. Souza Alves; Marcone A. L. Oliveira; Alessandra P. Carli (Natural Product Research, 2021)

A matter of suborder: are Zygoptera and Anisoptera larvae influenced by riparian vegetation in Neotropical Savanna streams? - Larissa F. R. Silva; Diego M. P. Castro; Leandro Juen; Marcos Callisto; Robert M. Hughes; Marcel G. Hermes (Hydrobiologia, 2021)

Sampling efforts for determining fish species richness in megadiverse tropical regions - Paulo S. Pompeu; Débora R. de Carvalho; Cecília G. Leal; Rafael P. Leitão; Carlos Bernardo M. Alves; Daniela F. Braga; Miriam A. Castro; Nara T. Junqueira; Robert M. Hughes (Environmental Biology of Fishes, 2021)

Upper crust attenuation in the Basin and Range Province of Sonora, Mexico - Raúl R. Castro; Gina P. Villalobos-Escobar (Journal of Seismology, 2021)

Activation of C–C motif chemokine receptor 2 modulates testicular macrophages number, steroidogenesis, and spermatogenesis progression - A. F. A. Figueiredo; N. T. Wnuk; C. P. Vieira; M. F. F. Gonçalves; M. R. G. Brener; A. B. Diniz; M. M. Antunes; H. M. Castro-Oliveira; G. B. Menezes; G. M. J. Costa (Cell and Tissue Research, 2021)

Multi-target drug with potential applications: violacein in the spotlight - Nelson Durán; Gerson Nakazato; Marcela Durán; Ignasio R. Berti; Guillermo R. Castro; Danijela Stanisic; Marcelo Brocchi; Wagner J. Fávaro; Carmen V. Ferreira-Halder; Giselle Z. Justo; Ljubica Tasic (World Journal of Microbiology and Biotechnology, 2021)

Correction to: Taxonomic, functional and phylogenetic bat diversity decrease from more to less complex natural habitats in the Amazon - William Douglas Carvalho; Karen Mustin; Fábio Z. Farneda; Isaí Jorge de Castro; Renato R. Hilário; Ana Carolina Moreira Martins; João D. Miguel; Bruna da Silva Xavier; José Júlio de Toledo (Oecologia, 2021)

Taxonomic, functional and phylogenetic bat diversity decrease from more to less complex natural habitats in the Amazon - William Douglas Carvalho; Karen Mustin; Fábio Z. Farneda; Isaí Jorge de Castro; Renato R. Hilário; Ana Carolina Moreira Martins; João D. Miguel; Bruna da Silva Xavier; José Júlio de Toledo (Oecologia, 2021)

Correction to: Metabarcoding meiofauna biodiversity assessment in four beaches of Northern Colombia: effects of sampling protocols and primer choice - Lyda R. Castro; Rachel S. Meyer; Beth Shapiro; Sabrina Shirazi; Samuel Cutler; Ana M. Lagos; Sigmer Y. Quiroga (Hydrobiologia, 2021)

Metabarcoding meiofauna biodiversity assessment in four beaches of Northern Colombia: effects of sampling protocols and primer choice - Lyda R. Castro; Rachel S. Meyer; Beth Shapiro; Sabrina Shirazi; Samuel Cutler; Ana M. Lagos; Sigmer Y. Quiroga (Hydrobiologia, 2021)

Counting Enchytraeus crypticus Juveniles in Chronic Exposures: An Alternative Method for Ecotoxicity Studies Using Tropical Artificial Soil - Mayara C. Felipe; Aline C. Bernegossi; Fernanda R. Pinheiro; Gleyson B. Castro; Lidia Moura; Marcelo Zaiat; Juliano J. Corbi (Bulletin of Environmental Contamination and Toxicology, 2021)

Anthropogenic impacts influence the functional traits of Chironomidae (Diptera) assemblages in a neotropical savanna river basin - Isabela Martins; Diego M. P. Castro; Diego R. Macedo; Robert M. Hughes; Marcos Callisto (Aquatic Ecology, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Detection of porcine circovirus type 2 (PCV2) in the Philippines and the complexity of PCV2-associated disease diagnosis - Agnes dela Cruz; Chiara Palmieri; Rachel Azul; Christina Legaspi; Suzan Lola; Tamsin S. Barnes; Christopher R. Parke; Conny Turni; John I. Alawneh; Augusto S. Baluyut; Voltaire G. Basinang; Jose E. David; et al. (Tropical Animal Health and Production, 2021)

Correction to: Importance of evaluating protein glycosylation in pluripotent stem cell‑derived cardiomyocytes for research and clinical applications - Maia I. Kelly; Mustafa Albahrani; Chase Castro; Ellen Poon; Bin Yan; Jack Littrell; Matthew Waas; Kenneth R. Boheler; Rebekah L. Gundry (Pflügers Archiv - European Journal of Physiology, 2021)

Importance of evaluating protein glycosylation in pluripotent stem cell-derived cardiomyocytes for research and clinical applications - Maia I. Kelly; Mustafa Albahrani; Chase Castro; Ellen Poon; Bin Yan; Jack Littrell; Matthew Waas; Kenneth R. Boheler; Rebekah L. Gundry (Pflügers Archiv - European Journal of Physiology, 2021)
Proper protein glycosylation is critical to normal cardiomyocyte physiology. Aberrant glycosylation can alter protein localization, structure, drug interactions, and cellular function. The in vitro differentiation of human pluripotent stem cells into cardiomyocytes (hPSC-CM) has become increasingly important to the study of protein function and to the fields of cardiac disease modeling, drug testing, drug discovery, and regenerative medicine. Here, we offer our perspective on the importance of protein glycosylation in hPSC-CM. Protein glycosylation is dynamic in hPSC-CM, but the timing and extent of glycosylation are still poorly defined. We provide new data highlighting how observed changes in hPSC-CM glycosylation may be caused by underlying differences in the protein or transcript abundance of enzymes involved in building and trimming the glycan structures or glycoprotein gene products. We also provide evidence that alternative splicing results in altered sites of glycosylation within the protein sequence. Our findings suggest the need to precisely define protein glycosylation events that may have a critical impact on the function and maturation state of hPSC-CM. Finally, we provide an overview of analytical strategies available for studying protein glycosylation and identify opportunities for the development of new bioinformatic approaches to integrate diverse protein glycosylation data types. We predict that these tools will promote the accurate assessment of protein glycosylation in future studies of hPSC-CM that will ultimately be of significant experimental and clinical benefit.

Prey items of baleen whale species off the coast of Chile from fecal plume analysis - Susannah J. Buchan; Paulina Vásquez; Carlos Olavarría; Leonardo R. Castro (Marine Mammal Science, 2021)

Separate Feeding Between the Pelagic Stage of the Squat Lobster Munida gregaria and the Larger Sized Zooplankton Crustacean Groups in the Beagle Channel as Revealed by Stable Isotopes - Leonardo R. Castro; Humberto E. González; José Garcés-Vargas; Pamela Barrientos (Frontiers in Marine Science, 2021)
In southern Patagonia, the Beagle Channel shows very low production during winter but simultaneously sustains very dense aggregations of the pelagic stage of squat lobster ( Munida gregaria ), a benthic decapod whose pelagic juveniles have the largest body size within the chitinous pelagic community. To assess the coexistence of the mesozooplankton community and the pelagic M. gregaria stage under the harsh feeding winter conditions, we conducted a research cruise at two locations connected to the Beagle Channel, Yendegaia Bay (land terminating-glacier) and Pia Fjord (marine-terminating glacier). Our results showed that the zooplankton communities were similar in these two fjords, that a single pelagic group dominated in terms of biomass (pelagic Munida gregaria ), and that differences in vertical distribution existed between most of the principal crustacean zooplankton and pelagic M. gregaria . All groups showed consumption of terrestrially derived organic matter, as revealed by their δ 13 C values. However, the isotopic composition, trophic positions (TP), and isotopic niche areas of the groups separated pelagic M. gregaria , presenting some of the lowest δ 15 N and the highest δ 13 C values, and the narrowest isotopic niche width. Pelagic M. gregaria was dominated by a single body size class along the 0–100 m water column, with no diel changes in vertical distribution, remained mostly in the upper layers (0–50 m), and benefited from the slightly higher phytoplankton concentrations at shallower depths as revealed by their higher δ 13 C values and low trophic position. In contrast, the other groups, including zoea M. gregaria stages, developed changes in distribution between day and night or remained deeper in the water column. These groups showed higher δ 15 N values, higher TP, and lower δ 13 C values, most of which probably fed on a nanoheterotrophs and terrestrial particulate organic matter mixture at deeper layers. Thus, the different vertical distributions, different trophic level food sources, and slightly different organic carbon sources apparently reduced any potential competence for food resources and form part of the feeding strategy that may facilitate the coexistence of the different large pelagic crustaceans under harsh feeding winter conditions in this high latitude austral region.

Depth-Dependent Shear-Wave Attenuation in Central Apennines, Italy - Raúl R. Castro; Francesca Pacor; Daniele Spallarossa (Pure and Applied Geophysics, 2021)

A novel method for the in vitro assembly of virus-like particles and multimeric proteins - Mabel Rodríguez; Ricardo M. Castro-Acosta; Elias R. Ruiz-Morales; Francisca Villanueva-Flores; Octavio T. Ramírez; Laura A. Palomares (Biotechnology Letters, 2021)

Biotechnological Potential of Eugenol and Thymol Derivatives Against Staphylococcus aureus from Bovine Mastitis - Daiana O. S. Nunes; Rafaelle Vinturelle; Francislene J. Martins; Thiago F. dos Santos; Alessandra Leda Valverde; Carlos Magno R. Ribeiro; Helena C. Castro; Evelize Folly (Current Microbiology, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Miconia albicans and Curcuma longa herbal medicines positively modulate joint pain, function and inflammation in patients with osteoarthritis: a clinical study - Thiago P. O. Gomes; Jonathan I. N. Souza; Lucas C. Somerlate; Vanessa A. Mendonça; Nerilson M. Lima; Gabriela P. Carli; Sandra B. R. Castro; Teresinha de Jesus A. S. Andrade; João V. L. Dias; Marcone A. L. Oliveira; Caio C. S. Alves; Alessandra P. Carli (Inflammopharmacology, 2021)

Pathological characteristics, survival, and risk of breast cancer associated with estrogen and xenobiotic metabolism polymorphisms in Mexican women with breast cancer - O. C. Martínez-Ramírez; C. Castro-Hernández; R. Pérez-Morales; L. Casas-Ávila; Ramos-García M. de Lorena; A. Salazar-Piña; J. Rubio (Cancer Causes & Control, 2021)

Physical and Biogeochemical Regionalization of the Southern Ocean and the CCAMLR Zone 48.1 - Giovanni Testa; Andrea Piñones; Leonardo R. Castro (Frontiers in Marine Science, 2021)
The Southern Ocean plays a major role in the Earth’s climate, provides fisheries products and help the maintenance of biodiversity. The degree of correspondence between physical and biogeochemical spatial variability and regionalization were investigated by calculating the main physical factors that statistically explained the biogeochemical variability within the Southern Ocean and the 48.1 zone of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). The mean value of physical and biogeochemical variables was estimated during austral summer within a grid of 1° × 1° south of 50°S. The regionalization was developed using both non-hierarchical and hierarchical clustering method, whereas BIO-ENV package and distance-based redundancy analysis (db-RDA) were applied in order to calculate which physical factors primarily explained the biogeochemical spatial variability. A total of 12 physical and 18 biogeochemical significant clusters were identified for the Southern Ocean (alpha: 0.05). The combination of bathymetry and sea ice coverage majorly explained biogeochemical variability (Spearman rank correlation coefficient: 0.68) and db-RDA indicated that physical variables expressed the 60.1% of biogeochemical variance. On the other hand, 14 physical and 16 biogeochemical significant clusters were identified for 48.1 CCAMLR zone. Bathymetry was the main factor explaining biogeochemical variability (Spearman coefficient: 0.81) and db-RDA analysis resulted in 77.1% of biogeochemical variance. The correspondence between physical and biogeochemical regions was higher for CCAMLR 48.1 zone with respect to the whole Southern Ocean. Our results provide useful information for both Southern Ocean and CCAMLR 48.1 zone ecosystem management and modeling parametrization.

Estimation of genetic parameters for four Peruvian guinea pig lines - J. I. Cedano-Castro; R. Jiménez; A. Huamán; B. Fuerst-Waltl; M. Wurzinger; G. Gutiérrez (Tropical Animal Health and Production, 2021)

Assessing Markovian Models for Seismic Hazard and Forecasting - Q. J. Gutierrez Peña; F. A. Nava Pichardo; E. Glowacka; R. R. Castro Escamilla; V. H. Márquez Ramírez (Pure and Applied Geophysics, 2021)

Application of rhamnolipid surfactant for remediation of toxic metals of long- and short-term contamination sites - C. S. C. Lopes; D. B. Teixeira; B. F. Braz; R. E. Santelli; L. V. A. de Castilho; J. G. C. Gomez; R. P. V. Castro; L. Seldin; D. M. G. Freire (International Journal of Environmental Science and Technology, 2021)

Nebivolol Prevents Up-Regulation of Nox2/NADPH Oxidase and Lipoperoxidation in the Early Stages of Ethanol-Induced Cardiac Toxicity - Gabriel T. do Vale; Carla B. P. da Silva; Arthur H. Sousa; Natália A. Gonzaga; Juliana M. Parente; Katiúscia M. Araújo; Michele M. Castro; Carlos R. Tirapelli (Cardiovascular Toxicology, 2021)

Bacterial Nanocellulose Mulch as a Potential Greener Alternative for Urban Gardening in the Small-Scale Food Production of Onion Plants - L. Cárcamo; S. Sierra; M. Osorio; J. Velásquez-Cock; L. Vélez-Acosta; C. Gómez-Hoyos; C. Castro; R. Zuluaga; P. Gañán (Agricultural Research, 2021)

Dietary inflammatory potential, cardiometabolic risk and inflammation in children and adolescents: a systematic review - Lara Gomes Suhett; Helen Hermana Miranda Hermsdorff; Bruna Clemente Cota; Sarah Aparecida Vieira Ribeiro; Nitin Shivappa; James R. Hébert; Sylvia do Carmo Castro Franceschini; Juliana Farias de Novaes (Critical Reviews in Food Science and Nutrition, 2021)

A research perspective towards a more complete biodiversity footprint: a report from the World Biodiversity Forum - Alexandra Marques; Marine Robuchon; Stefanie Hellweg; Tim Newbold; Jutta Beher; Sebastian Bekker; Franz Essl; Daniele Ehrlich; Samantha Hill; Martin Jung; Sandra Marquardt; Francesca Rosa; et al. (The International Journal of Life Cycle Assessment, 2021)

Effects of Environmental Variables and Habitat Integrity on the Structure of the Aquatic Insect Communities of Streams in the Cerrado-Caatinga Ecotone in Northeastern Brazil - E. R. Castro; D. S. Veras; G. S. Lustosa; C. A. S. Azevêdo; L. Juen (Neotropical Entomology, 2021)

Seismic energy radiated by earthquakes in the Basin and Range Province of Sonora, Mexico, near the rupture of the 1887 Mw 7.5 earthquake - Raúl R. Castro; Gina P. Villalobos-Escobar (Journal of Seismology, 2021)

d-Lactate and intestinal fatty acid-binding protein are elevated in serum in patients with acute ischemic stroke - Carlos R. Camara-Lemarroy; Nicolás Escobedo-Zúñiga; Francisco J. Guzmán-de la Garza; Jorge Castro-Garza; Javier Vargas-Villarreal; Fernando Góngora-Rivera (Acta Neurologica Belgica, 2021)

Hepatitis C treatment outcome in former or current intravenous drug users coinfected with HIV, with or without directly observed therapy - R. Sarmento-Castro; J. Méndez; A. Horta; C. Gonçalves; O. Vasconcelos; J. Seabra; M. Abreu; M. J. Gonçalves; M. J. Santos; A. P. Tavares (Infectious Diseases, 2021)

COVID-19: the impact of a global crisis on sustainable development research - Walter Leal Filho; Anabela Marisa Azul; Tony Wall; Claudio R. P. Vasconcelos; Amanda Lange Salvia; Arminda do Paço; Kalterina Shulla; Vanessa Levesque; Federica Doni; Lorena Alvarez-Castañón; Claudia Mac-lean; Lucas Veiga Avila; et al. (Sustainability Science, 2021)

Mosaic genome evolution and phylogenetics of Chrysodeixis includens nucleopolyhedrovirus (ChinNPV) and virulence of seven new isolates from the Brazilian states of Minas Gerais and Mato Grosso - Peter W. Inglis; Luis Arthur V. M. Santos; Saluana R. Craveiro; Bergmann M. Ribeiro; Maria Elita B. Castro (Archives of Virology, 2021)

Cubic-to-inverted micellar and the cubic-to-hexagonal-to-micellar transitions on phytantriol-based cubosomes induced by solvents - Mayra C. G. Lotierzo; Bruna R. Casadei; Raphael Dias de Castro; Barbara Malheiros; Leandro R. S. Barbosa (Drug Delivery and Translational Research, 2020)

Seismic stratigraphy of a deep water basin in the Brazilian equatorial margin: the eastern portion of Potiguar Basin and Touros High - Júlia C. L. G. Fonseca; Helenice Vital; Yoe A. R. Perez; David L. Castro; André G. Aquino da Silva; Moab P. Gomes (Geo-Marine Letters, 2020)

In Situ Transesterification of Marine Microalgae Biomass via Heterogeneous Acid Catalysis - Savienne M. F. E. Zorn; Cristiano E. R. Reis; Heitor B. S. Bento; Ana Karine F. de Carvalho; Messias B. Silva; Heizir F. De Castro (BioEnergy Research, 2020)

Effects of leaf litter extracts from four tree species on aquatic invertebrates: an ecotoxicological risk assessment approach - A. Alonso; B. R. Vázquez de Aldana; P. Castro-Díez; S. Medina-Villar; M. E. Pérez-Corona (Aquatic Ecology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Losing Genes: The Evolutionary Remodeling of Cetacea Skin - Gonçalo Espregueira Themudo; Luís Q. Alves; André M. Machado; Mónica Lopes-Marques; Rute R. da Fonseca; Miguel Fonseca; Raquel Ruivo; L. Filipe C. Castro (Frontiers in Marine Science, 2020)

Constraining Euler Deconvolution Solutions Through Combined Tilt Derivative Filters - Fabrício R. Castro; Saulo P. Oliveira; Jeferson de Souza; Francisco J. F. Ferreira (Pure and Applied Geophysics, 2020)

Update on the use of Pristina longiseta Ehrenberg, 1828 (Oligochaeta: Naididae) as a toxicity test organism - Gleyson B. Castro; Fernanda R. Pinheiro; Mayara C. Felipe; Aline C. Bernegossi; Douglas Girolli; Guilherme R. Gorni; Juliano J. Corbi (Environmental Science and Pollution Research, 2020)

Effects of Polyethylene Microplastics on Freshwater Oligochaeta Allonais inaequalis (Stephenson, 1911) Under Conventional and Stressful Exposures - Gleyson B. Castro; Aline C. Bernegossi; Fernanda R. Pinheiro; Mayara C. Felipe; Juliano J. Corbi (Water, Air, & Soil Pollution, 2020)

Delinted cottonseed in diets for finishing sheep - W. J. R. Castro; A. M. Zanine; D. J. Ferreira; A. L. Souza; R. M. A. Pinho; M. O. M. Parente; H. N. Parente; E. M. Santos (Tropical Animal Health and Production, 2020)

Molecular detection of pathogens in ticks associated with domestic animals from the Colombian Caribbean region - Andrea P. Cotes-Perdomo; Ángel Oviedo; Lyda R. Castro (Experimental and Applied Acarology, 2020)

Infection and colonization by Corynebacterium pseudodiphtheriticum: a 9-year observational study in a university central hospital - Sofia R. Valdoleiros; Catarina Sousa Neves; João Abranches Carvalho; Celina Gonçalves; Paulo Pereira; Olga Vasconcelos; Ana Paula Castro; Maria Helena Ramos (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Retrospective study of porcine circovirus 3 (PCV3) in swine tissue from Brazil (1967–2018) - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; R. L. Silveira; T. X. Castro (Brazilian Journal of Microbiology, 2020)

Production of Value-Added Microbial Metabolites: Oleaginous Fungus as a Tool for Valorization of Dairy By-products - Carolina A. Braz; Ana K. F. Carvalho; Heitor B. S. Bento; Cristiano E. R. Reis; Heizir F. De Castro (BioEnergy Research, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Aerobic processes for bioleaching manganese and silver using microorganisms indigenous to mine tailings - B. Huerta-Rosas; I. Cano-Rodríguez; Z. Gamiño-Arroyo; F. I. Gómez-Castro; F. R. Carrillo-Pedroza; P. Romo-Rodríguez; J. F. Gutiérrez-Corona (World Journal of Microbiology and Biotechnology, 2020)

Ichthyoplankton distribution and feeding habits of fish larvae at the inshore zone of northern Patagonia, Chile - Ainhoa Bernal; Leonardo R. Castro; Samuel Soto; Luis A. Cubillos (Marine Biodiversity, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Characterization of the complete mitochondrial genome of Amblyomma ovale, comparative analyses and phylogenetic considerations - Juan E. Uribe; Santiago Nava; Katherine R. Murphy; Evelina L. Tarragona; Lyda R. Castro (Experimental and Applied Acarology, 2020)

The use of an Allonais inaequalis reproduction test as an ecotoxicological bioassay - M. C. Felipe; A. C. Bernegossi; G. B. Castro; F. R. Pinheiro; B. L. Nadai; B. N. Cardoso-Silva; J. J. Corbi (Ecotoxicology, 2020)

Effects of combined 5-HT2A and cannabinoid receptor modulation on a schizophrenia-related prepulse inhibition deficit in mice - Adriana M. Marques; Michele V. Macena; Aline R. Cardoso; Camila S. O. Hammes; Fernanda M. L. Pinheiro; Newton G. Castro; Gilda A. Neves (Psychopharmacology, 2020)

Nitrogen flux into metabolites and microcystins changes in response to different nitrogen sources in Microcystis aeruginosa NIES ‐843 - Lauren E. Krausfeldt; Abigail T. Farmer; Hector F. Castro; Gregory L. Boyer; Shawn R. Campagna; Steven W. Wilhelm (Environmental Microbiology, 2020)
Summary The over‐enrichment of nitrogen (N) in the environment has contributed to severe and recurring harmful cyanobacterial blooms, especially by the non‐N 2 ‐fixing Microcystis spp. N chemical speciation influences cyanobacterial growth, persistence and the production of the hepatotoxin microcystin, but the physiological mechanisms to explain these observations remain unresolved. Stable‐labelled isotopes and metabolomics were employed to address the influence of nitrate, ammonium, and urea on cellular physiology and production of microcystins in Microcystis aeruginosa NIES‐843. Global metabolic changes were driven by both N speciation and diel cycling. Tracing 15 N‐labelled nitrate, ammonium, and urea through the metabolome revealed N uptake, regardless of species, was linked to C assimilation. The production of amino acids, like arginine, and other N‐rich compounds corresponded with greater turnover of microcystins in cells grown on urea compared to nitrate and ammonium. However, 15 N was incorporated into microcystins from all N sources. The differences in N flux were attributed to the energetic efficiency of growth on each N source. While N in general plays an important role in sustaining biomass, these data show that N‐speciation induces physiological changes that culminate in differences in global metabolism, cellular microcystin quotas and congener composition.

Biosorption of Rhodamine B Using a Low-Cost Biosorbent Prepared from Inactivated Aspergillus oryzae Cells: Kinetic, Equilibrium and Thermodynamic Studies - Flávia H. M. Souza; Vitória F. C. Leme; Giovanna O. B. Costa; Karine C. Castro; Tania R. Giraldi; Grazielle S. S. Andrade (Water, Air, & Soil Pollution, 2020)

Epigallocatechin-3-Gallate (EGCG) Improves Cognitive Deficits Aggravated by an Obesogenic Diet Through Modulation of Unfolded Protein Response in APPswe/PS1dE9 Mice - Miren Ettcheto; Amanda Cano; Patricia R. Manzine; Oriol Busquets; Ester Verdaguer; Rubén Dario Castro-Torres; Maria Luisa García; Carlos Beas-Zarate; Jordi Olloquequi; Carme Auladell; Jaume Folch; Antoni Camins (Molecular Neurobiology, 2020)

Sun Protection Habits and Sunburn in Elite Aquatics Athletes: Surfers, Windsurfers and Olympic Sailors - Guillermo De Castro-Maqueda; J. V. Gutierrez-Manzanedo; J. G. Ponce-González; J. R. Fernandez-Santos; M. Linares-Barrios; M. De Troya-Martín (Journal of Cancer Education, 2020)

Global characterization of hydrological and meteorological droughts under future climate change: The importance of timescales, vegetation‐CO 2 feedbacks and changes to distribution functions - Sergio M. Vicente‐Serrano; Fernando Domínguez‐Castro; Tim R. McVicar; Miquel Tomas‐Burguera; Marina Peña‐Gallardo; Iván Noguera; Juan I. López‐Moreno; Dhais Peña; Ahmed El Kenawy (International Journal of Climatology, 2020)
There is a strong scientific debate on how drought will evolve under future climate change. Climate model outputs project an increase in drought frequency and severity by the end of the 21st century. However, there is a large uncertainty related to the extent of the global land area that will be impacted by enhanced climatological and hydrological droughts. Although climate metrics suggest a likely strong increase in future drought severity, hydrologic metrics do not show a similar signal. In the literature, numerous attempts have been made to explain these differences using several physical mechanisms. This study provides evidence that characterization of drought from different statistical perspectives can lead to unreliable detection of climatological/hydrological droughts in model projections and accordingly give a “false alarm” of the impacts of future climate change. In particular, this study analyses future projections based on different drought metrics and stresses that detecting trends in drought behavior in future projections must consider the extreme character of drought events by comparing the percentage change in drought magnitude relative to a reference climatological period and rely on the frequency of events in the tail of the distribution. In addition, the autoregressive character of drought indices makes necessary the use of the same temporal scale when comparing different drought metrics in order to maintain comparability. Taking into consideration all these factors, our study demonstrates that climatological and hydrological drought trends are likely to undergo similar temporal evolution during the 21st century, with almost 30% of the global land areas experiencing water deficit under future greenhouse gas emissions scenarios. As such, a proper characterization of drought using comparable metrics can introduce lower differences and more consistent outputs for future climatic and hydrologic droughts.

A comparison of machine and deep-learning algorithms applied to multisource data for a subtropical forest area classification - C. Sothe; C. M. De Almeida; M. B. Schimalski; V. Liesenberg; L. E. C. La Rosa; J. D. B. Castro; R. Q. Feitosa (International Journal of Remote Sensing, 2020)

Electrocutions in free-living black-tufted marmosets (Callithrix penicillata) in anthropogenic environments in the Federal District and surrounding areas, Brazil - Alexandra A. B. G. Pereira; Bianca Dias; Sarah I. Castro; Marina F. A. Landi; Cristiano B. Melo; Tais M. Wilson; Gabriela R. T. Costa; Pedro H. O. Passos; Alessandro P. Romano; Matias P. J. Szabó; Márcio B. Castro (Primates, 2020)

Populations of Populus angustifolia have evolved distinct metabolic profiles that influence their surrounding soil - Liam O. Mueller; Samuel R. Borstein; Eric D. Tague; Stephen P. Dearth; Hector F. Castro; Shawn R. Campagna; Joseph K. Bailey; Jennifer A. Schweitzer (Plant and Soil, 2020)

Chemical and mineral comparison of fossil insect cuticles from Crato Konservat Lagerstätte, Lower Cretaceous of Brazil - Francisco Irineudo Bezerra; João H. da Silva; Emílio de Castro Miguel; Alexandre R. Paschoal; Daniel R. Nascimento; Paulo T. C. Freire; Bartolomeu C. Viana; Márcio Mendes (Journal of Iberian Geology, 2020)

Promotion of the Geological Heritage of Araripe Unesco Global Geopark, Brazil: the Casa da Pedra Reference Center - I. S. Carvalho; M. H. Henriques; A. R. S. F. Castro; Y. R. Félix (Geoheritage, 2020)

Acidithiobacillus ferrianus sp. nov.: an ancestral extremely acidophilic and facultatively anaerobic chemolithoautotroph - Paul R. Norris; Carmen Falagán; Ana Moya-Beltrán; Matías Castro; Raquel Quatrini; D. Barrie Johnson (Extremophiles, 2020)
Strain MG, isolated from an acidic pond sediment on the island of Milos (Greece), is proposed as a novel species of ferrous iron- and sulfur-oxidizing Acidithiobacillus . Currently, four of the eight validated species of this genus oxidize ferrous iron, and strain MG shares many key characteristics with these four, including the capacities for catalyzing the oxidative dissolution of pyrite and for anaerobic growth via ferric iron respiration. Strain MG also grows aerobically on hydrogen and anaerobically on hydrogen coupled to ferric iron reduction. While the 16S rRNA genes of the iron-oxidizing Acidi-thiobacillus species (and strain MG) are located in a distinct phylogenetic clade and are closely related (98–99% 16S rRNA gene identity), genomic relatedness indexes (ANI/dDDH) revealed strong genomic divergence between strain MG and all sequenced type strains of the taxon, and placed MG as the first cultured representative of an ancestral phylotype of iron oxidizing acidithiobacilli. Strain MG is proposed as a novel species, Acidithiobacillus ferrianus sp. nov. The type strain is MG T (= DSM 107098 T = JCM 33084 T ). Similar strains have been found as isolates or indicated by cloned 16S rRNA genes from several mineral sulfide mine sites.

Assessment of yield gaps on global grazed‐only permanent pasture using climate binning - Leonardo A. Monteiro; Andrew M. Allee; Eleanor E. Campbell; Lee R. Lynd; Johnny R. Soares; Deepak Jaiswal; Julianne de Castro Oliveira; Murilo dos Santos Vianna; Ashley E. Morishige; Gleyce K. D. A. Figueiredo; Rubens A. C. Lamparelli; Nathaniel D. Mueller; et al. (Global Change Biology, 2020)
To meet rising demands for agricultural products, existing agricultural lands must either produce more or expand in area. Yield gaps (YGs)—the difference between current and potential yield of agricultural systems—indicate the ability to increase output while holding land area constant. Here, we assess YGs in global grazed‐only permanent pasture lands using a climate binning approach. We create a snapshot of circa 2000 empirical yields for meat and milk production from cattle, sheep, and goats by sorting pastures into climate bins defined by total annual precipitation and growing degree‐days. We then estimate YGs from intra‐bin yield comparisons. We evaluate YG patterns across three FAO definitions of grazed livestock agroecosystems (arid, humid, and temperate), and groups of animal production systems that vary in animal types and animal products. For all subcategories of grazed‐only permanent pasture assessed, we find potential to increase productivity several‐fold over current levels. However, because productivity of grazed pasture systems is generally low, even large relative increases in yield translated to small absolute gains in global protein production. In our dataset, milk‐focused production systems were found to be seven times as productive as meat‐focused production systems regardless of animal type, while cattle were four times as productive as sheep and goats regardless of animal output type. Sustainable intensification of pasture is most promising for local development, where large relative increases in production can substantially increase incomes or “spare” large amounts of land for other uses. Our results motivate the need for further studies to target agroecological and economic limitations on productivity to improve YG estimates and identify sustainable pathways toward intensification.

Mangifera indica L. as Airborne Metal Biomonitor for Regions of the State of Espírito Santo (Brazil) - Leonardo Z. de Castro; Thaís R. B. da Silva; Silas N. Ronchi; Adriana A. T. Guimarães; Hermínio A. Nalini Júnior; Juliano S. Ribeiro; Silvia C. G. Coutinho; Elisangela F. Pimentel; Denise C. Endringer (Water, Air, & Soil Pollution, 2020)

Removal of Zn and Cd from Overlying Water by Mangrove Sediments: Testing the Effects of Sediment Resuspension/Redeposition Events - K. N. Suzuki; R. J. M. Castro; M. N. Sondermann; E. C. Machado; A. B. Bellido; R. T. Lopes; W. Machado (Water, Air, & Soil Pollution, 2020)

An operational forecasting system for physical processes in the Santos-Sao Vicente-Bertioga Estuarine System, Southeast Brazil - Carine G. R. Costa; José Roberto B. Leite; Belmiro M. Castro; Alan F. Blumberg; Nickitas Georgas; Marcelo Dottori; Antoni Jordi (Ocean Dynamics, 2020)

Biogeography, habitat transitions and hybridization in a radiation of South American silverside fishes revealed by mitochondrial and genomic RAD data - Lily C. Hughes; Yamila P. Cardoso; Julie A. Sommer; Roberto Cifuentes; Mariela Cuello; Gustavo M. Somoza; Mariano González‐Castro; Luiz R. Malabarba; Victor Cussac; Evelyn M. Habit; Ricardo Betancur‐R.; Guillermo Ortí (Molecular Ecology, 2020)
Rivers and lake systems in the southern cone of South America have been widely influenced by historical glaciations, carrying important implications for the evolution of aquatic organisms, including prompting transitions between marine and freshwater habitats and by triggering hybridization among incipient species via waterway connectivity and stream capture events. Silverside fishes ( Odontesthes ) in the region comprise a radiation of 19 marine and freshwater species that have been hypothesized on the basis of morphological or mitochondrial DNA data to have either transitioned repeatedly into continental waters from the sea or colonized marine habitats following freshwater diversification. New double digest restriction‐site associated DNA data presented here provide a robust framework to investigate the biogeographical history of and habitat transitions in Odontesthes . We show that Odontesthes silversides originally diversified in the Pacific but independently colonized the Atlantic three times, producing three independent marine‐to‐freshwater transitions. Our results also indicate recent introgression of marine mitochondrial haplotypes into two freshwater clades, with more recurring instances of hybridization among Atlantic‐ versus Pacific‐slope species. In Pacific freshwater drainages, hybridization with a marine species appears to be geographically isolated and may be related to glaciation events. Substantial structural differences of estuarine gradients between these two geographical areas may have influenced the frequency, intensity and evolutionary effects of hybridization events.

Root proteome and metabolome reveal a high nutritional dependency of aluminium in Qualea grandiflora Mart. (Vochysiaceae) - Natalia F. Cury; Renata C. C. Silva; Michelle S. F. Andre; Wagner Fontes; Carlos A. O. Ricart; Mariana S. Castro; Conceição E. S. Silveira; Thomas C. R. Williams; Marcelo V. de Sousa; Luiz A. R. Pereira (Plant and Soil, 2020)

Role of inflammation, oxidative stress, and autonomic nervous system activation during the development of right and left cardiac remodeling in experimental pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; A. C. Bahr; P. Türck; A. L. de Castro; C. Campos-Carraro; F. Visioli; T. R. Fernandes-Piedras; K. R. Casali; C. M. C. Scassola; G. Baldo; et al. (Molecular and Cellular Biochemistry, 2020)

Evidence of a landlocked reproducing population of the marine pejerrey Odontesthes argentinensis (Actinopterygii; Atherinopsidae) - Darío C. Colautti; Leandro Miranda; Mariano Gonzalez‐Castro; Vanina Villanova; Carlos A. Strüssmann; Miguel Mancini; Tomas Maiztegui; Gustavo Berasain; Ricardo Hattori; Fabian Grosman; Pablo Sanzano; Ismael Lozano; et al. (Journal of Fish Biology, 2020)
In South America, the order Atheriniformes includes the monophyletic genus Odontesthes with 20 species that inhabit freshwater, estuarine and coastal environments. Pejerrey Odontesthes argentinensis is widely distributed in coastal and estuarine areas of the Atlantic Ocean and is known to foray into estuaries of river systems, particularly in conditions of elevated salinity. However, to our knowledge, a landlocked self‐sustaining population has never been recorded. In this study, we examined the pejerrey population of Salada de Pedro Luro Lake (south‐east of Buenos Aires Province, Argentina) to clarify its taxonomic identity. An integrative taxonomic analysis based on traditional meristic, landmark‐based morphometrics and genetic techniques suggests that the Salada de Pedro Luro pejerrey population represents a novel case of physiological and morphological adaptation of a marine pejerrey species to a landlocked environment and emphasises the environmental plasticity of this group of fishes.

Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Carlos A. C. Crusciol; Rubia R. Marques; Antonio C. A. Carmeis Filho; Rogério P. Soratto; Claudio H. M. Costa; Jayme Ferrari Neto; Gustavo S. A. Castro; Cristiano M. Pariz; André M. Castilhos; Alan J. Franzluebbers (Nutrient Cycling in Agroecosystems, 2019)

Spatio‐temporal analysis for extreme temperature indices over the Levant region - Ala A. M. Salameh; Sonia R. Gámiz‐Fortis; Yolanda Castro‐Díez; Ahmad Abu Hammad; María Jesús Esteban‐Parra (International Journal of Climatology, 2019)
The temporal and spatial trends of 16 climate extreme indices based on daily maximum and minimum temperatures during the period 1987–2016 at 28 stations distributed across Israel and Palestine territories in the Levant region were annually and seasonally analysed. The nonparametric Man‐Kendall test and the Sen's slope estimator were employed for the trend analysis. Results showed that the region has significantly experienced a dominant warming trend for the last three decades, with more intense changes for minimum temperatures than for maximum. At annual scale, maximum values of minimum temperatures exhibited significant increasing trends up to 0.68°C/decade. For percentile‐based extreme temperature indices, changes detected were more pronounced than those for the absolute extreme temperature indices, with 93 and 89% of stations significantly showed increasing trends in TX90p and TN90p, respectively. The duration and fixed threshold extreme indices confirmed the trend toward a warming, with the 86% of the stations exhibited significant increasing trends in the annual occurrence of summer days (SU25) and tropical nights (TR20). Moreover, 57% of stations showed significant increasing trends in their very summer days (SU30) index. At seasonal scale, the analysis of trends for extreme temperature indices showed intense and broad significant increasing trends in all absolute extreme temperature indices. In summer, more than 75% of total stations exhibited significant increasing trends for warm days and warm nights (TX90p and TN90p). In winter and spring, 71% of the total stations also showed significant increasing trends in SU25 index, whereas the percentage of stations reached 82% in summer and 64% in autumn for significant increasing trends in TR20 index. Finally, the influence of large‐scale circulation patterns on temperature extremes was examined. The results highlighted the presence of significant correlations between most of the selected extreme temperature indices and the North Sea‐Caspian pattern at annual and seasonal scales.

Criollo goats limit their grass intake in the early morning suggesting a prophylactic self-medication behaviour in a heterogeneous vegetation - R. A. Torres-Fajardo; P. G. González-Pech; C. A. Sandoval-Castro; J. Ventura-Cordero; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

The worm burden of tracer kids and lambs browsing heterogeneous vegetation is influenced by strata harvested and not total dry matter intake or plant life form - P. R. Jaimez-Rodríguez; P. G. González-Pech; J. Ventura-Cordero; D. R. B. Brito; L. M. Costa-Júnior; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

Cholinergic Differentiation of Human Neuroblastoma SH-SY5Y Cell Line and Its Potential Use as an In vitro Model for Alzheimer’s Disease Studies - Liana M. de Medeiros; Marco A. De Bastiani; Eduardo P. Rico; Patrícia Schonhofen; Bianca Pfaffenseller; Bianca Wollenhaupt-Aguiar; Lucas Grun; Florência Barbé-Tuana; Eduardo R. Zimmer; Mauro A. A. Castro; Richard B. Parsons; Fábio Klamt (Molecular Neurobiology, 2019)

Multi-model inference as criterion to determine differences in growth patterns of distinct Crassostrea gigas stocks - F. J. Reynaga-Franco; E. A. Aragón-Noriega; J. M. Grijalva-Chon; R. Castro-Longoria; J. A. Arreola-Lizárraga; R. H. Barraza-Guardado; J. Chávez-Villalba (Aquaculture International, 2019)

A comparative chemical study of PM10 in three Latin American cities: Lima, Medellín, and São Paulo - Guilherme Martins Pereira; Bruna Oraggio; Kimmo Teinilä; Danilo Custódio; Xian Huang; Risto Hillamo; Célia A. Alves; Rajasekhar Balasubramanian; Néstor Y. Rojas; Odon R. Sanchez-Ccoyllo; Pérola de Castro Vasconcellos (Air Quality, Atmosphere & Health, 2019)

Novel choline analog 2-(4-((1-phenyl-1H-pyrazol-4-yl)methyl)piperazin-1-yl)ethan-1-ol produces sympathoinhibition, hypotension, and antihypertensive effects - Ricardo Menegatti; Flávio S. Carvalho; Luciano M. Lião; Bianca Villavicencio; Hugo Verli; Aline A. Mourão; Carlos H. Xavier; Carlos H. Castro; Gustavo R. Pedrino; Octavio L. Franco; Iransé Oliveira-Silva; Nicole M. Ashpole; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Gymnopodium floribundum fodder as a model for the in vivo evaluation of nutraceutical value against Haemonchus contortus - F. A. Méndez-Ortiz; C. A. Sandoval-Castro; J. Ventura-Cordero; L. A. Sarmiento-Franco; R. H. Santos-Ricalde; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The Impact of the Right Coronary Artery Geometric Parameters on Hemodynamic Performance - N. Pinho; L. C. Sousa; C. F. Castro; C. C. António; M. Carvalho; W. Ferreira; R. Ladeiras-Lopes; N. D. Ferreira; P. Braga; N. Bettencourt; S. I. S. Pinto (Cardiovascular Engineering and Technology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Speciation and periodic restricted environments. The case of genus Ononis L. (subsections Natrix and Viscosae ) - I. Castro; J. Rocha; C. Costa; G. Costa; R. Ramírez-Rodríguez; F. Amich; V. Carnide; A. L. Crespí (Plant Biosystems, 2019)

Vaginal biota number is smaller in tailed than docked hair ewes (Ovis aries), but is not affected by copulation - A. Orihuela; A. Fierros-García; C. Hallal-Calleros; S. R. Robles-Castro; R. Ungerfeld (Tropical Animal Health and Production, 2019)

A morphological database for Colombian anuran species from conservation‐priority ecosystems - Angela M. Mendoza‐Henao; Ángela M. Cortes‐Gomez; Mailyn A. Gonzalez; Oscar Dario Hernandez‐Córdoba; Andres R. Acosta‐Galvis; Fernando Castro‐Herrera; Juan M. Daza; Julio Mario Hoyos; Martha Patricia Ramirez‐Pinilla; Nicolás Urbina‐Cardona; Beatriz Salgado‐Negret (Ecology, 2019)
Species traits provide a strong link between an organism's fitness and processes at community and ecosystem levels. However, such data remain scarce for amphibians in the Neotropics. Colombia is the country with the highest number of threatened amphibians and the second greatest number of amphibian species worldwide. We present a data set containing eight morphological traits for 4,623 museum specimens of the seven largest collections in the country corresponding to 293 species of 14 families. The number of measured specimens per species ranged from 1 to 118 individuals with a median of 8 individuals per species. Overall, this database gathered morphological information for 37.6% of Colombian anuran diversity. Species measured were mainly distributed in the high Andean forest, the páramo, and wetland ecosystems, and was part of a national initiative led by the Instituto Alexander von Humboldt. The morphological traits were selected on the basis of their role in species’ responses to environmental variability and their contributions to ecosystem processes. These traits were related to habitat use, (forearm length, tibia length, femur length, foot length, and foot webbing), predation and food chains (head width and mouth width), and nutrient recycling (snout–vent length). We expect this data set will be used in studies on functional diversity in amphibians and the development of conservation planning for these taxa. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Porosity Estimation and Geometric Characterization of Fractured and Karstified Carbonate Rocks Using GPR Data in the Salitre Formation, Brazil - Iurianne M. M. Conti; David L. de Castro; Francisco H. R. Bezerra; Caroline L. Cazarin (Pure and Applied Geophysics, 2019)

Total synthesis of the linear and angular 3-methylated regioisomers of the marine natural product Kealiiquinone and biological evaluation of related Leucetta sp. alkaloids on human breast cancer - César R. Solorio-Alvarado; Velayudham Ramadoss; Rocío Gámez-Montaño; Juan R. Zapata-Morales; Angel J. Alonso-Castro (Medicinal Chemistry Research, 2019)

Vegetable oil and carbohydrate-rich diets marginally affected intestine histomorphology, digestive enzymes activities, and gut microbiota of gilthead sea bream juveniles - Carolina Castro; Ana Couto; Alexandre F. Diógenes; Geneviève Corraze; Stéphane Panserat; Cláudia R. Serra; Aires Oliva-Teles (Fish Physiology and Biochemistry, 2019)

Production of benzyl carbonyl (rose aroma) from whey and its effect on pollutant load removal - L. Conde Báez; J. Castro Rosas; J. R. Villagómez Ibarra; I. Palma Quiroz; J. B. Páez Lerma; C. A. Gómez Aldapa (Environment, Development and Sustainability, 2019)

Pulmonary actinomycosis in a free-living black-tufted marmoset (Callithrix penicillata) - Davi E. R. Sousa; Tais M. Wilson; Mizael Machado; Alexandra A. B. G. Pereira; Gabriela R. T. Costa; Valéria Dutra; Márcio B. Castro (Primates, 2019)

Molecular detection of Rickettsia spp., Anaplasma platys and Theileria equi in ticks collected from horses in Tayrona National Park, Colombia - Adriana Santodomingo; Keyla Sierra-Orozco; Andrea Cotes-Perdomo; Lyda R. Castro (Experimental and Applied Acarology, 2019)

Analysis of a complex slope failure in a granodiorite quarry bench - Leandro R. Alejano; María Veiga; Ignacio Pérez-Rey; Uxía Castro-Filgueira; Javier Arzúa; Álvaro J. Castro-Caicedo (Bulletin of Engineering Geology and the Environment, 2019)

Comparative Assessment of BGM and PLC/PRF/5 Cell Lines for Enteric Virus Detection in Biosolids - Sherif Abd-Elmaksoud; Nohelia Castro-del Campo; Charles P. Gerba; Ian L. Pepper; Kelly R. Bright (Food and Environmental Virology, 2019)

Two epizootic Perkinsus spp. events in commercial oyster farms at Santa Catarina, Brazil - Ana C. Luz Cunha; Vitor de A. Pontinha; Maria Alcina M. de Castro; Simone Sühnel; Sthefanie C. Medeiros; Ângela M. Moura da Luz; Ricardo Harakava; Leonardo Tachibana; Danielle F. Mello; Naissa M. Danielli; Alcir L. Dafre; Aimê R. M. Magalhães; et al. (Journal of Fish Diseases, 2019)
Perkinsus spp. have been detected in various bivalve species from north‐east Brazil. Santa Catarina is a South Brasil state with the highest national oyster production. Considering the pathogenicity of some Perkinsus spp., a study was carried out to survey perkinsosis in two oyster species cultured in this State, the mangrove oyster Crassostrea gasar and the Pacific oyster Crassostrea gigas . Sampling involved eight sites along the state coast, and oyster sampling was collected during the period between January 2013 and December 2014. For the detection of Perkinsus , Ray's fluid thioglycollate medium (RFTM) and histology were used, and for the identification of the species, PCR and DNA sequencing were used. Perkinsus spp. was found by RFTM in C. gigas and C. gasar from São Francisco do Sul. This pathology was also detected in C. gasar from Balneário Barra do Sul both, by RFTM and histology. Perkinsus marinus was identified in C. gigas and C. gasar from São Francisco do Sul and Perkinsus beihaiensis in C. gasar from Balneário Barra do Sul. This is the first report of P. marinus in C. gigas from South America. Results of this preliminary study suggest that both oyster species tolerate the species of Perkinsus identified, without suffering heavy lesions.

Anti-obesity effects of kaempferol by inhibiting adipogenesis and increasing lipolysis in 3T3-L1 cells - D. Torres-Villarreal; A. Camacho; H. Castro; R. Ortiz-Lopez; A. L. de la Garza (Journal of Physiology and Biochemistry, 2019)

On the low-frequency variability of wintertime Euro-Atlantic planetary wave-breaking - Gabriele Messori; Paolo Davini; M. Carmen Alvarez-Castro; Francesco S. R. Pausata; Pascal Yiou; Rodrigo Caballero (Climate Dynamics, 2019)

Climate change resilience of a globally important sea turtle nesting population - Ana R. Patrício; Miguel R. Varela; Castro Barbosa; Annette C. Broderick; Paulo Catry; Lucy A. Hawkes; Aissa Regalla; Brendan J. Godley (Global Change Biology, 2019)
Few studies have looked into climate change resilience of populations of wild animals. We use a model higher vertebrate, the green sea turtle, as its life history is fundamentally affected by climatic conditions, including temperature‐dependent sex determination and obligate use of beaches subject to sea level rise ( SLR ). We use empirical data from a globally important population in West Africa to assess resistance to climate change within a quantitative framework. We project 200 years of primary sex ratios (1900–2100) and create a digital elevation model of the nesting beach to estimate impacts of projected SLR . Primary sex ratio is currently almost balanced, with 52% of hatchlings produced being female. Under IPCC models, we predict: (a) an increase in the proportion of females by 2100 to 76%–93%, but cooler temperatures, both at the end of the nesting season and in shaded areas, will guarantee male hatchling production; (b) IPCC SLR scenarios will lead to 33.4%–43.0% loss of the current nesting area; (c) climate change will contribute to population growth through population feminization, with 32%–64% more nesting females expected by 2120; (d) as incubation temperatures approach lethal levels, however, the population will cease growing and start to decline. Taken together with other factors (degree of foraging plasticity, rookery size and trajectory, and prevailing threats), this nesting population should resist climate change until 2100, and the availability of spatial and temporal microrefugia indicates potential for resilience to predicted impacts, through the evolution of nest site selection or changes in nesting phenology. This represents the most comprehensive assessment to date of climate change resilience of a marine reptile using the most up‐to‐date IPCC models, appraising the impacts of temperature and SLR , integrated with additional ecological and demographic parameters. We suggest this as a framework for other populations, species and taxa.

Hydrographic and Biological Impacts of a Glacial Lake Outburst Flood (GLOF) in a Patagonian Fjord - Erika Meerhoff; Leonardo R. Castro; Fabián J. Tapia; Iván Pérez-Santos (Estuaries and Coasts, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Polymorphisms within the prolactin and growth hormone/insulin-like growth factor-1 functional pathways associated with fertility traits in Holstein cows raised in a hot-humid climate - Jose C. Leyva-Corona; Javier R. Reyna-Granados; Ricardo Zamorano-Algandar; Miguel A. Sanchez-Castro; Milton G. Thomas; R. Mark Enns; Scott E. Speidel; Juan F. Medrano; Gonzalo Rincon; Pablo Luna-Nevarez (Tropical Animal Health and Production, 2018)

Using floristics, modern systematics and phylogenetics for disentangling biodiversity hotspots across scales: a Mediterranean case study - V. I. Simón-Porcar; M. Escudero; L. Navarro; A. de Castro; J. Lorite; R. Molina-Venegas; J. Arroyo (Plant Biosystems, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Brain-Derived Neurotrophic Factor Prevents Depressive-Like Behaviors in Early-Symptomatic YAC128 Huntington’s Disease Mice - Victor Silva da Fonsêca; André R. da Silva Colla; Cristine de Paula Nascimento-Castro; Evelini Plácido; Julia Macedo Rosa; Marcelo Farina; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues; Patricia S. Brocardo (Molecular Neurobiology, 2018)

Characterizing the growth of Sarcoptes scabiei infrapopulations - Inmaculada Castro; José Espinosa; José E. Granados; Francisco J. Cano-Manuel; Paulino Fandos; Arián Ráez-Bravo; Jorge R. López-Olvera; Ramón C. Soriguer; Jesús M. Pérez (Experimental and Applied Acarology, 2018)

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

The impact of kraft pulping effluent on egg survival and hatching success in two species of Clupeiformes (Teleostei) - Alejandra Llanos-Rivera; Leonardo R. Castro; Paulina Vásquez; Jeannette Silva; Enrique Bay-Schmith (Environmental Science and Pollution Research, 2018)

Characterization of esterase activity from an Acetomicrobium hydrogeniformans enzyme with high structural stability in extreme conditions - Patricia S. Kumagai; Raissa F. Gutierrez; Jose L. S. Lopes; Julia M. Martins; David M. Jameson; Aline M. Castro; Luiz F. Martins; Ricardo DeMarco; Nelma R. S. Bossolan; B. A. Wallace; Ana P. U. Araujo (Extremophiles, 2018)

Morphotectonic development of the Ceará Terrace: a marginal ridge on the western side of the Romanche Fracture Zone in the Brazilian Equatorial Margin - João Fernando Pezza Andrade; M. P. Gomes; F. H. R. Bezerra; D. L. de Castro; H. Vital (Geo-Marine Letters, 2018)

Genetic ablation of pannexin1 counteracts liver fibrosis in a chemical, but not in a surgical mouse model - Sara Crespo Yanguas; Tereza C. da Silva; Isabel V. A. Pereira; Michaël Maes; Joost Willebrords; Valery I. Shestopalov; Bruna M. Goes; Marina Sayuri Nogueira; Inar Alves de Castro; Guilherme R. Romualdo; Luís F. Barbisan; Eva Gijbels; et al. (Archives of Toxicology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Notes on the Occurrence of Oligonychus milleri (McGregor) and Oligonychus ununguis (Jacobi) (Acari: Tetranychidae) in Brazil - E B Castro; O C Zanardi; J Garlet; R Ochoa; R J F Feres (Neotropical Entomology, 2018)

Plant-based chimeric HPV-virus-like particles bearing amyloid-β epitopes elicit antibodies able to recognize amyloid plaques in APP-tg mouse and Alzheimer’s disease brains - R. Gonzalez-Castro; G. Acero Galindo; Y. García Salcedo; L. Uribe Campero; V. Vazquez Perez; M. Carrillo-Tripp; G. Gevorkian; M. A. Gomez Lim (Inflammopharmacology, 2018)

Summer-autumn air pollution in León, Spain: changes in aerosol size distribution and expected effects on the respiratory tract - F. Oduber; A. Castro; A.I. Calvo; C. Blanco-Alegre; E. Alonso-Blanco; P. Belmonte; R. Fraile (Air Quality, Atmosphere & Health, 2018)

Morphological development in the first life phase of Adriatic sturgeon Acipenser naccarii under controlled conditions - R. Cabrera‐Castro; C. Zabala; M. C. Soriguer; A. Domezain; J. A. Hernando (Journal of Fish Biology, 2018)
Early development of the Adriatic sturgeon Acipenser naccarii from its free embryo after hatching (stage 36), until late embryo stage, when the transition to exogenous feeding starts (stage 45) is described. Special emphasis is given to morphological development and description of the different structures that are formed at each life stage. After hatching, free embryos still present embryonic characteristics, little pigmentation and an ovoid yolk sac. The mouth begins to open on the second day post hatch (dph) and is fully open at 3 dph. The head begins to separate from the body at 4 dph and straightens at 6 dph. The first fins to appear are the pectoral fins on the yolk sac and an embryological fin fold that extends from behind the head to the posterior part of the yolk sac. All other fins will develop from this fold. At 7 dph the caudal fin begins to take a heterocercal form and dorsal scutes are observed. This study provides information that will assist aquaculturists by establishing a reference for the normal development of A. naccarii , which may be useful for evaluating the suitability and quality of fish produced for restocking.

Transgenerational Effects of Toxicants: An Extension of the Daphnia 21-day Chronic Assay? - B. B. Castro; A. R. Freches; M. Rodrigues; B. Nunes; S. C. Antunes (Archives of Environmental Contamination and Toxicology, 2018)

Bat and bee pollination in Psittacanthus mistletoes, a genus regarded as exclusively hummingbird‐pollinated - Rodrigo F. Fadini; Erich Fischer; Sônia J. Castro; Andréa C. Araujo; Juan Francisco Ornelas; Paulo R. de Souza (Ecology, 2018)

Atorvastatin Prevents Early Oxidative Events and Modulates Inflammatory Mediators in the Striatum Following Intranasal 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) Administration in Rats - Naiani F. Marques; Adalberto A. Castro; Gianni Mancini; Fernanda L. Rocha; Adair R. S. Santos; Rui D. Prediger; Andreza Fabro De Bem; Carla I. Tasca (Neurotoxicity Research, 2018)

Expression of Neuronal NO Synthase and the Hyperglycemic Reflex to Anoxic Stimulation of the Carotid Body in Normoglycemic and Hyperglycemic Rats - A. Hernández-Leal; H. R. Tejeda-Chávez; S. Montero; M. Lemus; E. Castro; M. Ramírez-Flores; E. Roces de Álvarez-Buylla (Neurophysiology, 2018)

The cycling gonad: retinoic‐acid synthesis and degradation patterns during adult zebrafish Danio rerio oogenesis - R. Ruivo; A. Capitão; L. F. C. Castro; M. M. Santos (Journal of Fish Biology, 2018)
The expression pattern of genes coding for enzymes of the retinoic acid (RA) synthetic and degradation pathways was characterized in adult female zebrafish Danio rerio . Females were conditioned until maturation and post‐spawn expression dynamics were determined. A striking upregulation of cyp26b1 , but not cyp26a1 , was observed following egg deposition, decreasing to initial levels during recovery. A similar, yet lower, fluctuation was observed for aldh1a2 and rdh10a , the enzymes participating in the two‐step RA biosynthesis cascade. The present work highlights the dynamics of the adult D. rerio oogenesis and uncovers novel, yet elusive, metabolic contributors. Possible compartmentalized roles for the different gene paralogue isoforms are discussed.

Palatability of the Asian clam Corbicula fluminea (Müller 1774) in an invaded system - P. S. Castro; M. I. Ilarri; V. Modesto; C. Antunes; R. Sousa (Hydrobiologia, 2018)

The Scale-Dependent Role of Biological Traits in Landscape Ecology: A Review - Andrés Felipe Suárez-Castro; Jeremy S. Simmonds; Matthew G. E. Mitchell; Martine Maron; Jonathan R. Rhodes (Current Landscape Ecology Reports, 2018)

First evidence of viral and bacterial oyster pathogens in the Brazilian coast - D F Mello; N M Danielli; F Curbani; V A Pontinha; S Suhnel; M A M Castro; S C Medeiros; N C Wendt; R Trevisan; A R M Magalhães; A L Dafre (Journal of Fish Diseases, 2018)

Wet and dry extremes in Quito (Ecuador) since the 17th century - F. Domínguez‐Castro; R. García‐Herrera; S. M. Vicente‐Serrano (International Journal of Climatology, 2018)
Wet and dry extremes in Quito (Ecuador) over the last 400 years are studied using two sources of information: the longest available instrumental rainfall series in northern South America (1891–2015) and the rogation ceremonies recorded in the Chapter Acts of Quito (1600–1822). The rogation ceremonies present a seasonal distribution that is related to the crops and to the typical distribution of rainfall over the year. August was the month with most pro serenitate rogations because farmers needed dry conditions for harvest, whereas excess rainfall at this time would lead to rotting and loss of the harvest. The pro pluvia rogations were markedly more frequent during January and February when farmers needed rain for sowing. This relationship between climate and farming activities makes Quito's rogations a good proxy for drought and extreme wet conditions during January–February–March (JFM) and wet conditions during June–July–August (JJA). Standardized precipitation index (SPI) was computed for the instrumental period. The 3‐month SPI showed a significant linear trend over the last 125 years (−0.4 per decade, p = 0.009). The five wettest periods were 1651–1657, 1663–1669, 1913–1919, 1950–1956, and 1981–1985. Droughts have intensified in frequency and length since the middle of the 20th century. The most important drought periods were 1692–1701, 1718–1723, 1976–1980, 1990–1993, and 2001–2006. The severest drought during the last 400 years occurred in 1692–1701 when a great famine devastated Quito and affected most of the central Andes.

Morpho-environmental strategies in the genus Ononis L. (subsections Natrix and Viscosae ) in Western Mediterranean - J. Rocha; R. Ramírez; M. Díaz; M. Martins; I. García-Cabral; F. Amich; R. Almeida; V. Carnide; I. Castro; A. L. Crespí (Plant Biosystems, 2018)

A comparison of temporal variability of observed and model‐based pan evaporation over Uruguay (1973–2014) - Sergio M. Vicente‐Serrano; Mario Bidegain; Miquel Tomas‐Burguera; Fernando Dominguez‐Castro; Ahmed El Kenawy; Tim R. McVicar; Cesar Azorin‐Molina; Juan I. López‐Moreno; Raquel Nieto; Luis Gimeno; Agustín Giménez (International Journal of Climatology, 2018)
This study analyses variability and trends of atmospheric evaporative demand ( AED ) across Uruguay in the past four decades. Changes were assessed using pan evaporation measurements from 10 meteorological stations and compared to PenPan model calculations, which is a physically based model that employs meteorological data as input. Results demonstrate a high agreement between the observed AED and those estimated from the PenPan model. Both observations and model estimations agree on a high interannual variability in AED , though being statistically insignificant ( p > 0.05) at seasonal and annual scales. Given that AED shows high sensitivity to changes in relative humidity and sunshine duration, as a surrogate of solar radiation, the lack of significant trends in the AED observations and estimations over Uruguay can be linked to the insignificant trend found for these climate variables for the period from 1973 to 2014. This is the first study that reports Pan evaporation trends for this part of the world, helping to infill gaps for mid‐latitude Southern Hemisphere areas, which are poorly represented in Pan evaporation trends.

Vertical deformation and sea level changes in the coast of Chile by satellite altimetry and tide gauges - Henry D. C. Montecino; Vagner G. Ferreira; Aharon Cuevas; Leoncio Castro Cabrera; Juan Carlos Soto Báez; Silvio R. C. De Freitas (International Journal of Remote Sensing, 2017)

Correction to: Stepwise strategy for monitoring toxic cyanobacterial blooms in lentic water bodies - Inês P. E. Macário; Bruno B. Castro; Maria I. S. Nunes; Cristina Pizarro; Carla Coelho; Fernando Gonçalves; Daniela R. de Figueiredo (Environmental Monitoring and Assessment, 2017)

Stepwise strategy for monitoring toxic cyanobacterial blooms in lentic water bodies - Inês P. E. Macário; Bruno B. Castro; Isabel M. S. Nunes; Cristina Pizarro; Carla Coelho; Fernando Gonçalves; Daniela R. de Figueiredo (Environmental Monitoring and Assessment, 2017)

Asparagus macrorrhizus Pedrol, Regalado et López-Encina, an endemic species from Spain in extreme extinction risk, is a valuable genetic resource for asparagus breeding - J. J. Regalado; R. Moreno; P. Castro; E. Carmona-Martin; R. Rodríguez; J. Pedrol; N. Larrañaga; R. Guillén; J. Gil; C. L. Encina (Genetic Resources and Crop Evolution, 2017)

Migratory preferences of humpback whales between feeding and breeding grounds in the eastern South Pacific - Jorge Acevedo; Anelio Aguayo‐Lobo; Judith Allen; Natalia Botero‐Acosta; Juan Capella; Cristina Castro; Luciano Dalla Rosa; Judith Denkinger; Fernando Félix; Lilian Flórez‐González; Frank Garita; Héctor M. Guzmán; et al. (Marine Mammal Science, 2017)
Latitudinal preferences within the breeding range have been suggested for Breeding Stock G humpback whales that summer in different feeding areas of the eastern South Pacific. To address this hypothesis, humpback whales photo‐identified from the Antarctic Peninsula and the Fueguian Archipelago (southern Chile) were compared with whales photo‐identified from lower latitudes extending from northern Peru to Costa Rica. This comparison was performed over a time span that includes 18 austral seasons. A total of 238 whales identified from the Antarctic Peninsula and 25 whales from the Fueguian Archipelago were among those photo‐identified at the breeding grounds. Our findings showed that humpback whales from each feeding area were resighted unevenly across the breeding grounds, which suggests a degree of spatial structuring in the migratory pathway. Humpback whales that feed at the Antarctic Peninsula were more likely to migrate to the southern breeding range between northern Peru and Colombia, whereas whales that feed at the Fueguian Archipelago were more likely to be found in the northern range of the breeding ground off Panama. Further photo‐identification efforts and genetic sampling from poorly sampled or unsampled areas are recommended to confirm these reported connectivity patterns.

How does temperature influences the development of lactococcosis? Transcriptomic and immunoproteomic in vitro approaches - R Castro; M Reguera‐Brito; G H López‐Campos; M M Blanco; M Aguado‐Urda; J F Fernández‐Garayzábal; A Gibello (Journal of Fish Diseases, 2017)
Lactococcus garvieae is the aetiological agent of lactococcosis, a haemorrhagic septicaemia that affects marine and freshwater fish, with special incidence and economic relevance in farmed rainbow trout. Water temperature is one of the most important predisposing factors in the development of lactococcosis outbreaks. Lactococcosis in trout usually occur when water temperatures rise to about 18 °C, while fish carriers remain asymptomatic at temperatures below 13 °C. The aim of this work was to analyse the differences in the complete transcriptome response of L. garvieae grown at 18 °C and at 13 °C and to identify the immunogenic proteins expressed by this bacterium at 18 °C. Our results show that water temperature influences the expression of L. garvieae genes involved in the lysis of part of the bacterial cell population and in the cold response bacterial adaptation. Moreover, the surface immunogenic protein profile at 18 °C suggests an important role of the lysozyme‐like enzyme, WxL surface proteins and some putative moonlighting proteins (proteins with more than one function, usually associated with different cellular locations) as virulence factors in L. garvieae . The results of this study could provide insights into the understanding of the virulence mechanisms of L. garvieae in fish.

Woody plant community structure in “Dense Cerrado” fragments in the Upper Basin of the Araguaia River (Central Brazil): relationship with habitat loss and geographical distance - Mariana N. Siqueira; Selma Simões de Castro; Alessandro R. Morais; Karla M. S. Faria (Brazilian Journal of Botany, 2017)

Influence of drinking water salinity on carcass characteristics and meat quality of Santa Inês lambs - Daniela P. V. Castro; Sandra M. Yamamoto; Gherman G. L. Araújo; Rafael S. B. Pinheiro; Mario A. A. Queiroz; Ítalo R. R. Albuquerque; José H. A. Moura (Tropical Animal Health and Production, 2017)

Contribution by vertebrates to seed dispersal effectiveness in the Galápagos Islands: a community‐wide approach - M. Nogales; A. González‐Castro; B. Rumeu; A. Traveset; P. Vargas; P. Jaramillo; J. M. Olesen; R. H. Heleno (Ecology, 2017)
Seed dispersal and seedling recruitment are crucial phases in the life cycle of all spermatophyte plants. The net contribution of seed dispersers to plant establishment is known as seed dispersal effectiveness ( SDE ) and is defined as the product of a quantitative (number of seeds dispersed) and a qualitative (probability of recruitment) component. In Galápagos, we studied the direct contribution to SDE (number of seeds dispersed and effect on seedling emergence) provided by the five island groups of frugivores (giant tortoises, lizards, medium‐sized passerine birds, small non‐finch passerine birds, and finches) in the two main habitats in this archipelago: the lowland and the highland zones, and found 16 vertebrate species dispersing 58 plant species. Data on frequency of occurrence of seeds in droppings and number of seeds dispersed per unit area produced contrasting patterns of seed dispersal. Based on the former, giant tortoises and medium‐sized passerines were the most important seed dispersers. However, based on the latter, small non‐finch passerines were the most important dispersers, followed by finches and medium‐sized passerines. The effect of disperser gut passage on seedling emergence varied greatly depending on both the disperser and the plant species. Although the contribution to SDE provided by different disperser guilds changed across plant species, medium‐sized passerines (e.g., mockingbirds) provided a higher contribution to SDE than lava lizards in 10 out of 16 plant species analysed, whereas lava lizards provided a higher contribution to SDE than birds in five plant species. While both the quantitative and qualitative components addressed are important, our data suggests that the former is a better predictor of SDE in the Galápagos archipelago.

Preparation of Activated Carbon from Sugarcane Bagasse Soot and Methylene Blue Adsorption - Luana A. R. Giusto; Fábio L. Pissetti; Talita S. Castro; Fabiano Magalhães (Water, Air, & Soil Pollution, 2017)

Bacteriological and histopathological study of farmed rainbow trout, Oncorhynchus mykiss , in Peru - E C Mateo; T Castro; V Sierralta; D R Mateo (Journal of Fish Diseases, 2017)

Source Functions and Path Effects from Earthquakes in the Farallon Transform Fault Region, Gulf of California, Mexico that Occurred on October 2013 - Raúl R. Castro; Joann M. Stock; Egill Hauksson; Robert W. Clayton (Pure and Applied Geophysics, 2017)

Host status of selected cultivated fruit crops to Meloidogyne enterolobii - Vânia M. Freitas; Joelma G. P. Silva; Cesar B. Gomes; José M. C. Castro; Valdir R. Correa; Regina M. D. G. Carneiro (European Journal of Plant Pathology, 2017)

Fall rate of burnt pines across an elevational gradient in a Mediterranean mountain - Carlos R. Molinas-González; Alexandro B. Leverkus; Sara Marañón-Jiménez; Jorge Castro (European Journal of Forest Research, 2017)

Life-cycle assessment of the soybean-sunflower production system in the Brazilian Cerrado - Marília I. S. Folegatti Matsuura; Fernando R. T. Dias; Juliana F. Picoli; Kássio R. Garcia Lucas; Cesar de Castro; Marcelo H. Hirakuri (The International Journal of Life Cycle Assessment, 2017)

The climate in Zafra from 1750 to 1840: temperature indexes from documentary sources - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. M. Vaquero (Climatic Change, 2017)

Productivity of a Continuous Mining System for Block Caving Mines - L. F. Orellana; R. Castro; A. Hekmat; E. Arancibia (Rock Mechanics and Rock Engineering, 2017)

Exploring 1,2,3-triazole derivatives by using in vitro and in silico assays to target new antifungal agents and treat Candidiasis - Taísa F. Santos; Jéssica B. de Jesus; Paulo M. Neufeld; Alessandro K. Jordão; Vinícius R. Campos; Anna C. Cunha; Helena C. Castro; Maria C. B. V. de Souza; Vitor F. Ferreira; Carlos R. Rodrigues; Paula A. Abreu (Medicinal Chemistry Research, 2017)

Reliable methods for determination of triazine herbicides and their degradation products in seawater and marine sediments using liquid chromatography-tandem mass spectrometry - N. Rodríguez-González; R. Uzal-Varela; M.J. González-Castro; S. Muniategui-Lorenzo; E. Beceiro-González (Environmental Science and Pollution Research, 2017)

Integrated proteomics and metabolomics suggests symbiotic metabolism and multimodal regulation in a fungal‐endobacterial system - Zhou Li; Qiuming Yao; Stephen P. Dearth; Matthew R. Entler; Hector F. Castro Gonzalez; Jessie K. Uehling; Rytas J. Vilgalys; Gregory B. Hurst; Shawn R. Campagna; Jessy L. Labbé; Chongle Pan (Environmental Microbiology, 2017)
Summary Many plant‐associated fungi host endosymbiotic endobacteria with reduced genomes. While endobacteria play important roles in these tri‐partite plant–fungal–endobacterial systems, the active physiology of fungal endobacteria has not been characterized extensively by systems biology approaches. Here, we use integrated proteomics and metabolomics to characterize the relationship between the endobacterium Mycoavidus sp. and the root‐associated fungus Mortierella elongata . In nitrogen‐poor media, M. elongata had decreased growth but hosted a large and growing endobacterial population. The active endobacterium likely extracted malate from the fungal host as the primary carbon substrate for energy production and biosynthesis of phospho‐sugars, nucleobases, peptidoglycan and some amino acids. The endobacterium obtained nitrogen by importing a variety of nitrogen‐containing compounds. Further, nitrogen limitation significantly perturbed the carbon and nitrogen flows in the fungal metabolic network. M. elongata regulated many pathways by concordant changes on enzyme abundances, post‐translational modifications, reactant concentrations and allosteric effectors. Such multimodal regulations may be a general mechanism for metabolic modulation.

Life cycle inference and phylogeny of Ortholinea labracis n. sp. (Myxosporea: Ortholineidae), a parasite of the European seabass Dicentrarchus labrax (Teleostei: Moronidae), in a Portuguese fish farm - L F Rangel; S Rocha; G Casal; R Castro; R Severino; C Azevedo; F Cavaleiro; M J Santos (Journal of Fish Diseases, 2017)
Ortholinea labracis n. sp. is described and its life cycle is inferred from a Southern Portuguese fish farm, with basis on microscopic and molecular procedures. This myxosporean parasite infects the urinary bladder of the European seabass Dicentrarchus labrax and the intestinal epithelium of a marine oligochaete of the genus Tectidrilus . Myxospores subspherical in valvular view and ellipsoidal in sutural view measuring 7.6 ± 0.3 (6.8–8.7) μm in length, 7.2 ± 0.2 (6.7–7.7) μm in width and 6.5 ± 0.4 (5.8–7.7) μm in thickness. Two polar capsules, 3.0 ± 0.2 (2.6–3.4) μm long and 2.4 ± 0.1 (2.0–2.9) μm wide, located at the same level, but with divergent orientation and opening to opposite sides of the suture line. Sequencing of the SSU rRNA gene revealed a similarity of 100% between the analysed myxospores and triactinomyxon actinospores. The phylogenetic setting of O. labracis n. sp. shows subgrouping in correlation with tissue tropism, but identifies this parasite as another exception to the main division of Myxosporea into the main freshwater and marine lineages.

Gastrointestinal nematode infection does not affect selection of tropical foliage by goats in a cafeteria trial - J. Ventura-Cordero; P. G. González-Pech; P. R. Jaimez-Rodriguez; G. I. Ortíz-Ocampo; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2017)

Synthesis and in vitro evaluation of novel triazole/azide chalcones - Fernanda C. G. Evangelista; Maralice O. Bandeira; Graziele D. Silva; Marina G. Silva; Silmara N. Andrade; Deisielly R. Marques; Luciana M. Silva; Whocely V. Castro; Fabio V. Santos; Gustavo H. R. Viana; José A. F. P. Villar; Adriano P. Sabino; et al. (Medicinal Chemistry Research, 2017)

Diabetes and breast cancer mortality in Black women - Marjory Charlot; Nelsy Castro-Webb; Traci N. Bethea; Kimberly Bertrand; Deborah A. Boggs; Gerald V. Denis; Lucile L. Adams-Campbell; Lynn Rosenberg; Julie R. Palmer (Cancer Causes & Control, 2017)

Characterization of hepatitis B virus infection in illicit drug users in the Marajó Archipelago, northern Brazil - Andréia P. Andrade; Suzy D. B. Pacheco; Fabricio Q. Silva; Luiz M. L. Pinheiro; Jairo A. A. Castro; Carlos E. M. Amaral; Renata B. Hermes; Benedikt Fischer; João R. R. Pinho; José Alexandre R. Lemos; Aldemir B. Oliveira-Filho (Archives of Virology, 2017)

Performance and health of Holstein calves fed different levels of milk fortified with symbiotic complex containing pre- and probiotics - M. I. Marcondes; T. R. Pereira; J. C. C. Chagas; E. A. Filgueiras; M. M. D. Castro; G. P. Costa; A. L. L. Sguizzato; R. D. Sainz (Tropical Animal Health and Production, 2016)

Detailed Morphology of All Life Stages of the Agave Red Worm, Comadia redtenbacheri (Hammerschmidt) (Lepidoptera: Cossidae) - R Castro-Torres; C Llanderal-Cázares (Neotropical Entomology, 2016)

Evidence of oxidative stress in brain and liver of young rats submitted to experimental galactosemia - Márcia B. Castro; Bruna K. Ferreira; José Henrique Cararo; Adália E. Chipindo; Marina L. Magenis; Monique Michels; Lucinéia G. Danielski; Marcos R. de Oliveira; Gustavo C. Ferreira; Emilio L. Streck; Fabricia Petronilho; Patrícia F. Schuck (Metabolic Brain Disease, 2016)

Nitrogen Use Efficiency for Sugarcane-Biofuel Production: What Is Next? - R. Otto; S. A. Q. Castro; E. Mariano; S. G. Q. Castro; H. C. J. Franco; P. C. O. Trivelin (BioEnergy Research, 2016)

Acute hypoxia up-regulates HIF-1α and VEGF mRNA levels in Amazon hypoxia-tolerant Oscar (Astronotus ocellatus) - R. B. Baptista; N. Souza-Castro; V. M. F. Almeida-Val (Fish Physiology and Biochemistry, 2016)

Integrative taxonomy of Peniculus , Metapeniculus , and Trifur (Siphonostomatoida: Pennellidae), copepod parasites of marine fishes from Chile: species delimitation analyses using DNA barcoding and morphological evidence - Raúl Castro-romero; Martín M. Montes; Sergio R. Martorelli; Diego Sepulveda; Silvia Tapia; Andrés Martínez-aquino (Systematics and Biodiversity, 2016)

Diploid male dynamics under different numbers of sexual alleles and male dispersal abilities - Luiz R. R. Faria; Elaine Della Giustina Soares; Eduardo do Carmo; Paulo Murilo Castro de Oliveira (Theory in Biosciences, 2016)

Assessing the extent and nature of wildlife trade on the dark web - Joseph R. Harrison; David L. Roberts; Julio Hernandez‐Castro (Conservation Biology, 2016)
Use of the internet as a trade platform has resulted in a shift in the illegal wildlife trade. Increased scrutiny of illegal wildlife trade has led to concerns that online trade of wildlife will move onto the dark web. To provide a baseline of illegal wildlife trade on the dark web, we downloaded and archived 9852 items (individual posts) from the dark web, then searched these based on a list of 121 keywords associated with illegal online wildlife trade, including 30 keywords associated with illegally traded elephant ivory on the surface web. Results were compared with items known to be illegally traded on the dark web, specifically cannabis, cocaine, and heroin, to compare the extent of the trade. Of these 121 keywords, 4 resulted in hits, of which only one was potentially linked to illegal wildlife trade. This sole case was the sale and discussion of Echinopsis pachanoi (San Pedro cactus), which has hallucinogenic properties. This negligible level of activity related to the illegal trade of wildlife on the dark web relative to the open and increasing trade on the surface web may indicate a lack of successful enforcement against illegal wildlife trade on the surface web.

Seed‐dispersal networks on the C anaries and the G alápagos archipelagos: interaction modules as biogeographical entities - M. Nogales; R. Heleno; B. Rumeu; A. González‐Castro; A. Traveset; P. Vargas; J. M. Olesen (Global Ecology and Biogeography, 2016)
Aim Mutualistic network parameters, such as modularity and nestedness, show non‐random linkage patterns. Both increase network stability in different ways. Modularity hampers extinction cascades, whereas nestedness resists network disassembly. We explore these parameters in seed‐dispersal networks in two archipelagos and the significance of life history, habitat, geography and phylogeny as drivers of linkage patterns and the applicability of modules as biogeographical entities. Location C anaries ( A tlantic O cean) and G alápagos ( P acific O cean). Methods We compiled data on plant–seed disperser interactions from own observations and the literature, estimated network parameters describing interaction patterns (connectance, nestedness and modularity) and constructed a backbone phylogeny for the analyses. Results The C anarian network was highly nested but weakly modular, whereas the G alápagos network showed the opposite characteristics. Most key network species are native and have a favourable conservation status. Modularity in the C anaries is correlated with habitats (indirectly affected by altitude and orientation), whereas in the G alápagos it mainly reflects the functional roles of species. Main conclusions The divergent link patterns for the archipelagos imply that the highly nested C anarian network is stable against disassembly, whereas the modular G alápagos network may show strong resistance against extinction cascades. This difference may be driven by the specific evolutionary dynamics on the archipelagos.

Genetic pool structure of local apple cultivars from Portugal assessed by microsatellites - V. Ferreira; A. M. Ramos-Cabrer; V. Carnide; O. Pinto-Carnide; A. Assunção; A. Marreiros; R. Rodrigues; S. Pereira-Lorenzo; I. Castro (Tree Genetics & Genomes, 2016)

Quality of the Solimões River water for domestic use by the riverine community situated in Manacapuru-Amazonas-Brazil - N. G. P. Pantoja; L. M. Castro; S. D. Rocha; J. A. Silva; J. S. P. Ribeiro; A. R. Donald; L. M. Silva; T. C. S. Oliveira (Environmental Science and Pollution Research, 2016)

CMA band variability and physical mapping of 5S and 45S rDNA sites in Brazilian Cactaceae: Pereskioideae and Opuntioideae - Juliana P. Castro; Enoque Medeiros-Neto; Gustavo Souza; Lânia I. F. Alves; Fabiane R. C. Batista; Leonardo P. Felix (Brazilian Journal of Botany, 2016)

Efficacy of Cinnamaldehyde Against Enteric Viruses and Its Activity After Incorporation Into Biodegradable Multilayer Systems of Interest in Food Packaging - M. J. Fabra; J. L. Castro-Mayorga; W. Randazzo; J. M. Lagarón; A. López-Rubio; R. Aznar; G. Sánchez (Food and Environmental Virology, 2016)

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

Antinociceptive effect of a novel armed spider peptide Tx3-5 in pathological pain models in mice - Sara M. Oliveira; Cássia R. Silva; Gabriela Trevisan; Jardel G. Villarinho; Marta N. Cordeiro; Michael Richardson; Márcia H. Borges; Célio J. Castro; Marcus V. Gomez; Juliano Ferreira (Pflügers Archiv - European Journal of Physiology, 2016)

Insights into the virulence‐related genes of Edwardsiella tarda isolated from turbot in Europe: genetic homogeneity and evidence for vibrioferrin production - N Castro; C R Osorio; N Buján; J C Fuentes; J Rodríguez; M Romero; C Jiménez; A E Toranzo; B Magariños (Journal of Fish Diseases, 2016)
Edwardsiella tarda has long been known as a pathogen that causes severe economic losses in aquaculture industry. Insights gained on E. tarda pathogenesis may prove useful in the development of new methods for the treatment of infections as well as preventive measures against future outbreaks. In this report, we have established the correlation between the presence of virulence genes, related with three aspects typically involved in bacterial pathogenesis (chondroitinase activity, quorum sensing and siderophore‐mediated ferric uptake systems), in the genome of E. tarda strains isolated from turbot in Europe and their phenotypic traits. A total of 8 genes were tested by PCR for their presence in 73 E. tarda isolates. High homogeneity was observed in the presence/absence pattern of all the strains. Positive results in the amplification of virulence‐related genes were correlated with the detection of chondroitinase activity in agar plates, in vivo AHL production during fish infection and determination of type of siderophore produced by E. tarda . To the best of our knowledge, this is the first study carried out with European strains on potential virulence factors. Furthermore, we demonstrated for the first time that E. tarda produces the siderophore vibrioferrin.

Root system traits and its relationship with photosynthesis and productivity in four maize genotypes under drought - A.O. Lavinsky; P.C. Magalhães; M.M. Diniz; C.C. Gomes-Jr; E.M. Castro; R. Ávila (Cereal Research Communications, 2016)

Effects of fish oil replacement by vegetable oil blend on digestive enzymes and tissue histomorphology of European sea bass (Dicentrarchus labrax) juveniles - Carolina Castro; Ana Couto; Amalia Pérez-Jiménez; Cláudia R. Serra; Patricia Díaz-Rosales; Rui Fernandes; Geneviève Corraze; Stéphane Panserat; Aires Oliva-Teles (Fish Physiology and Biochemistry, 2016)

Thyroid hormones improve cardiac function and decrease expression of pro-apoptotic proteins in the heart of rats 14 days after infarction - Alexandre Luz de Castro; Rafael Oliveira Fernandes; Vanessa D. Ortiz; Cristina Campos; Jéssica H. P. Bonetto; Tânia R. G. Fernandes; Adriana Conzatti; Rafaela Siqueira; Angela Vicente Tavares; Paulo Cavalheiro Schenkel; Adriane Belló-Klein; Alex Sander da Rosa Araujo (Apoptosis, 2016)

Comparative histology and ontogenetic change in the carapace of armadillos (Mammalia: Dasypodidae) - C. M. Krmpotic; M. R. Ciancio; A. A. Carlini; M. C. Castro; A. C. Scarano; C. G. Barbeito (Zoomorphology, 2015)

Flower and fruit structure of the endangered species Petagnaea gussonei (Sprengel) Rauschert (Saniculoideae, Apiaceae) and implications for its reproductive biology - O. De Castro; P. Colombo; L. Gianguzzi; R. Perrone (Plant Biosystems, 2015)

Expression of myostatin in the spotted rose snapper Lutjanus guttatus during larval and juvenile development under cultured conditions - J. Torres‐Velarde; L. Ibarra‐Castro; E. Rodríguez‐Ibarra; I. Sifuentes‐Romero; R. Hernández‐Cornejo; A. García‐Gasca (Journal of Fish Biology, 2015)
In this study, the developmental expression pattern of myostatin ( mstn ) in the spotted rose snapper Lutjanus guttatus under culture conditions is presented. The full coding sequence of mstn from L. guttatus was isolated from muscle tissue, obtaining 1134 nucleotides which encode a peptide of 377 amino acids. The phylogenetic analysis indicated that this sequence corresponds to mstn‐1 . mstn expression was detected in embryonic stages, and maintained at low levels until 28 days post‐hatch, when it showed a significant increase, coinciding with the onset of metamorphosis. After that, expression was fluctuating, coinciding probably with periods of rapid and slow muscle growth or individual growth rates. mstn expression was also analysed by body mass with higher levels detected in smaller animals, irrespective of age. mstn was also expressed in other tissues from L. guttatus , presenting higher levels in brain, eye and gill. In brain for instance, two variants of mstn were isolated, both coding sequences were identical to muscle, except that one of them contained a 75 nucleotide deletion in exon 1, maintaining the reading frame but deleting two conserved cysteine residues. Phylogenetic analysis indicated that this brain variant was also mstn‐1 . The function of this variant is not clear and needs further investigation. These results indicate that mstn‐1 participates in different physiological processes other than muscle growth in fishes.

Estimation of the spectral parameter kappa in the region of the Gulf of California, Mexico - Raúl R. Castro; Lenin Ávila-Barrientos (Journal of Seismology, 2015)

Regional climate modelling in CLARIS-LPB: a concerted approach towards twentyfirst century projections of regional temperature and precipitation over South America - E. Sánchez; S. Solman; A. R. C. Remedio; H. Berbery; P. Samuelsson; R. P. Da Rocha; C. Mourão; L. Li; J. Marengo; M. de Castro; D. Jacob (Climate Dynamics, 2015)

How pervasive is biotic homogenization in human‐modified tropical forest landscapes? - Ricardo Ribeiro de Castro Solar; Jos Barlow; Joice Ferreira; Erika Berenguer; Alexander C. Lees; James R. Thomson; Júlio Louzada; Márcia Maués; Nárgila G. Moura; Victor H. F. Oliveira; Júlio C. M. Chaul; José Henrique Schoereder; et al. (Ecology Letters, 2015)
Land‐cover change and ecosystem degradation may lead to biotic homogenization, yet our understanding of this phenomenon over large spatial scales and different biotic groups remains weak. We used a multi‐taxa dataset from 335 sites and 36 heterogeneous landscapes in the Brazilian Amazon to examine the potential for landscape‐scale processes to modulate the cumulative effects of local disturbances. Biotic homogenization was high in production areas but much less in disturbed and regenerating forests, where high levels of among‐site and among‐landscape β‐diversity appeared to attenuate species loss at larger scales. We found consistently high levels of β‐diversity among landscapes for all land cover classes, providing support for landscape‐scale divergence in species composition. Our findings support concerns that β‐diversity has been underestimated as a driver of biodiversity change and underscore the importance of maintaining a distributed network of reserves, including remaining areas of undisturbed primary forest, but also disturbed and regenerating forests, to conserve regional biota.

The past, present and future of thermophilous Cyperus polystachyos Rottb. (Cyperaceae) on the island of Ischia (southern Italy) - G. Sibilio; A. Russo; R. Vallariello; B. Menale; P. De Luca; O. De Castro (Plant Biosystems, 2015)

Analytical Solutions for Steady Phreatic Flow Appearing/Re-emerging Toward/from a Bedrock/Caprock Isobaric Breach: The Polubarinova-Kochina–Numerov and Pavlovsky Problems Revisited - Yu. V. Obnosov; A. R. Kacimov; O. Castro-Orgaz (Transport in Porous Media, 2015)

New insights towards the establishment of phycocyanin concentration thresholds considering species-specific variability of bloom-forming cyanobacteria - Inês P. E. Macário; Bruno B. Castro; Maria I. S. Nunes; Sara C. Antunes; Cristina Pizarro; Carla Coelho; Fernando Gonçalves; Daniela R. de Figueiredo (Hydrobiologia, 2015)

Isotopic variation in five species of stream fishes under the influence of different land uses - D. R. Carvalho; D. Castro; M. Callisto; M. Z. Moreira; P. S. Pompeu (Journal of Fish Biology, 2015)
The aim of this study was to test if changes in land use alter the isotopic signature of fish species, promoting changes in the trophic position and food resource partitioning between these consumers. Three different systems were investigated: pasture streams ( n = 3), streams in sugar cane plantations ( n = 3) and reference streams ( n = 3). Fish species Aspidoras fuscoguttatus , Astyanax altiparanae , Characidium zebra , Hisonotus piracanjuba and Knodus moenkhausii were selected, and their nitrogen and carbon isotopic compositions were estimated to assess changes in the trophic level and partitioning of food items consumed. The composition of δ 13 C (‰) only differed among the land use categories for A. altiparanae , H. piracanjuba and K. moenkhausii. Resource partitioning was different for all species, with changes in the sources or proportions they consumed in each land use category, but only A. altiparanae introduced new food sources in large quantity in altered land uses. It is important to note, however, that the results from the resource partitioning analysis are limited due to large overlapping of isotopic signatures between the analysed food resources. All fish species exhibited variation in δ 15 N (‰), with the highest values found in streams under sugar cane or pasture influence. Despite the variation in nitrogen isotopic values, only C. zebra and H. piracanjuba displayed changes in trophic level. Therefore, it is believed that the increase in the δ 15 N (‰) value of the individuals collected in streams under the influence of sugar cane or pasture was due to the greater influence of livestock dung and chemical and organic fertilizers. The results also highlight the importance of studying consumer species along with all forms of resources available at each location separately, because the signatures of these resources also vary within different land uses.

Expression of intercellular lipid transport and cholesterol metabolism genes in eggs and early larvae stages of turbot, Scophthalmus maximus, a marine aquaculture species - I. Cunha; S. Galante-Oliveira; E. Rocha; R. Urbatzka; L. F. C. Castro (Marine Biology, 2015)

Study of the somaclonal variation produced by different methods of polyploidization in Asparagus officinalis L. - J. J. Regalado; E. Carmona Martín; P. Castro; R. Moreno; J. Gil; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Molecular detection of Rickettsia, Borrelia, and Babesia species in Ixodes ricinus sampled in northeastern, central, and insular areas of Italy - Lyda R. Castro; Simona Gabrielli; Albertina Iori; Gabriella Cancrini (Experimental and Applied Acarology, 2015)

Detection of a new QTL/gene for growth habit in chickpea CaLG1 using wide and narrow crosses - L. Ali; S. Azam; J. Rubio; H. Kudapa; E. Madrid; R. K. Varshney; P. Castro; W. Chen; J. Gil; T. Millan (Euphytica, 2015)

Dispersive liquid–liquid microextraction and HPLC to analyse fluoxetine and metoprolol enantiomers in wastewaters - Ana R. Ribeiro; Virgínia M. F. Gonçalves; Alexandra S. Maia; Cláudia Ribeiro; Paula M. L. Castro; Maria E. Tiritan (Environmental Chemistry Letters, 2015)

Removal of Decachlorobiphenyl in Vermicomposting Process Amended with Rabbit Manure and Peat Moss - Juan J. Villalobos-Maldonado; Rocío Meza-Gordillo; Norma A. Mancilla-Margalli; Teresa R. Ayora-Talavera; Martha A. Rodríguez-Mendiola; Carlos Arias-Castro; Paola T. Vázquez-Villegas; Federico A. Gutiérrez-Miceli; Víctor M. Ruíz-Valdiviezo (Water, Air, & Soil Pollution, 2015)

Micropropagation of wild species of the genus Asparagus L. and their interspecific hybrids with cultivated A. officinalis L., and verification of genetic stability using EST-SSRs - J. J. Regalado; E. Carmona-Martín; P. Castro; R. Moreno; J. Gil; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Determination of the spinel group end-members based on electron microprobe analyses - Gabriela R. Ferracutti; M. Florencia Gargiulo; M. Luján Ganuza; Ernesto A. Bjerg; Silvia M. Castro (Mineralogy and Petrology, 2015)

Modulation of apoptosis by sulforaphane is associated with PGC-1α stimulation and decreased oxidative stress in cardiac myoblasts - Rafael O. Fernandes; Jéssica H. P. Bonetto; Boran Baregzay; Alexandre L. de Castro; Stephanie Puukila; Heidi Forsyth; Paulo C. Schenkel; Susana F. Llesuy; Ilma Simoni Brum; Alex Sander R. Araujo; Neelam Khaper; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2015)

The climate in Zafra from 1750 to 1840: precipitation - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. M. Vaquero (Climatic Change, 2015)

HER2 and β-catenin protein location: importance in the prognosis of breast cancer patients and their correlation when breast cancer cells suffer stressful situations - F. Darío Cuello-Carrión; Jorge E. Shortrede; Daiana Alvarez-Olmedo; Niubys Cayado-Gutiérrez; Gisela N. Castro; Felipe C. M. Zoppino; Martín Guerrero; Estefania Martinis; Rodolfo Wuilloud; Nidia N. Gómez; Verónica Biaggio; Javier Orozco; et al. (Clinical & Experimental Metastasis, 2015)

Anticipative management for coral reef ecosystem services in the 21st century - Alice Rogers; Alastair R. Harborne; Christopher J. Brown; Yves‐Marie Bozec; Carolina Castro; Iliana Chollett; Karlo Hock; Cheryl A. Knowland; Alyssa Marshell; Juan C. Ortiz; Tries Razak; George Roff; et al. (Global Change Biology, 2015)
Under projections of global climate change and other stressors, significant changes in the ecology, structure and function of coral reefs are predicted. Current management strategies tend to look to the past to set goals, focusing on halting declines and restoring baseline conditions. Here, we explore a complementary approach to decision making that is based on the anticipation of future changes in ecosystem state, function and services. Reviewing the existing literature and utilizing a scenario planning approach, we explore how the structure of coral reef communities might change in the future in response to global climate change and overfishing. We incorporate uncertainties in our predictions by considering heterogeneity in reef types in relation to structural complexity and primary productivity. We examine 14 ecosystem services provided by reefs, and rate their sensitivity to a range of future scenarios and management options. Our predictions suggest that the efficacy of management is highly dependent on biophysical characteristics and reef state. Reserves are currently widely used and are predicted to remain effective for reefs with high structural complexity. However, when complexity is lost, maximizing service provision requires a broader portfolio of management approaches, including the provision of artificial complexity, coral restoration, fish aggregation devices and herbivore management. Increased use of such management tools will require capacity building and technique refinement and we therefore conclude that diversification of our management toolbox should be considered urgently to prepare for the challenges of managing reefs into the 21st century.

Inoculation of Pinus pinea seedlings with Pisolithus tinctorius and Suillus bellinii promotes plant growth in benfluralin contaminated soil - Albina R. Franco; Paula M. L. Castro (Plant and Soil, 2015)

Reassessing global change research priorities in mediterranean terrestrial ecosystems: how far have we come and where do we go from here? - E. Doblas‐Miranda; J. Martínez‐Vilalta; F. Lloret; A. Álvarez; A. Ávila; F. J. Bonet; L. Brotons; J. Castro; J. Curiel Yuste; M. Díaz; P. Ferrandis; E. García‐Hurtado; et al. (Global Ecology and Biogeography, 2015)
Aim Mediterranean terrestrial ecosystems serve as reference laboratories for the investigation of global change because of their transitional climate, the high spatiotemporal variability of their environmental conditions, a rich and unique biodiversity and a wide range of socio‐economic conditions. As scientific development and environmental pressures increase, it is increasingly necessary to evaluate recent progress and to challenge research priorities in the face of global change. Location Mediterranean terrestrial ecosystems. Methods This article revisits the research priorities proposed in a 1998 assessment. Results A new set of research priorities is proposed: (1) to establish the role of the landscape mosaic on fire‐spread; (2) to further research the combined effect of different drivers on pest expansion; (3) to address the interaction between drivers of global change and recent forest management practices; (4) to obtain more realistic information on the impacts of global change and ecosystem services; (5) to assess forest mortality events associated with climatic extremes; (6) to focus global change research on identifying and managing vulnerable areas; (7) to use the functional traits concept to study resilience after disturbance; (8) to study the relationship between genotypic and phenotypic diversity as a source of forest resilience; (9) to understand the balance between C storage and water resources; (10) to analyse the interplay between landscape‐scale processes and biodiversity conservation; (11) to refine models by including interactions between drivers and socio‐economic contexts; (12) to understand forest–atmosphere feedbacks; (13) to represent key mechanisms linking plant hydraulics with landscape hydrology. Main conclusions (1) The interactive nature of different global change drivers remains poorly understood. (2) There is a critical need for the rapid development of regional‐ and global‐scale models that are more tightly connected with large‐scale experiments, data networks and management practice. (3) More attention should be directed to drought‐related forest decline and the current relevance of historical land use.

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

Toward hemodynamic diagnosis of carotid artery stenosis based on ultrasound image data and computational modeling - Luísa C. Sousa; Catarina F. Castro; Carlos C. António; André Miguel F. Santos; Rosa Maria dos Santos; Pedro Miguel A. C. Castro; Elsa Azevedo; João Manuel R. S. Tavares (Medical & Biological Engineering & Computing, 2014)

Unsteady wall shear stress analysis from image-based computational fluid dynamic aneurysm models under Newtonian and Casson rheological models - Marcelo A. Castro; María C. Ahumada Olivares; Christopher M. Putman; Juan R. Cebral (Medical & Biological Engineering & Computing, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Exploring N-Acylhydrazone Derivatives Against Clinical Resistant Bacterial Strains - Andressa C. Lannes; Bruno Leal; Juliana S. Novais; Viviane Lione; Georgia C. T. S. Monteiro; André L. Lourenço; Plínio C. Sathler; Alessandro K. Jordão; Carlos R. Rodrigues; Lúcio M. Cabral; Anna Claudia Cunha; Vinicius Campos; et al. (Current Microbiology, 2014)

The climate in Zafra from 1750 to 1840: history and description of weather observations - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. A. García; J. M. Vaquero; J. M. Moreno González; J. Castillo Durán (Climatic Change, 2014)

Carrier state induced by oxytetracycline therapy against streptococcosis in N ile tilapia, O reochromis niloticus ( L .) - F C Faria; C A G Leal; G A Carvalho‐Castro; R C Leite; H C P Figueiredo (Journal of Fish Diseases, 2014)

Electrochemical removal of synthetic textile dyes from aqueous solutions using Ti/Pt anode: role of dye structure - Cynthia K. C. Araújo; Gustavo R. Oliveira; Nedja S. Fernandes; Carmem L. P. S. Zanta; Suely Souza Leal Castro; Djalma R. da Silva; Carlos A. Martínez-Huitle (Environmental Science and Pollution Research, 2014)

Phytomanagement of Cd-contaminated soils using maize (Zea mays L.) assisted by plant growth-promoting rhizobacteria - Helena Moreira; Ana P. G. C. Marques; Albina R. Franco; António O. S. S. Rangel; Paula M. L. Castro (Environmental Science and Pollution Research, 2014)

Kinetics and regulation of lactose transport and metabolism in Kluyveromyces lactis JA6 - A. M. Santos; W. B. Silveira; L. G. Fietto; R. L. Brandão; I. M. Castro (World Journal of Microbiology and Biotechnology, 2014)

Chlorophyll and suspended sediment mapping to the Caribbean Sea from rivers in the capital city of the Dominican Republic using ALOS AVNIR-2 data - Yuji Sakuno; Esteban R. Miño; Satoshi Nakai; Hidemi Mutsuda; Tetsuji Okuda; Wataru Nishijima; Rolando Castro; Amarillis García; Rosanna Peña; Marcos Rodríguez; G. Conrado Depratt (Environmental Monitoring and Assessment, 2014)

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

Safety and Health Hazard Observations in Hmong Farming Operations - R. L. Neitzel; J. Krenz; A. B. de Castro (Journal of Agromedicine, 2014)

Early Spanish meteorological records (1780–1850) - F. Domínguez‐Castro; J. M. Vaquero; F. S. Rodrigo; A. M. M. Farrona; M. C. Gallego; R. García‐Herrera; M. Barriendos; A. Sanchez‐Lorenzo (International Journal of Climatology, 2014)
This article summarizes recent efforts on early instrumental data recovery in Spain conducted under the Salvà‐Sinobas project. We have retrieved and digitized more than 100 000 meteorological observations prior to 1850 in Spain. This data set contains measurements of air temperature, atmospheric pressure, wind direction and state of the atmosphere in 16 places located in Iberia and the Balearic Islands. Most of the observations are made on a daily basis. However, monthly and annual information has also been retrieved. The time coverage of the series is not homogeneous, with the earliest records starting in Seville in 1780. Prior to this work only two series were available in Spain (i.e. Cadiz and Barcelona), so this data set represents a great advance in the early data availability for Spain. Due to the lack of metadata in most of the series, their interpretation must be made with caution. © 2013 Royal Meteorological Society

Effect of water restriction on total phenolics and antioxidant properties of Amburana cearensis (Fr. Allem) A.C. Smith cotyledons during seed imbibition - Erica P. L. Pereira; Paulo R. Ribeiro; Marta B. Loureiro; Renato D. de Castro; Luzimar G. Fernandez (Acta Physiologiae Plantarum, 2014)

A new Dasypodini armadillo (Xenarthra: Cingulata) from San Gregorio Formation, Pliocene of Venezuela: affinities and biogeographic interpretations - Mariela C. Castro; Alfredo A. Carlini; Rodolfo Sánchez; Marcelo R. Sánchez-Villagra (The Science of Nature, 2014)

Oxidative stress parameters in blood, liver, and kidney of diabetic rats treated with curcumin and/or insulin - Heloisa Einloft Palma; Patrícia Wolkmer; Miguel Gallio; Marcos M. B. Corrêa; Roberta Schmatz; Gustavo R. Thomé; Luciane B. Pereira; Verônica S. P. Castro; Andréia B. Pereira; Andressa Bueno; Lizielle S. de Oliveira; Debora Rosolen; et al. (Molecular and Cellular Biochemistry, 2014)

Analysis of various physiological salines for heart rate, CNS function, and synaptic transmission at neuromuscular junctions in Drosophila melanogaster larvae - Clara de Castro; Josh Titlow; Zana R. Majeed; Robin L. Cooper (Journal of Comparative Physiology A, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Fractionation of heavy metals and assessment of contamination of the sediments of Lake Titicaca - Luis Fernando Cáceres Choque; Oswaldo E. Ramos Ramos; Sulema N. Valdez Castro; Rigoberto R. Choque Aspiazu; Rocío G. Choque Mamani; Samuel G. Fernández Alcazar; Ondra Sracek; Prosun Bhattacharya (Environmental Monitoring and Assessment, 2013)

Unintended consequences and trade‐offs of fish passage - Robert L McLaughlin; Eric R B Smyth; Theodore Castro‐Santos; Michael L Jones; Marten A Koops; Thomas C Pratt; Luis‐Antonio Vélez‐Espino (Fish and Fisheries, 2013)
We synthesized evidence for unintended consequences and trade‐offs associated with the passage of fishes. Provisioning of fish passageways at dams and dam removals are being carried out increasingly as resource managers seek ways to reduce fragmentation of migratory fish populations and restore biodiversity and nature‐like ecosystem services in tributaries altered by dams. The benefits of provisioning upstream passage are highlighted widely. Possible unwanted consequences and trade‐offs of upstream passage are coming to light, but remain poorly examined and underappreciated. Unintended consequences arise when passage of native and desirable introduced fishes is delayed, undone (fallback), results in patterns of movement and habitat use that reduce D arwinian fitness (e.g. ecological traps), or is highly selective taxonomically and numerically. Trade‐offs arise when passage decisions intended to benefit native species interfere with management decisions intended to control the unwanted spread of non‐native fishes and aquatic invertebrates, or genes, diseases and contaminants carried by hatchery and wild fishes. These consequences and trade‐offs will vary in importance from system to system and can result in large economic and environmental costs. For some river systems, decisions about how to manage fish passage involve substantial risks and could benefit from use of a formal, structured process that allows transparent, objective and, where possible, quantitative evaluation of these risks. Such a process can also facilitate the design of an adaptive framework that provides valuable insights into future decisions.

Temperature Performance of Different Pervious Pavements: Rainwater Harvesting for Energy Recovery Purposes - Amaya V. Novo; Joseba R. Bayon; Daniel Castro-Fresno; Jorge Rodriguez-Hernandez (Water Resources Management, 2013)

Body live weight and milk production parameters in the Majorera and Palmera goat breeds from the Canary Islands: influence of weight loss - Joana R. Lérias; Lorenzo E. Hernández-Castellano; Antonio Morales-delaNuez; Susana S. Araújo; Noemí Castro; Anastasio Argüello; Juan Capote; André M. Almeida (Tropical Animal Health and Production, 2013)

Generating anatomical models of the heart and the aorta from medical images for personalized physiological simulations - J. Weese; A. Groth; H. Nickisch; H. Barschdorf; F. M. Weber; J. Velut; M. Castro; C. Toumoulin; J. L. Coatrieux; M. De Craene; G. Piella; C. Tobón-Gomez; et al. (Medical & Biological Engineering & Computing, 2013)

Detection of a new Os HV ‐1 DNA strain in the healthy P acific oyster, C rassostrea gigas Thunberg, from the G ulf of C alifornia - J M Grijalva‐Chon; R Castro‐Longoria; J Ramos‐Paredes; T L Enríquez‐Espinoza; F Mendoza‐Cano (Journal of Fish Diseases, 2013)

Genetic map of the primocane-fruiting and thornless traits of tetraploid blackberry - P. Castro; E. T. Stafne; J. R. Clark; K. S. Lewers (Theoretical and Applied Genetics, 2013)

Multilocus genetic diversity and historical biogeography of the endemic wall lizard from I biza and F ormentera, P odarcis pityusensis ( S quamata: L acertidae) - V. Rodríguez; R. P. Brown; B. Terrasa; V. Pérez‐Mellado; J. A. Castro; A. Picornell; M. M. Ramon (Molecular Ecology, 2013)
Two monophyletic sister species of wall lizards inhabit the two main groups of B alearic I slands: P odarcis lilfordi from islets and small islands around M allorca and M enorca and P odarcis pityusensis from I biza, F ormentera and associated islets. Genetic diversity within the endangered P . lilfordi has been well characterized, but P . pityusensis has not been studied in depth. Here, 2430 bp of mt DNA and 15 microsatellite loci were analysed from P . pityusensis populations from across its natural range. Two main genetic groupings were identified, although geographical structuring differed slightly between the mt DNA and the nuclear loci. In general, individuals from islets/islands adjacent to the main island of I biza were genetically distinct from those from F ormentera and the associated F reus islands for both mt DNA and the nuclear loci. However, most individuals from the island of I biza were grouped with neighbouring islets/islands for nuclear loci, but with F ormentera and F reus islands for the mitochondrial locus. A time‐calibrated B ayesian tree was constructed for the principal mitochondrial lineages within the B alearics, using the multispecies coalescent model, and provided statistical support for divergence of the two main P . pityusensis lineages 0.111–0.295 Ma. This suggests a mid‐late P leistocene intraspecific divergence, compared with an early P leistocene divergence in P . lilfordi , and postdates some major increases in sea level between 0.4 and 0.6 Ma, which may have flooded F ormentera. The program IM a2 provided a posterior divergence time of 0.089–0.221 Ma, which was similar to the multispecies coalescent tree estimate. More significantly, it indicated low but asymmetric effective gene copy migration rates, with higher migration from F ormentera to I biza populations. Our findings suggest that much of the present‐day diversity may have originated from a late P leistocene colonization of one island group from the other, followed by allopatric divergence of these populations. Subsequent gene flow between these insular groups seems likely to be explained by recent human introductions. Two evolutionary significant units can be defined for P . pityusensis but these units would need to exclude the populations that have been the subjects of recent admixture.

Region-specific regulation of 5-HT1B receptors in the rat brain by chronic venlafaxine treatment - R. Vidal; A. Diaz; A. Pazos; E. Castro (Psychopharmacology, 2013)

Evaluation of an ensemble of regional climate model simulations over South America driven by the ERA-Interim reanalysis: model performance and uncertainties - Silvina A. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; J. Marengo; N. L. Pessacg; A. R. C. Remedio; S. C. Chou; H. Berbery; H. Le Treut; M. de Castro; et al. (Climate Dynamics, 2013)

Tissue expression of PPAR-alpha isoforms in Scophthalmus maximus and transcriptional response of target genes in the heart after exposure to WY-14643 - R. Urbatzka; S. Galante-Oliveira; E. Rocha; L. F. C. Castro; I. Cunha (Fish Physiology and Biochemistry, 2013)

Red deer (Cervus elaphus) as a host for the cattle tick Rhipicephalus microplus (Acari: Ixodidae) in Yucatan, Mexico - R. I. Rodríguez-Vivas; M. M. Ojeda-Chi; J. A. Rosado-Aguilar; I. C. Trinidad-Martínez; J. F. J. Torres-Acosta; V. Ticante-Perez; J. M. Castro-Marín; C. A. Tapia-Moo; G. Vázquez-Gómez (Experimental and Applied Acarology, 2013)

Concentration of trace metals in sediments and soils from protected lands in south Florida: background levels and risk evaluation - Joffre E. Castro; Adolfo M. Fernandez; Valentina Gonzalez-Caccia; Piero R. Gardinali (Environmental Monitoring and Assessment, 2013)

Empirical ground-motion relations using moderate earthquakes recorded by Medellín–Aburrá Valley (Colombia) strong-motion networks - Gina P. Villalobos-Escobar; Raúl R. Castro (Bulletin of Earthquake Engineering, 2013)

Diversity of Archaea in Brazilian savanna soils - E. Catão; A. P. Castro; C. C. Barreto; R. H. Krüger; C. M. Kyaw (Archives of Microbiology, 2013)

Are lizards feeling the heat? A tale of ecology and evolution under two temperatures - Shai Meiri; Aaron M. Bauer; Laurent Chirio; Guarino R. Colli; Indraneil Das; Tiffany M. Doan; Anat Feldman; Fernando‐Castro Herrera; Maria Novosolov; Panayiotis Pafilis; Daniel Pincheira‐Donoso; Gary Powney; et al. (Global Ecology and Biogeography, 2013)
Aim Temperature influences most components of animal ecology and life history – but what kind of temperature? Physiologists usually examine the influence of body temperatures, while biogeographers and macroecologists tend to focus on environmental temperatures. We aim to examine the relationship between these two measures, to determine the factors that affect lizard body temperatures and to test the effect of both temperature measures on lizard life history. Location World‐wide. Methods We used a large (861 species) global dataset of lizard body temperatures, and the mean annual temperatures across their geographic ranges to examine the relationships between body and mean annual temperatures. We then examined factors influencing body temperatures, and tested for the influence of both on ecological and life‐history traits while accounting for the influence of shared ancestry. Results Body temperatures and mean annual temperatures are uncorrelated. However, accounting for activity time (nocturnal species have low body temperatures), use of space (fossorial and semi‐aquatic species are ‘colder’), insularity (mainland species are ‘hotter’) and phylogeny, the two temperatures are positively correlated. High body temperatures are only associated with larger hatchlings and increased rates of biomass production. Annual temperatures are positively correlated with clutch frequency and annual longevity, and negatively correlated with clutch size, age at first reproduction and longevity. Main conclusions Lizards with low body temperatures do not seem to have ‘slower’ life‐history attributes than species with high body temperatures. The longer seasons prevalent in warm regions, and physiological processes that operate while lizards are inactive (but warm enough), make environmental temperatures better predictors of lizard life‐history variation than body temperatures. This surprisingly greater effect of environmental temperatures on lizard life histories hints that global warming may have a profound influence on lizard ecology and evolution.

Induction of capsaicinoid accumulation in placental tissues of Capsicum chinense Jacq. requires primary ammonia assimilation - Wendy del R. Ancona-Escalante; Fray M. Baas-Espinola; Lizbeth A. Castro-Concha; Felipe A. Vázquez-Flota; Marcela Zamudio-Maya; María L. de Miranda-Ham (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Concentration of ascorbic acid and antioxidant response in early life stages of Engraulis ringens and zooplankton during the spawning seasons of 2006–2009 off central Chile - M. C. Krautz; L. R. Castro; M. González; A. Llanos-Rivera; I. Montes; H. González; R. R. González; J. C. Vera (Marine Biology, 2013)

The first meteorological measurements in the Iberian Peninsula: evaluating the storm of November 1724 - F. Domínguez-Castro; R. M. Trigo; J. M. Vaquero (Climatic Change, 2013)

The dimensionality of ecological networks - Anna Eklöf; Ute Jacob; Jason Kopp; Jordi Bosch; Rocío Castro‐Urgal; Natacha P. Chacoff; Bo Dalsgaard; Claudio de Sassi; Mauro Galetti; Paulo R. Guimarães; Silvia Beatriz Lomáscolo; Ana M. Martín González; et al. (Ecology Letters, 2013)
How many dimensions (trait‐axes) are required to predict whether two species interact? This unanswered question originated with the idea of ecological niches, and yet bears relevance today for understanding what determines network structure. Here, we analyse a set of 200 ecological networks, including food webs, antagonistic and mutualistic networks, and find that the number of dimensions needed to completely explain all interactions is small (

Metabolic responses of the squat lobster (Pleuroncodes monodon) larvae to low oxygen concentration - B. Yannicelli; K. Paschke; R. R. González; L. R. Castro (Marine Biology, 2013)

Assessment of genetic diversity and phylogenetic relationships in Asparagus species related to Asparagus officinalis - P. Castro; J. Gil; A. Cabrera; R. Moreno (Genetic Resources and Crop Evolution, 2013)

Population Fluctuation and Damage Caused by Phytophagous Mites on Three Rubber Tree Clones - E B Castro; F M Nuvoloni; C R R Mattos; R J F Feres (Neotropical Entomology, 2013)

Effect of diflubenzuron on the development of Pinus pinaster seedlings inoculated with the ectomycorrhizal fungus Pisolithus tinctorius - Miguel A. Ramos; Nadine R. Sousa; Albina R. Franco; Vítor Costa; Rui S. Oliveira; Paula M. L. Castro (Environmental Science and Pollution Research, 2013)

Can the red palm mite threaten the Amazon vegetation? - Manoel G. C. Gondim; Tatiane M. M. G. Castro; Alberto L. Marsaro; Denise Navia; José W. S. Melo; Peterson R. Demite; Gilberto J. de Moraes (Systematics and Biodiversity, 2012)

Performance of a multi-RCM ensemble for South Eastern South America - A. F. Carril; C. G. Menéndez; A. R. C. Remedio; F. Robledo; A. Sörensson; B. Tencer; J.-P. Boulanger; M. de Castro; D. Jacob; H. Le Treut; L. Z. X. Li; O. Penalba; et al. (Climate Dynamics, 2012)

Epidemiological aspects of HCV infection in HIV-infected individuals in Piauí State, Northeast Brazil - Aldemir B. Oliveira-Filho; Evaldo H. Oliveira; Jairo A. A. Castro; Letiano V. Silva; Antonio C. R. Vallinoto; José Alexandre R. Lemos (Archives of Virology, 2012)

Connection between NAO, weather types and precipitation in León, Spain (1948–2008) - S. Fernández‐González; S. del Río; A. Castro; A. Penas; M. Fernández‐Raga; A. I. Calvo; R. Fraile (International Journal of Climatology, 2012)
The variability of winter precipitation in the west of the Iberian Peninsula is strongly affected by the North Atlantic Oscillation (NAO). This study focuses on identifying the relationship that exists between precipitation registered in the city of León (in northwestern Spain), the NAO index and the associated weather type during the same period. In order to achieve this objective, the prevailing weather type has been calculated for each day in León from January 1948 to March 2009, using the objective Lamb Weather Types classification method. The most significant results appear in winter (from December to March). During these months an increase has been observed in the frequency of ‘anticyclonic’ weather type (A) (very dry), and a decrease in the ‘cyclonic’ (C), ‘south‐westerly’ (SW) and ‘westerly’ (W) types (the three rainiest weather types). The positive trend in the NAO index could be the main cause of the decrease in the frequency of the three rainiest weather types (C, SW and W) and therefore, responsible for the relevant decline in winter precipitation observed in the city of León. The high correlation coefficients between the NAO index, the frequency of the three rainiest weather types and winter precipitation suggests an interesting method to forecast rainfall. Using a binary logistic regression model, a downscaling model for daily precipitation has been obtained based on the weather types and the NAO index. The daily results obtained for the winter months are good (TSS = 0.64) bearing in mind that only sea level pressure data were used in the logistic model. Copyright © 2011 Royal Meteorological Society

Effect of Storage Conditions on Total Volatile Base Nitrogen Determinations in Fish Muscle Extracts - P. Castro; R. Millán; J. C. Penedo; E. Sanjuán; A. Santana; M. J. Caballero (Journal of Aquatic Food Product Technology, 2012)

Mycorrhizal symbiosis affected by different genotypes of Pinus pinaster - Nadine R. Sousa; Miguel A. Ramos; Albina R. Franco; Rui S. Oliveira; Paula M. L. Castro (Plant and Soil, 2012)

Tauroursodeoxycholic Acid Prevents MPTP-Induced Dopaminergic Cell Death in a Mouse Model of Parkinson’s Disease - M. Castro-Caldas; A. Neves Carvalho; E. Rodrigues; C. J. Henderson; C. R. Wolf; C. M. P. Rodrigues; M. J. Gama (Molecular Neurobiology, 2012)

Score to identify the severity of adult patients with influenza A (H1N1) 2009 virus infection at hospital admission - A. Capelastegui; J. M. Quintana; A. Bilbao; P. P. España; O. Garin; J. Alonso; J. Astray; R. Cantón; J. Castilla; A. Castro; M. Delgado-Rodríguez; P. Godoy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Diet and exercise training reduce blood pressure and improve autonomic modulation in women with prehypertension - Allan R. K. Sales; Bruno M. Silva; Fabricia J. Neves; Natália G. Rocha; Renata F. Medeiros; Renata R. T. Castro; Antonio C. L. Nóbrega (European Journal of Applied Physiology, 2012)

Chiral pharmaceuticals in the environment - Ana R. Ribeiro; Paula M. L. Castro; Maria E. Tiritan (Environmental Chemistry Letters, 2012)

Net primary productivity, upwelling and coastal currents in the Gulf of Ulloa, Baja California, México - E. González-Rodríguez; A. Trasviña-Castro; G. Gaxiola-Castro; L. Zamudio; R. Cervantes-Duarte (Ocean Science, 2012)
The Gulf of Ulloa, a highly productive area off the western coast of the Baja California Peninsula, is examined for five successive years (2003–2007) by using satellite data and seasonal net primary productivity (NPP) estimates obtained from a vertical generalised production model. The results identify that northwestern winds blow parallel to the coast throughout the year. However, highest NPP occurs from March to June. During this period, an equatorward coastal current transports water from neighbouring upwelling areas to the northern Gulf of Ulloa and in combination with local upwelling, which injects nutrients into the euphotic zone, produce the observed increase in NPP. The opposite situation occurs in late summer when a warm poleward current of tropical characteristics arrives and inhibits the productivity in the whole region and generates the yearly lowest NPP levels. Our findings reveal the importance of lateral advection in the modulation of the primary productivity in this subtropical upwelling region.

Adenosine Deaminase Activity in Serum and Lymphocytes of Rats Infected with Sporothrix schenckii - Verônica S. P. Castro; Victor C. Pimentel; Aleksandro S. Da Silva; Gustavo R. Thomé; Patrícia Wolkmer; Jorge L. C. Castro; Márcio M. Costa; Cássia B. da Silva; Daniele C. Oliveira; Sydney H. Alves; Maria R. C. Schetinger; Sonia T. A. Lopes; et al. (Mycopathologia, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Obstructive Sleep Apnea Severity Correlates with Cellular and Plasma Oxidative Stress Parameters and Affective Symptoms - C. M. R. Franco; A. M. J. Lima; L. Ataíde; O. G. Lins; C. M. M. Castro; A. A. Bezerra; M. F. de Oliveira; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

Limits of pine forest distribution at the treeline: herbivory matters - A. Herrero; R. Zamora; J. Castro; J. A. Hódar (Plant Ecology, 2012)

Evolutionary Implications of Dental Eruption in Dasypus (Xenarthra) - Martin R. Ciancio; Mariela C. Castro; Fernando C. Galliari; Alfredo A. Carlini; Robert J. Asher (Journal of Mammalian Evolution, 2012)

Concentration of ascorbic acid and innate immune effectors in Engraulis ringens and Strangomera bentincki during their main spawning period (2007–2008) in the Humboldt current system off Chile - M. C. Krautz; L. R. Castro; M. González; J. C. Vera; H. E. González (Marine Biology, 2012)

Impact of water quality on bacterioplankton assemblage along Cértima River Basin (central western Portugal) assessed by PCR–DGGE and multivariate analysis - Daniela R. de Figueiredo; Raquel V. Ferreira; Mário Cerqueira; Teresa Condesso de Melo; Mário J. Pereira; Bruno B. Castro; António Correia (Environmental Monitoring and Assessment, 2012)

Functional dissimilarity of melanomacrophage centres in the liver and spleen from females of the teleost fish Prochilodus argenteus - H. J. Ribeiro; M. S. Procópio; J. M. M. Gomes; F. O. Vieira; R. C. Russo; K. Balzuweit; H. Chiarini-Garcia; Antonio Carlos Santana Castro; E. Rizzo; José Dias Corrêa (Cell and Tissue Research, 2011)

Variability of the monthly European temperature and its association with the Atlantic sea‐surface temperature from interannual to multidecadal scales - S. R. Gámiz‐Fortis; M. J. Esteban‐Parra; D. Pozo‐Vázquez; Y. Castro‐Díez (International Journal of Climatology, 2011)
The relationships between the main patterns of variability of the Atlantic sea‐surface temperatures (SSTs) and the European land‐surface temperatures (LSTs) at interannual‐to‐multidecadal time scales are investigated along the period 1872–2004. Principal component analysis (PCA) is used firstly to obtain the main spatio‐temporal patterns of variability of the LSTs and SSTs. Singular Spectral Analysis (SSA) is then used to decompose the time series associated with these patterns into nonlinear trends and quasi‐periodic oscillations, searching for common oscillatory modes to the SSTs and LSTs. The potential predictability of the LSTs based on the SSTs is also analysed. Regarding the SSA results, three robust oscillations of periods around 13.7, 7.5 and 5.2 years, present both in the Atlantic SSTs and north‐western European LSTs, were isolated. These oscillations were found to be associated mainly with a quadripolar SST pattern in the North Atlantic region, usually related to the North Atlantic Oscillation (NAO) atmospheric mode of variability. The predictability study revealed that the SSTs of the Atlantic Ocean are able to account for about 12% of the north‐western European LSTs variance. Additionally, an oscillatory component with period around 3.6 years was identified, but no significant connection between SST and LST was found for this mode. In addition, at this time scale, we find that the El Niño‐Southern Oscillation (ENSO) is leading the Atlantic SST quadripolar pattern by 6 months. Finally, the analysis of the nonlinear trends showed the presence of oscillations with periods around 60–100 years, both in the SSTs and LSTs. At these later time scales, our results reveal that the multidecadal behaviour of the southern European LSTs is related to Atlantic Multidecadal Oscillation (AMO) during the period 1872–1940, unlike the northern and eastern European LSTs, while, during the period 1941–2004, the AMO sign seems to be present in whole Europe. Copyright © 2010 Royal Meteorological Society

Location of Moderate-Sized Earthquakes Recorded by the NARS–Baja Array in the Gulf of California Region Between 2002 and 2006 - Raul R. Castro; Arturo Perez-Vertti; Ignacio Mendez; Antonio Mendoza; Luis Inzunza (Pure and Applied Geophysics, 2011)

Fisheries and trade of seahorses in Brazil: historical perspective, current trends, and future directions - Ierecê L. Rosa; Tacyana P. R. Oliveira; Frederico M. Osório; Luiz E. Moraes; André L. C. Castro; Glaura M. L. Barros; Rômulo R. N. Alves (Biodiversity and Conservation, 2011)

Phylotype diversity in a benthic cyanobacterial mat community on King George Island, maritime Antarctica - Cecilia Callejas; Paul R. Gill; Ana I. Catalán; Gastón Azziz; Susana Castro-Sowinski; Silvia Batista (World Journal of Microbiology and Biotechnology, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Spinal cord direct current stimulation: finite element analysis of the electric field and current density - Gabriel R. Hernández-Labrado; José L. Polo; Elisa López-Dolado; Jorge E. Collazos-Castro (Medical & Biological Engineering & Computing, 2011)

Polymorphic microsatellite loci for the Balearic Island Lizard Podarcis lilfordi (Squamata: Lacertidae) - P. Bloor; V. Rodríguez; B. Terrasa; R. P. Brown; V. Pérez-Mellado; J. A. Castro; A. Picornell; M. M. Ramon (Conservation Genetics Resources, 2011)

Infection and mortality of Penaeus vannamei at extreme salinities when challenged with Mexican yellow head virus - F Navarro‐Nava; R Castro‐Longoria; J M Grijalva‐Chon; J Ramos‐Paredes; J De la Rosa‐Vélez (Journal of Fish Diseases, 2011)

Principal components analysis to evaluate ventilatory variability: comparison of athletes and sedentary men - R. R. T. Castro; M. Magini; S. Pedrosa; A. R. K. Sales; A. C. L. Nóbrega (Medical & Biological Engineering & Computing, 2011)

Use of Raptors for Biomonitoring of Heavy Metals: Gender, Age and Tissue Selection - I. Castro; J. R. Aboal; J. A. Fernández; A. Carballeira (Bulletin of Environmental Contamination and Toxicology, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Acute Toxicity and Effects Analysis of Endosulfan Sulfate to Freshwater Fish Species - John F. Carriger; Tham C. Hoang; Gary M. Rand; Piero R. Gardinali; Joffre Castro (Archives of Environmental Contamination and Toxicology, 2011)

Impact of non-selective fungicides on the growth and production of ochratoxin A by Aspergillus ochraceus and A. carbonarius in barley-based medium - Eva M. Mateo; F.M. Valle-Algarra; R. Mateo-Castro; M. Jiménez (Food Additives & Contaminants: Part A, 2011)

Anti-HIV Drugs Nevirapine and Efavirenz Affect Anxiety-Related Behavior and Cognitive Performance in Mice - Pedro R. T. Romão; Joelson C. Lemos; Jeverson Moreira; Gisele de Chaves; Morgana Moretti; Adalberto A. Castro; Vanessa M. Andrade; Carina R. Boeck; João Quevedo; Elaine C. Gavioli (Neurotoxicity Research, 2011)

Management of nursery practices for efficient ectomycorrhizal fungi application in the production of Quercus ilex - Rui S. Oliveira; Albina R. Franco; Miroslav Vosátka; Paula M. L. Castro (Symbiosis, 2010)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Cytogenetics of Alismataceae and Limnocharitaceae: CMA/DAPI banding and 45S rDNA sites - L. L. Feitoza; M. I. G. Martins; A. A. J. F. Castro; L. P. Félix; R. Carvalho (Plant Systematics and Evolution, 2010)

Haplotype analyses, mechanism and evolution of common double mutants in the human LDL receptor gene - M. T. Tejedor; A. Cenarro; D. Tejedor; M. Stef; R. Mateo-Gallego; I. de Castro; A. L. García-Otin; L. V. Monteagudo; F. Civeira; M. Pocovi (Molecular Genetics and Genomics, 2010)

Endosulfan and its metabolite, endosulfan sulfate, in freshwater ecosystems of South Florida: a probabilistic aquatic ecological risk assessment - Gary M. Rand; John F. Carriger; Piero R. Gardinali; Joffre Castro (Ecotoxicology, 2010)

Species identification using a small nuclear gene fragment: application to sympatric wild carnivores from South-western Europe - R. Oliveira; D. Castro; R. Godinho; G. Luikart; P. C. Alves (Conservation Genetics, 2010)

Effects of dose and period of sewage sludge application on soil, tree and pasture components in a Pinus radiata D. Don silvopastoral system - A. Rigueiro-Rodríguez; S. Castro; M. R. Mosquera-Losada (Agroforestry Systems, 2010)

Changes in metabolic substrates during early development in anchoveta Engraulis ringens (Jenyns 1842) in the Humboldt Current - M. C. Krautz; S. Vásquez; L. R. Castro; M. González; A. Llanos-Rivera; S. Pantoja (Marine Biology, 2010)

Genetic, Biochemical, and Individual Responses of the Teleost Fish Carassius auratus to Uranium - Joana Lourenço; B. B. Castro; R. Machado; B. Nunes; S. Mendo; F. Gonçalves; R. Pereira (Archives of Environmental Contamination and Toxicology, 2010)

Antioxidant system activation by mercury in Pfaffia glomerata plantlets - N. S. Calgaroto; G. Y. Castro; D. Cargnelutti; L. B. Pereira; J. F. Gonçalves; L. V. Rossato; F. G. Antes; V. L. Dressler; E. M. M. Flores; M. R. C. Schetinger; F. T. Nicoloso (BioMetals, 2010)

Blockade of adenosine A2A receptor counteracts neuropeptide-S-induced hyperlocomotion in mice - Carina R. Boeck; Caroline Martinello; Adalberto A. de Castro; Morgana Moretti; Tiago dos Santos Casagrande; Remo Guerrini; Girolamo Calo’; Elaine C. Gavioli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Frequency distribution of XbaIG > T and HaeIIIT > C GLUT1 polymorphisms among different Brazilian ethnic groups - G. C. S. Costa; L. C. J. Alcantara; R. Azevedo; G. Muricy; S. H. Kashima; D. T. Covas; B. Galvão-Castro; S. R. Gadelha (Molecular Biology Reports, 2010)

Effects of ECF-Kraft pulp mill effluent treated with fungi (Rhizopus oryzae) on reproductive steroids and liver CYP1A of exposed goldfish (Carassius auratus) - M. S. Diniz; I. Peres; L. Castro; A. C. Freitas; T. A. P. Rocha-Santos; P. M. Costa; R. Pereira; A. C. Duarte (Ecotoxicology, 2009)

Leishmania amazonensis Growth Inhibitors: Biological and Theoretical Features of Sulfonamide 4-Methoxychalcone Derivatives - Alessandra M. T. Souza; Helena C. Castro; Monique A. Brito; Carla R. Andrighetti-Fröhner; Uiaran Magalhães; Kely N. Oliveira; Daniela Gaspar-Silva; Letícia K. Pacheco; Antônio C. Joussef; Mário Steindel; Cláudia M. O. Simões; Dilvani O. Santos; et al. (Current Microbiology, 2009)

Relationship between geomorphology and contamination with weathered hydrocarbons in an old river levee/marsh association - R. H. Adams; D. Olán-Castro; F. J. Guzmán-Osorio; I. J. Diaz-Ramírez (International Journal of Environmental Science and Technology, 2009)

Haplotype and quantitative transcript analyses of Portuguese breast/ovarian cancer families with the BRCA1 R71G founder mutation of Galician origin - Catarina Santos; Ana Peixoto; Patrícia Rocha; Ana Vega; Maria José Soares; Nuno Cerveira; Susana Bizarro; Manuela Pinheiro; Deolinda Pereira; Helena Rodrigues; Fernando Castro; Rui Henrique; et al. (Familial Cancer, 2009)

2D versus 3D in the kinematic analysis of the horse at the trot - F. Miró; R. Santos; J. L. Garrido-Castro; A. M. Galisteo; R. Medina-Carnicer (Veterinary Research Communications, 2009)

High Ag-NOR-site variation associated to a secondary contact in brown trout from the Iberian Peninsula - P. Martínez; J. Castro; B. G. Pardo; C. Bouza; M. Hermida; R. Vilas (Genetica, 2009)

A New Developmental Toxicity Test for Pelagic Fish Using Anchoveta (Engraulis ringens J.) - A. Llanos-Rivera; L. R. Castro; J. Silva; E. Bay-Schmith (Bulletin of Environmental Contamination and Toxicology, 2009)

Low level and sub-chronic exposure to methylmercury induces hypertension in rats: nitric oxide depletion and oxidative damage as possible mechanisms - Denise Grotto; Michele M. de Castro; Gustavo R. M. Barcelos; Solange C. Garcia; Fernando Barbosa (Archives of Toxicology, 2009)

First isolation of Tenacibaculum maritimum from wedge sole, Dicologoglossa cuneata (Moreau) - J R López; S Núñez; B Magariños; N Castro; J I Navas; R De La Herran; A E Toranzo (Journal of Fish Diseases, 2009)
The first isolation of Tenacibaculum maritimum from wedge sole, Dicologoglossa cuneata, is reported. The pathogen was recovered from ulcers of cultured fish, from three different outbreaks. The six isolates obtained were biochemically and serologically characterized and diagnosis was confirmed by polymerase chain reaction using specific primers and partial 16S rRNA gene sequencing. The isolates constituted a homogeneous phenotypic group; however, they belong to two of the different serotypes described within this species. A virulence evaluation of the isolates using Wedge sole fry was also performed.

Cytogenetics of Alismatales s.s.: chromosomal evolution and C-banding - L. L. Feitoza; L. P. Felix; A. A. J. F. Castro; R. Carvalho (Plant Systematics and Evolution, 2009)

Toxicity evaluation of three pesticides on non-target aquatic and soil organisms: commercial formulation versus active ingredient - Joana L. Pereira; Sara C. Antunes; Bruno B. Castro; Catarina R. Marques; Ana M. M. Gonçalves; Fernando Gonçalves; Ruth Pereira (Ecotoxicology, 2009)

Silage from maize (Zea mays), annual ryegrass (Lolium multiflorum) or their mixture in the dry season feeding of grazing dairy cows in small-scale dairy production systems in the Highlands of Mexico - J. P. Anaya-Ortega; G. Garduño-Castro; A. Espinoza-Ortega; R. Rojo-Rubio; C. M. Arriaga-Jordán (Tropical Animal Health and Production, 2009)

Chemical composition of urban aerosols in Toulouse, France during CAPITOUL experiment - A. I. Calvo; V. Pont; C. Liousse; B. Dupré; A. Mariscal; C. Zouiten; E. Gardrat; P. Castera; C. G. Lacaux; A. Castro; R. Fraile (Meteorology and Atmospheric Physics, 2008)

Molecular epidemiology of hepatitis B virus in an isolated Afro-Brazilian community - A. R. C. Motta-Castro; R. M. B. Martins; N. M. Araujo; C. Niel; G. B. Facholi; B. V. Lago; F. C. A. Mello; S. A. Gomes (Archives of Virology, 2008)

Detection of the yellow‐head virus (YHV) in wild blue shrimp, Penaeus stylirostris , from the Gulf of California and its experimental transmission to the Pacific white shrimp, Penaeus vannamei - R Castro‐Longoria; N Quintero‐Arredondo; J M Grijalva‐Chon; J Ramos‐Paredes (Journal of Fish Diseases, 2008)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

Inhibition of Ca2+ influx by surfactant in NR8383 alveolar macrophages - R. Castro; X. H. Sun; X.-B. Liu; J. R. Martinez; G. H. Zhang (Inflammation Research, 2008)

Agrobacterium-mediated genetic transformation of Prunus salicina - Carolina Urtubia; Jessica Devia; Álvaro Castro; Pablo Zamora; Carlos Aguirre; Eduardo Tapia; Paola Barba; Paola Dell`Orto; Michael R. Moynihan; César Petri; Ralph Scorza; Humberto Prieto (Plant Cell Reports, 2008)

Body-wave Attenuation in the Region of Garda, Italy - Raúl R. Castro; Marco Massa; Paolo Augliera; Francesca Pacor (Pure and Applied Geophysics, 2008)

Temperature effects on the anchoveta Engraulis ringens egg development: do latitudinal differences occur? - E. Tarifeño; M. Carmona; A. Llanos-Rivera; L. R. Castro (Environmental Biology of Fishes, 2008)

Cloning and expression of trypanothione reductase from a New World Leishmania species - Denise Barçante Castro-Pinto; Marcelo Genestra; Gustavo B. Menezes; Mariana Waghabi; Antonio Gonçalves; Catarina De Nigris Del Cistia; Carlos Mauricio R. Sant’Anna; Leonor L. Leon; Leila Mendonça-Lima (Archives of Microbiology, 2008)

Immunosuppressive properties of surfactant in alveolar macrophage NR8383 - J. Kerecman; S. B. Mustafa; M. M. Vasquez; P. S. Dixon; R. Castro (Inflammation Research, 2008)

Vaccination of turbot, Psetta maxima (L.), against the protozoan parasite Philasterides dicentrarchi : effects on antibody production and protection - M L Sanmartín; A Paramá; R Castro; S Cabaleiro; J Leiro; J Lamas; J L Barja (Journal of Fish Diseases, 2008)
The efficacy of a vaccine against the fish pathogen Philasterides dicentrarchi was evaluated in turbot by measuring the production of specific antibodies and duration of protection. Four groups of turbot were vaccinated twice, on days 0 and 30, with phosphate‐buffered saline, mineral oil adjuvant, antigen or antigen plus adjuvant. Specific serum antibodies were determined on day 0 and 1 month after the first and the second vaccinations. Protection was evaluated 1 month after the first vaccination and 1 and 5 months after the second vaccination. Serum antibody titres, measured by enzyme‐linked immunosorbent assay, and protection, assessed by challenges, increased significantly 1 month after the second vaccination in the group injected with antigen plus adjuvant and the protection lasted for at least a further 5 months in this group. The relative protection was 77% and 66% 1 and 5 months after the second vaccination, respectively. Administration of antigen or adjuvant separately had no effect on antibody response or protection. The results indicate that emulsion containing antigen plus adjuvant induced durable protection against P. dicentrarchi after the administration of the two vaccinations, and that this preparation can be used as a vaccine against the pathogen.

Population genetic structure of Earth's largest fish, the whale shark ( Rhincodon typus ) - A. L. F. CASTRO; B. S. STEWART; S. G. WILSON; R. E. HUETER; M. G. MEEKAN; P. J. MOTTA; B. W. BOWEN; S. A. KARL (Molecular Ecology, 2007)
Large pelagic vertebrates pose special conservation challenges because their movements generally exceed the boundaries of any single jurisdiction. To assess the population structure of whale sharks ( Rhincodon typus ), we sequenced complete mitochondrial DNA control regions from individuals collected across a global distribution. We observed 51 single site polymorphisms and 8 regions with indels comprising 44 haplotypes in 70 individuals, with high haplotype ( h = 0.974 ± 0.008) and nucleotide diversity (π = 0.011 ± 0.006). The control region has the largest length variation yet reported for an elasmobranch (1143–1332 bp). Phylogenetic analyses reveal no geographical clustering of lineages and the most common haplotype was distributed globally. The absence of population structure across the Indian and Pacific basins indicates that oceanic expanses and land barriers in Southeast Asia are not impediments to whale shark dispersal. We did, however, find significant haplotype frequency differences (amova, F ST = 0.107, P

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Culture of the histophagous ciliate Philasterides dicentrarchi (Ciliophora: Scuticociliatia) in fish tissues - R Castro; A Paramá; J L Barja; J Leiro; M L Sanmartin; J Lamas (Journal of Fish Diseases, 2007)

Toxicological evaluation of genetically modified cotton (Bollgard®) and Dipel® WP on the non-target soil mite Scheloribates praeincisus (Acari: Oribatida) - Anibal R. Oliveira; Thiago R. Castro; Deise M. F. Capalbo; Italo Delalibera (Experimental and Applied Acarology, 2007)

Interspecific differentiation and intraspecific substructure in two closely related clupeids with extensive hybridization, Alosa alosa and Alosa fallax - P. Alexandrino; R. Faria; D. Linhares; F. Castro; M. Le Corre; R. Sabatié; J. L. Baglinière; S. Weiss (Journal of Fish Biology, 2006)
In this study, the evolutionary relationships within and among populations of European shads, Alosa alosa and Alosa fallax , was investigated. Screening of allelic variation across eight allozyme loci and sequencing 448 bp of the mtDNA cytochrome b gene in 14 rivers throughout the range of the species supported that the two taxa were independent lineages (1·3% net nucleotide divergence) despite extensive hybridization. Genetic diversity and structure was considerably higher in A. fallax than A. alosa and the former species revealed evidence of distinct lineages in the Mediterranean and Atlantic basins. A Bayesian clustering approach combined with gill raker counts verified that individuals of the two species could be assigned to their parent group with relatively high confidence. Evaluation of hybridization in the Lima and Mondego Rivers in Portugal provided evidence that introgression is extensive but is not currently obscuring (through hybrid swarming) the diagnosability of the two species.

Sensitivity studies of the RegCM3 simulation of summer precipitation, temperature and local wind field in the Caribbean Region - D. Martínez-Castro; R. Porfirio da Rocha; A. Bezanilla-Morlot; L. Alvarez-Escudero; J. P. Reyes-Fernández; Y. Silva-Vidal; R. W. Arritt (Theoretical and Applied Climatology, 2006)

Ultrastructure and germination of Vitis vinifera cv. Loureiro pollen - I. Abreu; I. Costa; M. Oliveira; M. Cunha; R. de Castro (Protoplasma, 2006)

A continental scale evaluation of the role of limpet grazing on rocky shores - Ross A. Coleman; Antony J. Underwood; Lisandro Benedetti-Cecchi; Per Åberg; Francisco Arenas; Julio Arrontes; João Castro; Richard G. Hartnoll; Stuart R. Jenkins; José Paula; Paolo Della Santina; Stephen J. Hawkins (Oecologia, 2006)

Apoptotic effect of fludarabine is independent of expression of IAPs in B-cell chronic lymphocytic leukemia - K. L. Silva; D. V. Vasconcellos; E. D. de Paula Castro; A. M. Coelho; R. Linden; R. C. Maia (Apoptosis, 2006)

Does the Gradualness of Leaf Shedding Govern Nutrient Resorption from Senescing Leaves in Mediterranean Woody Plants? - R. Milla; P. Castro-Díez; M. Maestro-Martínez; G. Montserrat-Martí (Plant and Soil, 2005)

Studies on the diversity of arbuscular mycorrhizal fungi and the efficacy of two native isolates in a highly alkaline anthropogenic sediment - R. S. Oliveira; M. Vosátka; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2005)

Geotechnical Site Characterisation in the Umbria-Marche Area and Evaluation of Earthquake Site-Response - L. Luzi; D. Bindi; G. Franceschina; F. Pacor; R. R. Castro (Pure and Applied Geophysics, 2005)

Persistent Organochlorine Pesticide Levels in Breast Adipose Tissue in Women with Malignant and Benign Breast Tumors - S. M. Waliszewski; M. T. Bermudez; R. M. Infanzon; C. S. Silva; O. Carvajal; P. Trujillo; S. Gomez Arroyo; R. Villalobos Pietrini; V. A. Saldanña; G. Melo; S. Esquivel; F. Castro; et al. (Bulletin of Environmental Contamination and Toxicology, 2005)

Isolation and properties of a pure bacterial strain capable of fluorobenzene degradation as sole carbon and energy source - M. F. Carvalho; R. Ferreira Jorge; C. C. Pacheco; P. De Marco; P. M. L. Castro (Environmental Microbiology, 2005)
Summary A pure bacterial strain capable of aerobic biodegradation of fluorobenzene (FB) as the sole carbon and energy source was isolated by selective enrichment from sediments collected from a polluted site. 16S rRNA and fatty acid analyses support that strain F11 belongs to a novel genus within the α‐2 subgroup of the Proteobacteria, possibly within a new clade related to the order Rhizobiales . In batch cultures, growth of strain F11 on FB led to stoichiometric release of fluoride ion. Maximum experimental growth rate of 0.04 h −1 was obtained at FB concentration of 0.4 mM. Growth kinetics were described by the Luong model. An inhibitory effect with increasing FB concentrations was observed, with no growth occurring at concentrations higher than 3.9 mM. Strain F11 was shown to be able to use a range of other organic compounds, including other fluorinated compounds such as 2‐fluorobenzoate, 4‐fluorobenzoate and 4‐fluorophenol. To our knowledge, this is the first time biodegradation of FB, as the sole carbon and energy source, by a pure bacterium has been reported.

Limited nucleotide divergence over large spatial scales in the asterinid sea star Patiriella exigua - D. J. Colgan; M. Byrne; E. Rickard; L. R. Castro (Marine Biology, 2005)

High prevalence of hepatitis B virus infection among tuberculosis patients with and without HIV in Rio de Janeiro, Brazil - C. A. Blal; S. R. L. Passos; C. Horn; I. Georg; M. G. Bonecini-Almeida; V. C. Rolla; L. Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Larvae of Crystallodytes pauciradiatus (Perciformes: Creediidae) from Easter Island, South Pacific - M. F. Landaeta; G. Herrera; L. R. Castro (Journal of Fish Biology, 2005)
Larvae of Crystallodytes pauciradiatus (Creediidae) are described from 47 individuals (2·9–21·3 mm). They are elongate, slender, lightly pigmented, have prominent preopercular spines and unique small spines on the lower jaw. Early stages are restricted to the nearshore water around Easter Island, South Pacific.

El Niño–southern oscillation events and associated European winter precipitation anomalies - D. Pozo‐Vázquez; S. R. Gámiz‐Fortis; J. Tovar‐Pescador; M. J. Esteban‐Parra; Y. Castro‐Díez (International Journal of Climatology, 2005)
The winter precipitation anomalies in the European area have been analysed over the period 1900–98 based on the El Niño–Southern oscillation (ENSO) state. A set of winter and autumn ENSO events is first selected using the Sea‐Surface temperature (SST) data of the Niño 3 region, with the constraint that the ENSO event is well developed during the winter and autumn of study, and that it is an extreme event. Cold and warm ENSO events and periods that can be regarded as normal are selected. For the selected winter ENSO events and for the winter following the selected autumn ENSO events, composites of European winter precipitation anomalies have been obtained and compared with each other. A study of the consistency among events of the relationship between ENSO and precipitation anomalies was also carried out. The analysis of the winter precipitation anomalies based on the selected winter ENSO events shows the existence, for the European area and during La Niña events, of a statistically significant precipitation anomaly pattern with positive precipitation anomalies north of the British Isles and in the Scandinavian area and negative anomalies in southern Europe, resembling the precipitation pattern associated with the positive phase of the North Atlantic oscillation (NAO). Particularly, for the southwestern area of the Iberian Peninsula, the negative anomaly reaches 20% of the winter average precipitation. The consistency analysis shows that this precipitation pattern is not the result of a few major events, but rather that it is stable and qualitatively similar to that found during the positive phase of the NAO. A non‐linear response to ENSO is found in the eastern Mediterranean area: negative precipitation anomalies are found, having similar amplitude anomalies, both during El Niño and La Niña events. The analysis of the precipitation anomalies for the winter following the selected autumn ENSO events shows very similar results to those found for the previous analysis, thus suggesting the existence of a potential source of seasonal forecasting of European precipitation. An analysis of the sensitivity of the precipitation anomalies to the strength of the ENSO events shows that, when the strength of the ENSO increases, the magnitude of the rainfall anomalies does not change, but the area influenced and the coherence between events do increase slightly. Copyright © 2005 Royal Meteorological Society

High CO2 Levels in Boreholes at El Teide Volcano Complex (Tenerife, Canary Islands): Implications for Volcanic Activity Monitoring - V. Soler; J. A. Castro-Almazán; R. T. Viñas; A. Eff-Darwich; S. Sánchez-Moral; C. Hillaire-Marcel; I. Farrujia; J. Coello; J. de la Nuez; M. C. Martín; M. L. Quesada; E. Santana (Pure and Applied Geophysics, 2004)

Divergence of two forms of Triphoturus in the eastern Pacific based on mtDNA cytochrome b gene sequences and larval morphology - L. Rodríguez‐Graña; G. Herrera; L. Herrera; L. R. Castro (Journal of Fish Biology, 2004)
Divergence between two eastern Pacific forms of Triphoturus , currently considered to belong to the same species was tested by DNA sequences of the cytochrome b gene (DNA obtained from larvae collected in northern Chile and from adults in the Southern California Bight) and examination of larval characters. The number of apparently fixed substitutions (12 among 31 variable sites, out of 1001 bases) was high and the pattern of mid‐lateral trunk pigmentation in larvae also differed consistently between the two forms. The results support the separate species status for T. mexicanus (North America) and T. oculeus (Central‐South America).

Multiple Paternity in Norway Lobster ( Nephrops norvegicus L.) Assessed with Microsatellite Markers - M. L. Cancela; R. Streiff; S. Mira; M. Castro (Marine Biotechnology, 2004)

Gynogenesis Assessment Using Microsatellite Genetic Markers in Turbot ( Scophthalmus maximus ) - J. Castro; C. Bouza; L. Snchez; R. M. Cal; F. Piferrer; P. Martnez (Marine Biotechnology, 2003)

Ichthyoplankton distribution off the Peninsula de Mejillones, Chile (23° S, 71° W), under variable hydrographic conditions during the austral summer and winter of the 1997 El Niño - Laura Rodríguez-Graña; Leonardo R. Castro (Hydrobiologia, 2003)

Nesting characteristics of the olive ridley turtle ( Lepidochelys olivacea ) in Cabo Pulmo, southern Baja California - M. C. Lpez-Castro; R. Carmona; W. J. Nichols (Marine Biology, 2003)

Participatory landrace selection for on-farm conservation: An example from the Central Valleys of Oaxaca, Mexico - Mauricio R. Bellon; Julien Berthaud; Melinda Smale; José Alfonso Aguirre; Suketoshi Taba; Flavio Aragón; Jaime Díaz; Humberto Castro (Genetic Resources and Crop Evolution, 2003)

Frequent Mitochondrial Gene Rearrangements at the Hymenopteran nad3-nad5 Junction - Mark Dowton; Lyda R. Castro; Sarah L. Campbell; Sharmilla D. Bargon; Andrew D. Austin (Journal of Molecular Evolution, 2003)

Recombinagenic effect of cryptolepine inuvsH +//uvsH + anduvsH//uvsH diploid strains ofAspergillus nidulans - S. J. R. Chiuchetta; M. A. A. Castro-Prado (Folia Microbiologica, 2002)

Effects of extremely hot days on people older than 65 years in Seville (Spain) from 1986 to 1997 - Díaz J.; García R.; F. Velázquez de Castro; Hernández E.; López C.; Otero A. (International Journal of Biometeorology, 2002)

First record of the paedomorphic goby Schindleria praematura , Easter Island, South Pacific - M. F. Landaeta; R. Veas; L. R. Castro (Journal of Fish Biology, 2002)
Thirty‐five larvae and adults of the paedomophic goby Schindleria praematura were collected around Easter Island, during November 1999. Mean abundance from the five stations where they were caught ( n =26) was 10.2 ± 6.1 individuals 1000 m −3 . They occurred only in shallow areas. Oocyte counts ranged from 70 to 110. Otolith examination suggests that adults appear to live no longer than 3 months.

Morphophysiological studies on alligator gar (Atractosteus spatula) larval development as a basis for their culture and repopulation of their natural habitats - R. Mendoza; C. Aguilera; G. Rodríguez; M. González; R. Castro (Reviews in Fish Biology and Fisheries, 2002)

Total Mercury Concentrations in Lakes and Fish of Western Maryland, USA - M. S. Castro; E. N. McLaughlin; S. L. Davis; R. P. Morgan, II (Archives of Environmental Contamination and Toxicology, 2002)

Population dynamics of reintroduced forest birds on New Zealand islands - Doug P. Armstrong; R. Scott Davidson; Wendy J. Dimond; John K. Perrott; Isabel Castro; John G. Ewen; Richard Griffiths; Jason Taylor (Journal of Biogeography, 2002)
Aim We studied dynamics of four populations of New Zealand forest birds for 5–9 years after reintroduction to islands. We primarily aimed to predict whether these populations were viable, and what, if any, management was needed to maintain them. However, the small scale of these islands also provided an opportunity to study density‐dependent population growth over a short time frame. Location We studied New Zealand robin (toutouwai, Petroica australis ) and stitchbird (hihi, Notiomystis cincta ) populations reintroduced to Tiritiri Matangi, a 220‐ha offshore island near Auckland, and saddleback (tieke, Philesturnus carunculatus ) and stitchbird populations reintroduced to Mokoia, a 135‐ha island in Lake Rotorua. These islands are free of mammalian predators, but have highly modified habitat following clearing and regeneration. Methods We closely monitored each population, individually marking all or most of the birds and in some cases experimentally manipulated population density or food supply. We used model selection procedures to understand factors affecting survival, fecundity and dispersal, and developed stochastic simulation models. Results The Tiritiri Matangi robin and Mokoia saddleback populations grew without management and appear to be viable. Both showed strong evidence of density‐dependent growth, with fecundity (saddlebacks) and juvenile survival (both populations) declining with increasing density. Neither stitchbird population appears viable without management and supplementation experiments showed reproduction and/or survival to be limited by food supply. The Tiritiri Matangi population appears viable as long as supplementary feeding continues. However, the Mokoia population has a high mortality rate regardless of supplementary feeding, resulting in tenuous viability even with intensive management. Mokoia stitchbirds suffer from infection by Aspergillus fumigatus , a pathogenic fungus that is prevalent in highly modified habitats and more abundant on Mokoia than Tiritiri Matangi. Main conclusions Some forest birds can thrive in regenerating forest on islands and strong evidence of density dependence can be detected in such populations in as little as 5 years. This allows density‐dependent models to be developed, providing guidance when island populations are harvested for further translocations. Other species are limited by food supply in regenerating environments, a problem potentially overcome by management. However, prevalence of A. fumigatus may render highly modified environments uninhabitable by some species regardless of management.

An attenuation study using earthquakes from the 1997 Umbria-Marche sequence - Raúl R. Castro; Giancarlo Monachesi; Luca Trojani; Marco Mucciarelli; Massimo Frapiccini (Journal of Seismology, 2002)

Phytoremediation of polyaromatic hydrocarbons, anilines and phenols - Patricia J. Harvey; Bruno F. Campanella; Paula M. L. Castro; Hans Harms; Eric Lichtfouse; Anton R. Schäffner; Stanislav Smrcek; Daniele Werck-Reichhart (Environmental Science and Pollution Research, 2002)

A geochemical and geophysical approach to derive a conceptual circulation model of CO 2 -rich mineral waters: A case study of Vilarelho da Raia, northern Portugal - Marques J.; Monteiro Santos; Graa R.; Castro R.; Aires-Barros L.; L. Mendes Victor (Hydrogeology Journal, 2001)

Hydrogenated fish fat for grazing dairy cows in summer - M. R. Gallardo; S. E. Valtorta; P. E. Leva; H. C. Castro; J. A. Maiztegui (International Journal of Biometeorology, 2001)

The Basques according to polymorphic Alu insertions - M. de Pancorbo; López-Martínez M.; Martínez-Bouzas C.; Castro A.; Fernández-Fernández I.; G. Antúnez de Mayolo; A. Antúnez de Mayolo; P. Antúnez de Mayolo; Rowold D.; Herrera R. (Human Genetics, 2001)

Nosocomial Spread of Hepatitis B Virus in Two Hemodialysis Units, Investigated by Restriction Fragment Length Polymorphism Analysis - L. De Castro; N. M. Araujo; R. R. Sabino; F. Alvarenga; C. F. T. Yoshida; S. A. Gomes (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Behavioral and demographic changes following the loss of the breeding female in cooperatively breeding marmosets - C. Lazaro-Perea; C. S. S. Castro; R. Harrison; A. Araujo; M. F. Arruda; C. T. Snowdon (Behavioral Ecology and Sociobiology, 2000)

Effects of Disturbance on Nitrogen Export from Forested Lands of the Chesapeake Bay Watershed - Keith N. Eshleman; Robert H. Gardner; Steven W. Seagle; Nancy M. Castro; Daniel A. Fiscus; James R. Webb; James N. Galloway; Frank A. Deviney; Alan T. Herlihy (Environmental Monitoring and Assessment, 2000)

Extracellular protease of Natrialba magadii : purification and biochemical characterization - María I. Giménez; Claudia A. Studdert; Jorge J. Sánchez; R. E. De Castro (Extremophiles, 2000)

Interaction between jasmonic and gibberellic acids on in vitro tuberization of potato plantlets - Gabriela Castro; Guillermina Abdala; Cecilia Agüero; R. Tizio (Potato Research, 2000)

Removal of heavy metals from stainless steel effluents by waste biomass from Brazilian alcoholic beverage production - Maristella A. Dias; Heizir F. Castro; Patrícia F. Pimentel; Newton C.M. Gomes; Carlos A. Rosa; Valter R. Linardi (World Journal of Microbiology and Biotechnology, 2000)

Genotype and phenotype analysis of Friedreich's ataxia compound heterozygous patients - M. De Castro; J. García-Planells; E. Monrós; J. Cañizares; R. Vázquez-Manrique; J.J. Vílchez; M. Urtasun; M. Lucas; G. Navarro; G. Izquierdo; M.D. Moltó; F. Palau (Human Genetics, 2000)

Adenoviruses Encoding HPRT Correct Biochemical Abnormalities of HPRT-Deficient Cells and Allow Their Survival in Negative Selection Medium - Thomas D. Southgate; Derek Bain; Lynette D. Fairbanks; Adrian E. Morelli; Adriana T. Larregina; H. Anne Simmonds; Maria G. Castro; Pedro R. Löwenstein (Metabolic Brain Disease, 1999)

Some Results from the Hailpad Network in León (Spain): Noteworthy Correlations among Hailfall Parameters - R. Fraile; J. L. Sánchez; J. L. de la Madrid; A. Castro; J. L. Marcos (Theoretical and Applied Climatology, 1999)

Activity, feeding behaviour and diet of Ogcocephalus vespertilio in southern west Atlantic - F. Z. Gibran; R. M. C. Castro (Journal of Fish Biology, 1999)
The Brazilian batfish Ogcocephalus vespertilio is a nocturnal and early morning predator on bottom invertebrates, staying stationary and hidden in rock holes, crevices or among bottom rocks during the day. While active, it searches for prey walking along the bottom with the help of its specialized paired fins, with the illicium protracted and oscillating or exploring the substrate. The prey are either snapped up from the bottom, after visual detection, or dug out with use of the mouth and rostrum. It feeds on crustaceans (hermit crabs, true crabs, shrimps, amphipods, porcelain crabs, isopods and mysid shrimps), molluscs (snails, sea slugs and clams), polychaete worms (mostly Errantia) and echinoderms (sea urchins and brittle stars).

On the prosthetic groups of the NiFe sulfhydrogenase from Pyrococcus furiosus: topology, structure, and temperature-dependent redox chemistry - Pedro J. Silva; Baltazar de Castro; W. R. Hagen (JBIC Journal of Biological Inorganic Chemistry, 1999)

Production of amylolytic enzymes by Bacillus amyloliquefaciens in pure culture and in co-culture with Zymomonas mobilis - Carlos M. Abate; Guillermo R. Castro; Faustino Siñeriz; Danley A.S. Callieri (Biotechnology Letters, 1999)

P- and S-Wave Site Response of the Seismic Network RESNOM Determined from Earthquakes of Northern Baja California, Mexico - R. R. Castro; RESNOM Working Group (Pure and Applied Geophysics, 1998)

Use of a microquantity enzyme immunoassay in a large-scale study of measles, mumps, and rubella immunity in Italy - F. Condorelli; A. Stivala; R. Gallo; A. Marino; C. M. Battaglini; A. Messina; G. Russo; A. Castro; G. Scalia (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Repopulation and culture of the Pacific Calico scallops in Bahia Concepcion, Baja California Sur, Mexico - E.F. Felix-Pico; A. Tripp-Quezada; J.L. Castro-Ortiz; G. Serrano-Casillas; P.G. Gonzalez-Ramirez; M. Villalejo-Fuerte; R. Palomares-Garcia; F.A. Garcia-Dominguez; M. Mazon-Suastegui; G. Bojorquez-Verastica; G. Lopez-Garcia (Aquaculture International, 1997)

Validation of present-day regional climate simulations over Europe: LAM simulations with observed boundary conditions - J. H. Christensen; B. Machenhauer; R. G. Jones; C. Schär; P. M. Ruti; M. Castro; G. Visconti (Climate Dynamics, 1997)

Follow-up of mercury levels in fish, human hair and urine in the Madeira and Tapajós basins, Amazon, Brazil - O. Malm; J. R. D. Guimarães; M. B. Castro; W. R. Bastos; J. P. Viana; F. J. P. Branches; E. G. Silveira; W. C. Pfeiffer (Water, Air, & Soil Pollution, 1997)

Geographical distribution of B chromosomes in the grasshopper Eyprepocnemis plorans, along a river basin, is mainly shaped by non-selective historical events - J. Cabrero; M. D. Lo´pez–Leo´n; R. Go´mez; A. J. Castro; A. Marti´–Alganza; J. P. M. Camacho (Chromosome Research, 1997)

Direct detection of the porcine reproductive and respiratory syndrome (PRRS) virus by reverse polymerase chain reaction (RT-PCR) - P. Suárez; R. Zardoya; C. Prieto; A. Solana; E. Tabarés; J. M. Bautista; J. M. Castro (Archives of Virology, 1994)

Antipoliovirus activity of isothiazole derivatives: mode of action of 5,5?-diphenyl-3,3?-diisothiazole disulfide (DID) - A. Garozzo; M. R. Pinizzotto; F. Guerrera; G. Tempera; A. Castro; E. Geremia (Archives of Virology, 1994)

African swine fever virus - R. C. Wardley; C. de M. Andrade; D. N. Black; F. L. de Castro Portugal; L. Enjuanes; W. R. Hess; C. Mebus; A. Ordas; D. Rutili; J. Sanchez Vizcaino; J. D. Vigario; P. J. Wilkinson; et al. (Archives of Virology, 1983)

Properties of monoamine oxidase in control and Lesch-Nyhan fibroblasts - Maria R. Castro Costa; Susan B. Edelstein; Carmela M. Castiglione; Helen Chao; Xandra O. Breakefield (Biochemical Genetics, 1980)